Temporal and spatial transferability in telemetry-based dynamic species distribution models: The effects of algorithms and pseudo-absence techniques - Joshua C Wilson; Philip N Trathan; Hugh J Venables; Horst Bornemann; Rochelle Constantine; Daniel P Costa; Luciano Dalla Rosa; Louise Emmerson; Ari S Friedlaender; Michael E Goebel; Simon Goldsworthy; Mark A Hindell; et al. (Ecological Modelling, 2026)

The Matador Bug and Several Related Leaf-footed Bugs (Hemiptera: Coreidae) Accumulate Cyanogens From their Host Plants - Colin R. Morrison; Brian E. Sedio; Lawrence E. Gilbert; Justin C. Havird; Ummat Somjee (Journal of Chemical Ecology, 2026)

Heterospecific social behavior in primates: insights into the evolutionary roots of pet-keeping - Cyril C. Grueter; Fany Roncin; K. Anne-Isola Nekaris; Jill Pruetz; Richard McFarland; Sabit Hasan; Malgorzata Arlet; Timothy M. Eppley; Susan M. Cheyne; Vincent Nijman; Eckhard W. Heymann; Pascal R. Marty; et al. (Primates, 2026)
Primate interspecific interactions with both other primates and non-primate species range from predator–prey dynamics to affiliative behaviors such as grooming, play, and carrying. While many primates participate in interspecific associations or commensal relationships, to our knowledge interspecific social interactions have never been systematically synthesized. Here, we present the first comprehensive review of such interactions, compiling 427 cases from the literature, media sources, and a global survey of primatologists. These involved 88 primate species and 127 non-primate species (including mammals, birds, reptiles, amphibians, malacostracans, and insects) across wild (n = 311) and captive (n = 111) contexts. The most frequent interactions occurred within or between primate families (e.g., Cercopithecidae–Cercopithecidae, Cebidae–Atelidae), though affiliative behaviors were also directed toward distantly related taxa such as dogs and birds. Play (n = 139) and grooming (n = 136) were most common. Juveniles and infants predominantly engaged in play, while adult females were more likely to groom. Adult males were less affiliative overall. Contrary to expectations, affiliative behaviors were not more often directed toward immature than adult heterospecifics. Primates were the initiators in most interactions. These findings offer new insights into the diversity and contexts of heterospecific sociality in primates and suggest that some behavioral tendencies relevant to later forms of human–animal companionship – such as caregiving, tolerance, and exploratory play – may be more widespread among primates than previously recognized.

Assessing the efficacy of coral restoration along Florida’s coral reef under the chronic persistence of stony coral tissue loss disease - William C. Sharp; Kristene T. Parsons; Erinn M. Muller; Amanda Bourque; David S. Gilliam; Diego Lirman; Colin P. Shea; Joshua D. Voss; John H. Hunt (Frontiers in Marine Science, 2026)
Stony coral tissue loss disease (SCTLD) has caused unprecedented coral mortality across Florida’s Coral Reef (FCR) since 2014, raising concerns about whether coral restoration can succeed under chronic disease conditions and whether outplanting activities may increase disease transmission risk. As the disease transitioned from epizootic outbreak to enzootic persistence, we conducted a large-scale experimental outplanting to assess coral restoration efficacy under chronic SCTLD persistence and to evaluate the relative importance of SCTLD versus non-disease drivers of restoration outcomes. From May 2021 through April 2023, we outplanted 1,165 colonies of three SCTLD-susceptible species ( Montastraea cavernosa, Orbicella faveolata , and Pseudodiploria clivosa ) sourced from land-based facilities and in-water nurseries across six regions spanning FCR and monitored survival and disease incidence. Concurrent surveys of natural coral communities assessed whether outplanting activities affected local SCTLD prevalence. Probabilities of infection per monitoring interval remained <1-2% across all species, regions, and propagation sources throughout the monitoring period. Importantly, outplanting activities did not increase SCTLD prevalence in neighboring natural coral communities. In contrast to the low and relatively uniform disease incidence, variation in coral survival was strongly structured by ecological and operational factors. The overall coral colony survival rate at the end of the study was 77.3% but was influenced by reef stratum (inshore vs. offshore reefs), geographic region, and colony source. M. cavernosa and P. clivosa exhibited higher survival at inshore sites compared to offshore sites, whereas O. faveolata showed no consistent reef stratum effect on survival. Across FCR, survival varied spatially between regions independent of latitude, suggesting local environmental drivers. Colony source effects varied by species. M. cavernosa and P. clivosa from land-based facilities exhibited significantly lower survival than colonies from in-water nurseries, whereas O. faveolata showed no significant differences between propagation sources. Our results indicate that under SCTLD-enzootic conditions, restoration outcomes are shaped more strongly by habitat suitability, geographic context, and propagation-related factors than by SCTLD itself. These findings suggest that coral restoration can proceed within SCTLD-enzootic zones without increasing disease risk to neighboring coral communities or substantially elevating SCTLD-related mortality of outplanted colonies.

Multigenerational exposure to per- and polyfluoroalkyl substances (PFAS) negatively impacts the reproductive health of male mice - Leah Gillespie; Jacinta H. Martin; Amanda L. Anderson; Natalie A. Trigg; John E. Schjenken; Shannon P. Smyth; Ilana R. Bernstein; Simone J. Stanger; Logan McElhone; Colin C. Conine; Fay Waldrip; Erin J. Campbell; et al. (Environmental Research, 2026)

Microcystin-LR impacts viability, migration, and proliferation of the Atlantic salmon gill epithelial cell line, ASG-10: implications for tissue repair - Ensiyeh Ghanizadeh-Kazerouni; Thomais Tsoulia; Anita Solhaug; Mona C. Gjessing; Maria K. Dahle; Colin J. Brauner (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Novel Haemoproteus parasite lineage in Hooded Vultures (Necrosyrtes monachus) forms a distinct clade in Accipitriformes and highlights primer selection challenges in understudied avian hosts - Misa Shimizu; Oliver J. L. Fox; Jez Blackburn; Michael Colley; Colin Cross; Wendy James; John Jarju; Emmanuel Jatta; Naffie Sarr; Roger Walsh; Stephanie Key; Claudio Navarrete; et al. (Acta Parasitologica, 2026)

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Pregnancy Eating Attitudes-Questionnaire (PEA-Q): Longitudinal measurement invariance from early to late pregnancy in a community sample - Riley J. Jouppi; Colin E. Vize; Christine C. Call; Rebecca L. Emery Tavernier; Lydia B. Brown; Rachel P. Kolko Conlon; Jennifer L. Grace; Gina M. Sweeney; Michele D. Levine (Appetite, 2026)

Rationale and Study Protocol for the Academy of Nutrition and Dietetics’ Breastfeeding Registry Study - Allison C. Gaubert; Julie M. Long; Lindsay Woodcock; Casey R. Colin; Lauri Wright; Hanadi Hamadi; Constantina Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2026)

Projected Methane Emissions From a Boreal Thermokarst Bog Are Sensitive to Carbon Substrate Availability, Distribution, and Transport Pathway Dominance - Benjamin C. Maglio; Ruth Rutter; Valeria Briones; Andrew Mullen; Chu‐Chun Chang; Joshua M. Rady; Tobey Carman; Colin Edgar; Eugénie S. Euskirchen; Jennifer D. Watts; Susan M. Natali; Elchin E. Jafarov; et al. (Global Change Biology, 2026)
Methane is a potent greenhouse gas, which traps significantly more heat than carbon dioxide over short timescales, but remains underrepresented in models used for projecting future climate scenarios, particularly in permafrost landscapes. Understanding methane dynamics in northern wetlands is critical for improving projections of high‐latitude carbon feedbacks to the global climate system. To address this, we integrated ecological processes driving methane production, oxidation, and transport pathways into the DVM‐DOS‐TEM terrestrial biosphere model. Using long‐term site observations from a thermokarst bog in boreal Alaska, we calibrated and benchmarked the model against observations of methane and carbon dioxide fluxes, carbon and nitrogen stocks, and soil temperature and moisture. Parameter sensitivity analyses identified opposing correlations for methanogenesis and heterotrophic respiration, revealing a dependence on carbon availability. We also found sensitivity to the distribution of carbon relative to the water table position. Investigation of the dominance of different methane transport pathways demonstrated the need for observations of methane flux partitioning, and the utility in comparing simulated to observed seasonality. The cumulative methane efflux projected to the year 2100 had a range of 211–3470 g C m −2 between low and high warming scenarios. Methane emissions dominated by diffusion showed the greatest variability across projections. Increased soil temperature and carbon availability from permafrost thaw resulted in increasing methane emissions between 2030 and 2060. But methane emission was then limited by a deepening of the water table. Nevertheless, we estimated a positive radiative forcing (i.e., warming) from these mid‐century methane emissions that persisted until 2100. An ebullition‐dominant parameterization led to lower variability but a net negative radiative forcing (i.e., cooling) on average. Our study highlights the importance of representing methane emission pathways and the uncertainty associated with partitioning them on predicting the carbon budget and radiative forcing of wetland ecosystems in high latitudes.

Assessing the integration of social marketing principles in ivory demand management interventions in China and Southeast Asia - Molly R. C. Brown; Victoria K. Wells; Colin M. Beale (Conservation Biology, 2026)
Consumer demand for ivory perpetuates the unsustainable and illegal killing of African elephants and other wildlife species. Interventions that aim to change consumer behavior are increasingly recognized as a crucial element of demand management. However, poor design and implementation have limited their effectiveness. We evaluated how ivory demand‐management interventions in China and neighboring Southeast Asian countries align with best practices from the behavioral field of social marketing. Through a literature review, we identified 55 interventions conducted from 2008 to 2022. We used 2 social marketing frameworks to assess each intervention's capacity to influence behavior. We conducted semistructured interviews with 5 intervention practitioners to provide contextual grounding for our review findings. From 2018 to 2022, social marketing principles were more frequently applied and interventions were of a higher quality ( n = 26) than interventions conducted from 2008 to 2017, reflecting a growing adoption of consumer‐insight‐driven strategies. Since 2018, 7 interventions applied no social marketing principles, and 9 interventions, to varying degrees, included monitoring and evaluation. Although 13 interventions contained some theoretical considerations, these were often vague and superficial. Despite identifying a shift from experiential practices to evidence‐based approaches over time, the shift was largely restricted to communications‐based social and behavior change approaches. This left the wide range of social marketing approaches underused. Ivory demand management must improve the breadth and depth of social marketing used to contribute to long‐term elephant conservation. We suggest all consumer approaches tackling demand for wildlife meaningfully consider integrating behavioral theories in intervention design, undertake primary or secondary research to enable evidence‐led decision‐making, conduct systematic monitoring for evidence‐based learning and adaptation, and use impact and process evaluation methods to understand the mechanisms and magnitude of behavioral change following interventions.

Identification of Dolly Varden (Salvelinus malma) in the Canadian Arctic east of the Mackenzie River - Spencer Y. Weinstein; Amanda Dumond; Tracey N. Loewen; James D. Reist; Matthew C. Hale; Colin P. Gallagher; Jean-Sébastien Moore; Les N. Harris; Ross F. Tallman; Robert Bajno; Zoya A. Martin; Paul M. Craig; et al. (Environmental Biology of Fishes, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Correction: Herbivore cues and plant damage-associated compounds jointly alter seed germination and seedling herbivory - Katherine M. Overstrum; Eirette M. Santiago; Brooke A. Pellegrini; Kevin C. Headrick; Colin M. Orians; John L. Orrock; Evan L. Preisser (Oecologia, 2026)

Estimating area of occupancy for specialist oil-collecting bees: Integrating species distribution models and spatial overlays to assess extinction risk - Annalie Melin; Jonathan F. Colville; John C. Manning; Colin M. Beale (Journal of Insect Conservation, 2026)

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Basaltic island evolution close to the limits of reef growth: Norfolk Island, Southwest Pacific - Alysha M. Johnson; Mark E. Dickson; Sarah M. Hamylton; Elizabeth Johnstone; Rafael C. Carvalho; Colin D. Woodroffe (Geomorphology, 2026)

Herbivore cues and plant damage-associated compounds jointly alter seed germination and seedling herbivory - Katherine M. Overstrum; Eirette M. Santiago; Brooke A. Pellegrini; Kevin C. Headrick; Colin M. Orians; John L. Orrock; Evan L. Preisser (Oecologia, 2026)
While plant defense against herbivory is primarily thought to occur following attack, there is also evidence that plants can detect and respond to pre-attack cues. These cues include chemicals released from damaged conspecifics and kairomones, non-attack-related substances emitted by an herbivore that plants can detect and use to their benefit. It is unknown, however, whether or how plants react to the interaction of these pre-attack cues. We measured germination, growth, and herbivore susceptibility of B. nigra seedlings in an experiment that crossed the presence/absence of crushed B. nigra leaves with the presence/absence of mucus of a generalist herbivore, A. subfuscus . Seeds exposed to both crushed leaves and slug mucus germinated 8% more quickly than control seeds; neither risk cue increased germination speed when tested individually. The same pattern was found in herbivore bioassays: Spodoptera exigua ate almost 10 × more foliage from control seedlings than from seedlings exposed to both crushed leaves and slug mucus. There was no difference in the final biomass of mature plants, suggesting that plants exposed to herbivore cues early in their development can increase defense without a measurable cost in size at maturity.

Assessing mechanisms of intrinsic vulnerability in sharks occupying different marine environments - Sushmita Mukherji; Colin Simpfendorfer; Natalie Dowling; Nils C. Krueck (Biodiversity and Conservation, 2026)
The status of many shark species worldwide is concerning due to a combination of their life-history traits and widespread exposure to threats, especially fishing. However, the intrinsic vulnerability of species differ given that life-history traits vary with environmental conditions. Here, we aim to assess the links between sharks’ reproductive strategy, maximum depth recorded, and environment occupied (shelf, deepwater and pelagic) to investigate the varying levels of intrinsic vulnerability of different shark species. We find that shelf habitats are dominated by placental viviparous species that rarely occupy other environments. In contrast, oviparous species are found in both shelf and deep-sea habitats but are absent from pelagic environments due to a lack of substrate for egg deposition. Importantly, oviparous species reveal a significantly lower maximum size, size at birth, size at maturity as well as continuous reproduction, all of which are indicators of relatively high productivity and thus lower intrinsic vulnerability. In comparison, placental viviparous species reveal a larger maximum size, size at birth, size at maturity as well as annual or biennial reproduction. These life-history traits are indicative of lower productivity and thus higher intrinsic vulnerability of this dominant species group in shelf habitats where fishing mortality is known to be high. In consequence, placental viviparous species reveal higher proportion of species listed as threatened (VU, EN, CR) in the International Union for Conservation of Nature (IUCN) Red List compared to oviparous species. However, threats to deep-sea oviparous as well as to aplacental and lecithotrophic viviparous species (which are also abundant in deeper waters) are likely to increase in future due to the expansion of fisheries into open ocean and deeper waters. Although key life-history traits of deep-sea oviparous shark species are indicative of relatively higher productivity, these species have evolved under lower levels of primary productivity and predation risk characteristic of deeper waters. Slower growth and low natural mortality in deep sea oviparous species mean that the risk of population depletion is still high when mortality levels are elevated. Therefore, these findings underscore the importance of adopting precautionary and proactive strategies for sharks inhabiting deep-water environments.

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Forest breaks improve employees’ health and attitudes towards work - Daniel P. Longman; Yvanna Todorova; Nicolette C. Bishop; Janine K. Coates; Lewis J. James; Adelina Lintuluoto; Colin N. Shaw (Urban Forestry & Urban Greening, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Discharge and nutrients interact to determine trophic structure in a wetland: Evidence from a landscape‐scale manipulation - Marco Fernandez; Joel C. Trexler; Colin J. Saunders; Judson W. Harvey; Nathan J. Dorn (Limnology and Oceanography, 2025)
Identifying drivers of consumer biomass patterns and community structure is complex for managed freshwater ecosystems that are sensitive to nutrients and drought. In the Florida Everglades, flow restoration is expected to reintroduce discharge across an expansive wetland, yet most research on consumers has focused on water depth and dry disturbances. Low‐velocity flow can mediate nutrient availability for basal food resources, but its scaled‐up effects on consumer communities remain largely untested. We quantified consumer responses to a landscape‐scale flow manipulation that created discharge variability along a 2.5‐km path of interconnected shallow sloughs. Over 4 yr, we repeatedly sampled macroinvertebrates, small fishes, and large predatory fishes (standard length > 8 cm) in 26 sloughs—some along a flow path experiencing pulsed water releases and others in two non‐flowing reference areas. We tested the effects of antecedent discharge on consumer biomass while accounting for local nutrient concentrations (total phosphorus). Discharge increased biomass across all consumer groups, particularly in oligotrophic sloughs. Conversely, eutrophic sloughs demonstrated stronger top‐down effects on small fishes and macroinvertebrates, with discharge primarily benefiting large predatory fishes. Nutrient gradients preferentially increased large fishes and caused macroinvertebrate community shifts favoring herbivorous and possibly predation‐resistant taxa. Structural equation modeling similarly indicated bottom‐up support from discharge but stronger top‐down control in nutrient‐rich sloughs. These findings demonstrate that discharge and total phosphorus interactively produce distinct consumer biomass patterns. Flow restoration in oligotrophic Everglades sloughs is hypothesized to enhance aquatic consumer biomass across trophic levels, revealing an ecological benefit to slow‐flowing ecosystems not previously recognized.

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

From Attitude to Action: Unpacking Nutrition Care Process Attitudes Among Dietetics Educators and Preceptors - L. LaBonte; C. Papoutsakis; S. Lewis; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

Development of Targeted Training Programs Through Exploration of Barriers and Enablers for the Use of the Nutrition Care Process Among a Diverse Sample of Registered Dietitian/Nutritionists - I. Asare; L. Wright; C. Papoutsakis; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

Improving Outcomes in End Stage Renal Disease: The Nutrition Care Process and Impactful Care Plans – the Augment Study - G. Hultin; H. Hamadi; C. Colin; E. Jimenez; G. Proaño; L. Woodcock; J. Vergili; C. Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2025)

Current Views on Addressing Nutritional Concerns in Adult Cystic Fibrosis Patients from Practicing Registered Dietitians - C. West; M. Kay; P. Davidson; L. Wright; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2025)

A novel load testing method for condition assessment of network-level highway bridges using moving artificial truck fleets in an open traffic environment - Junyong Zhou; Qingpeng Zheng; Tang Tang; Bin Wei; Xiaoyi Zhou; Colin C. Caprani (Engineering Structures, 2025)

Wave impacts on vertical cliffs: Insights from laboratory experiments and field observations - Yaxiong Shen; Colin N. Whittaker; Catriona F. Thompson; Alison C. Raby; Adam P. Young; Mark E. Dickson (Coastal Engineering, 2025)

Priorities, concerns, and potential compromises amongst urban forest stakeholders: international lessons from Aotearoa New Zealand - Thomas F. Carlin; Tim Barnard; Toby Chapman; Justin Morgenroth; Daniel R. Richards; Robyn Simcock; Jonathon Avery; Zoë Avery; Yvette Dickinson; Kate Elliot; Claire Freeman; Derek Hayes; et al. (Urban Ecosystems, 2025)
Urban forests provide numerous benefits including habitat for wildlife, improving human health, purifying air and water, and preventing and mitigating the effects of climate change. The need to protect and improve our urban forests will only increase as populations increase and cities densify and expand over time. However, urban forest establishment and maintenance is challenging due to a lack of effective policies, delays, lack of communication, inappropriate targets, and lack of recognition, disunity, or resourcing amongst stakeholders. Here we present the results from a joint urban forest symposium-workshop that sought to determine the priorities and challenges of different stakeholder groups in New Zealand, including arborists, ecologists, non-ecologist researchers, indigenous peoples, and planners. We synthesise these lessons as recommendations to improve urban forest planning, design, establishment, and minimise conflicts between stakeholder groups. While the highest priorities of each stakeholder group are fairly distinct, there are high levels of overlap in the general priorities and challenges they face in working towards advancing those priorities. We suggest a 3-phase framework to deliver progress that broadly considers (1) data collection, (2) policy development, and (3) resource development. We suggest this framework should be supported by continual monitoring and data sharing, an increased investment in green employment and education, and further recognition of urban foresters, indigenous communities, and ecologists. We suggest that an inclusive approach based on a shared understanding of forest values and removing barriers is most likely to result in long-term success.

Tracking Road Salt Contamination Through Community Monitoring: Annual Surface Water Chloride Trends in Streams of a Major Urban Area, the Vancouver Lower Mainland, B.C., Canada - Clare L. Kilgour; Carley E. Winter; Colin J. Brauner; Ana M. Chará-Serna; Alan C. James; Nicola C. Kroetsch; Patricia M. Schulte; Chris M. Wood (Archives of Environmental Contamination and Toxicology, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

A novel insertion/deletion in APC promotor 1B is associated with both gastric and colon polyposis - Frankie Fann; Marcy Richardson; Douglas Riegert-Johnson; Colin C. Young; Brittany F. Sears (Familial Cancer, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Symbiodiniaceae and Bacterial Microbiome Dynamics Differentially Impact the Survival of Dominant Reef‐Flat Porites Corals - Colin Lock; Therese C. Miller; Colin J. Anthony; Héloïse Rouzé; James Fifer; Grace McDermott; Carlos A. Tramonte; Loreto Paulino; Sarah W. Davies; Laurie Raymundo; Bastian Bentlage (Environmental Microbiology, 2025)
Coral reefs face significant threats across the globe, prompting a surge in restoration efforts aimed at mitigating their global decline. The health, resilience, and adaptability of corals are greatly influenced by their microbial communities, and while the response of coral microbiomes to many environmental stressors has been extensively studied, less is known about their natural dynamics following transplantation, which is an essential process for restoring degraded reef habitats. In this study, we integrated DNA metabarcoding (16S & ITS2) with ecological monitoring to investigate the dynamics of Symbiodiniaceae and bacterial communities in two dominant coral spp., Porites lobata and Porites cylindrica , and their different colour morphs, as they underwent transplantation and an 18‐week acclimatisation period. We saw significant differences in microbial communities between the two Porites spp., outplanting sites, and individual coral colonies, as well as a colour morph‐related difference in P. lobata bacterial communities. We saw reduced relative abundances of Endozoicomonadaceae, specifically from the genus Parendozoicomonas, following transplantation. P. lobata colonies with later Symbiodiniaceae shifts (18 weeks) had lower long‐term survival. Changes in Symbiodiniaceae and bacterial communities have implications for holobiont function and colony survival, which should be considered when designing and implementing coral reef rehabilitation projects.

Chironomid-based paleotemperature reconstruction of the North Slave Region (Northwest Territories, Canada) during the Late Holocene - Colin Robertson; Nicolas Pelletier; John P. Smol; Jesse C. Vermaire (Journal of Paleolimnology, 2025)

Contribution of combined stressors on density and gene expression dynamics of the copepod Temora longicornis in the North Sea - Ilias Semmouri; Karel A. C. De Schamphelaere; Filip Van Nieuwerburgh; Dieter Deforce; Colin R. Janssen; Jana Asselman (Molecular Ecology, 2025)
The impact of multiple environmental and anthropogenic stressors on the marine environment remains poorly understood. Therefore, we studied the contribution of environmental variables to the densities and gene expression of the dominant zooplankton species in the Belgian part of the North Sea, the calanoid copepod Temora longicornis . We observed a reduced density of copepods, which were also smaller in size, in samples taken from nearshore locations when compared to those obtained from offshore stations. To assess the factors influencing the population dynamics of this species, we applied generalised additive models. These models allowed us to quantify the relative contribution of temperature, nutrient levels, salinity, turbidity, concentrations of photosynthetic pigments, as well as chemical pollutants such as polychlorinated biphenyls and polycyclic aromatic hydrocarbons (PAHs), on copepod density. Temperature and Secchi depth, a proxy for turbidity, were the most important environmental variables predicting the densities of T. longicornis , followed by summed PAH and chlorophyll concentrations. Analysing gene expression in field‐collected adults, we observed significant variation in metabolic and stress‐response genes. Temperature correlated significantly with genes involved in proteolytic activities, and encoding heat shock proteins. Yet, concentrations of anthropogenic chemicals did not induce significant differences in the gene expression of genes involved in the copepod's fatty acid metabolism or well‐known stress‐related genes, such as glutathione transferases or cytochrome P450. Our study highlights the potential of gene expression biomonitoring and underscores the significance of a changing environment in future studies.

Specificity database for bacterial pesticidal proteins against invertebrate targets - Colin Berry; Victoria Valby; Ruchir Mishra; Bryony C. Bonning; Leopoldo Palma; Neil Crickmore (Journal of Invertebrate Pathology, 2025)

Exposure and health risks of benzene from combustion by gas stoves: A modelling approach in U.S. homes - Anchal Garg; Yannai Kashtan; Metta Nicholson; Colin J. Finnegan; Eric D. Lebel; Drew R. Michanowicz; Seth B.C. Shonkoff; Kari C. Nadeau; Robert B. Jackson (Journal of Hazardous Materials, 2025)

Sites of Special Scientific Interest: Their role and importance in conserving England's geoheritage - Colin D. Prosser; Hannah C. Townley (Proceedings of the Geologists' Association, 2025)

Evaluating five shoreline change models against 40 years of field survey data at an embayed sandy beach - Oxana Repina; Rafael C. Carvalho; Giovanni Coco; José A.Á. Antolínez; Iñaki de Santiago; Mitchell D. Harley; Camilo Jaramillo; Kristen D. Splinter; Sean Vitousek; Colin D. Woodroffe (Coastal Engineering, 2025)

Combined rupture mechanisms of shallow foundations: implications in limit state design - Luca P. Argani; Alessandro Gajo; Colin C. Smith (European Journal of Environmental and Civil Engineering, 2025)

Integration of genetic, taxonomic, and functional dimensions of biodiversity yields conservation insights - Carla L. Atkinson; Irene Sánchez González; Jamie R. Bucholz; Garrett W. Hopper; Ryan C. Garrick; Colin R. Jackson; Jeffrey D. Lozier (Biological Conservation, 2025)

Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.

Biocrust Mosses and Cyanobacteria Exhibit Distinct Carbon Uptake Responses to Variations in Precipitation Amount and Frequency - Kristina E. Young; Osvaldo Sala; Anthony Darrouzet‐Nardi; Colin Tucker; Rebecca Finger‐Higgens; Megan Starbuck; Sasha C. Reed (Ecology Letters, 2025)
Dryland organisms exhibit varied responses to changes in precipitation, including event size, frequency, and soil moisture duration, influencing carbon uptake and reserve management strategies. This principle, central to the pulse‐reserve paradigm, has not been thoroughly evaluated in biological soil crusts (biocrusts), essential primary producers on dryland surfaces. We conducted two experiments to investigate carbon uptake in biocrusts under different precipitation regimes. In the first, we applied a gradient of watering amounts to biocrusts dominated by moss or cyanobacteria, hypothesising distinct pulse‐response strategies. The second experiment extended watering treatments over three months, varying pulse size and frequency. Our results revealed distinct carbon uptake patterns: moss crusts exhibited increased CO 2 uptake with larger, less frequent watering events, whereas cyanobacteria crusts maintained similar carbon uptake across all event sizes. These findings suggest divergent pulse‐response strategies across biocrust types, with implications for modelling dryland carbon dynamics and informing land management under changing precipitation regimes.

Limited persistence of the heat-tolerant zooxanthella, Durusdinium trenchii, in corals transplanted to a barrier reef where it is rare among natal colonies - Kira E. Turnham; Allison M. Lewis; Dustin W. Kemp; Mark E. Warner; Drew F. Wham; Robin T. Smith; Kenneth Hoadley; Patrick L. Colin; Yimnang Golbuu; Todd C. LaJeunesse (Coral Reefs, 2025)

Nuance in the Narrative of a Brown Poison Frog: Environmental Alkaloids and Specialized Foraging in a Presumed Toxin-Free and Diet-Generalized Species - Jeffrey L. Coleman; Steven Y. Wang; Paul E. Marek; Colin R. Morrison; Brian E. Sedio; David C. Cannatella (Journal of Chemical Ecology, 2025)

Increasingly Seasonal Jet Stream Raises Risk of Co‐Occurring Flooding and Extreme Wind in Great Britain - John K. Hillier; Hannah C. Bloomfield; Colin Manning; Freya Garry; Len Shaffrey; Paul Bates; Dhirendra Kumar (International Journal of Climatology, 2025)
Insurers and risk managers for critical infrastructure such as transport or power networks typically do not account for flooding and extreme winds happening at the same time in their quantitative risk assessments. We explore this potentially critical underestimation of risk from these co‐occurring hazards through studying events using the regional 12 km resolution UK Climate Projections for a 1981–1999 baseline and projections of 2061–2079 (RCP8.5). We create a new wintertime (October–March) set of 3427 wind events to match an existing set of fluvial flow extremes and design innovative multi‐event e pisodes (Δ t of 1–180 days long) that reflect how periods of adverse weather affect society (e.g., through damage). We show that the probability of co‐occurring wind‐flow episodes in Great Britain (GB) is underestimated 2–4 times if events are assumed independent. Significantly, this underestimation is greater both as severity increases and episode length reduces, highlighting the importance of considering risk from closely consecutive storms (Δ t ~ 3 days) and the most severe storms. In the future (2061–2079), joint wind‐flow extremes are twice as likely as during 1981–1999. Statistical modelling demonstrates that changes may significantly exceed thermodynamic expectations of higher river flows in a wetter future climate. The largest co‐occurrence increases happen in mid‐winter (DJF) with changes in the North Atlantic jet stream an important driver; we find the jet is strengthened and squeezed into a southward‐shifted latitude window (45°–50° N) giving typical future conditions that match instances of high flows and joint extremes impacting GB today. This strongly implies that the large‐scale driving conditions (e.g., jet stream state) for a multi‐impact ‘perfect storm’ will vary by country; understanding regional drivers of weather hazards over climate timescales is vital to inform risk mitigation and planning (e.g., diversification and mutual aid across Europe).

Investigating chemical risk in green and loggerhead turtles foraging in Moreton Bay using species-specific cell-based bioassays - Janelle C. Kenney; Dylan White-Kiely; Jason P. van de Merwe; Colin J. Limpus; Kimberly A. Finlayson (Marine Pollution Bulletin, 2025)

Quaternary rivers, tufas and mires of southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; Colin A. Whiteman; B. Andrew Haggart; David R. Bridgland; Ella Egberts; Michael J. Grant; Marcus Hatch; Peter G. Knowles; Danielle C. Schreve; Philip S. Toms; Francis F. Wenban-Smith; Mark J. White (Proceedings of the Geologists' Association, 2025)

Quaternary sea level landforms and sediments in southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; B. Andrew Haggart; Danielle C. Schreve; Colin A. Whiteman (Proceedings of the Geologists' Association, 2025)

A Comprehensive Survey of 2024 Funding for Radiation Oncology Visiting Medical Student Electives - Drew T. Bergman; Colin J. McNamara; Alexys C. Gayne; Charles R. Jr. Thomas; Nirav S. Kapadia (Journal of Cancer Education, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Soil Nitrogen Supply Exerts Largest Influence on Leaf Nitrogen in Environments with the Greatest Leaf Nitrogen Demand - Alissar Cheaib; Elizabeth F. Waring; Risa McNellis; Evan A. Perkowski; Jason P. Martina; Eric W. Seabloom; Elizabeth T. Borer; Peter A. Wilfahrt; Ning Dong; Iain Colin Prentice; Ian J. Wright; Sally A. Power; et al. (Ecology Letters, 2025)
Accurately representing the relationships between nitrogen supply and photosynthesis is crucial for reliably predicting carbon–nitrogen cycle coupling in Earth System Models (ESMs). Most ESMs assume positive correlations amongst soil nitrogen supply, leaf nitrogen content, and photosynthetic capacity. However, leaf photosynthetic nitrogen demand may influence the leaf nitrogen response to soil nitrogen supply; thus, responses to nitrogen supply are expected to be the largest in environments where demand is the greatest. Using a nutrient addition experiment replicated across 26 sites spanning four continents, we demonstrated that climate variables were stronger predictors of leaf nitrogen content than soil nutrient supply. Leaf nitrogen increased more strongly with soil nitrogen supply in regions with the highest theoretical leaf nitrogen demand, increasing more in colder and drier environments than warmer and wetter environments. Thus, leaf nitrogen responses to nitrogen supply are primarily influenced by climatic gradients in photosynthetic nitrogen demand, an insight that could improve ESM predictions.

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

Data fusion for enhancing urban air quality modeling using large-scale citizen science data - Anna C. O'Regan; Henrik Grythe; Stig Hellebust; Susana Lopez-Aparicio; Colin O'Dowd; Paul D. Hamer; Gabriela Sousa Santos; Marguerite M. Nyhan (Sustainable Cities and Society, 2024)

Forever chemicals don't make hero mutant ninja turtles: Elevated PFAS levels linked to unusual scute development in newly emerged freshwater turtle hatchlings (Emydura macquarii macquarii) and a reduction in turtle populations - David J. Beale; Duncan Limpus; Georgia Sinclair; Utpal Bose; Nicholas Bourne; Sally Stockwell; Damian C. Lettoof; Rohan Shah; Thao V. Nguyen; Viviana Gonzalez-Astudillo; Christoph Braun; Albert Myburgh; et al. (Science of The Total Environment, 2024)

An investigation of an outbreak of Salmonella Typhimurium infections linked to cantaloupe – United States, 2022 - Sharon Seelman Federman; Erin Jenkins; Cullen Wilson; Arturo DeLaGarza; Colin Schwensohn; Benjamin Schneider; Johnson Nsubuga; Robert Literman; Allison Wellman; Brooke M. Whitney; Rebecca L. Bell; Kerri Harris-Garner; et al. (Food Control, 2024)

Environmental Change Drivers Reduce Sapling Layer Diversity in Sugar Maple-Beech Forests of Eastern North America - Michael R. Zarfos; Gregory B. Lawrence; Colin M. Beier; Blair D. Page; Todd C. McDonnell; Timothy J. Sullivan; Mariann T. Garrison-Johnston; Martin Dovciak (Ecosystems, 2024)

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Muhammed A. Oyinlola; Mostafa Khorsandi; Noa B. Mayer; Natalie Butler; Jacey C. Van Wert; Erika J. Eliason; Richard Arsenault; Colin J. Brauner; Scott G. Hinch; Andre St-Hilaire (Climatic Change, 2024)

Chemical characterization and biological activity of Curvularia Lunata, an endophytic fungus isolated from lemongrass (Cymbopogon citratus) - Mehak Kaur; Rahul C. Mishra; Vaibhavi Lahane; Anita Kumari; Akhilesh K. Yadav; Monika Garg; Colin J. Barrow; Mayurika Goel (Brazilian Journal of Microbiology, 2024)

A genome assembly and transcriptome atlas of the inbred Babraham pig to illuminate porcine immunogenetic variation - John C. Schwartz; Colin P. Farrell; Graham Freimanis; Andrew K. Sewell; John D. Phillips; John A. Hammond (Immunogenetics, 2024)
The inbred Babraham pig serves as a valuable biomedical model for research due to its high level of homozygosity, including in the major histocompatibility complex (MHC) loci and likely other important immune-related gene complexes, which are generally highly diverse in outbred populations. As the ability to control for this diversity using inbred organisms is of great utility, we sought to improve this resource by generating a long-read whole genome assembly and transcriptome atlas of a Babraham pig. The genome was de novo assembled using PacBio long reads and error-corrected using Illumina short reads. Assembled contigs were then mapped to the porcine reference assembly, Sscrofa11.1, to generate chromosome-level scaffolds. The resulting TPI_Babraham_pig_v1 assembly is nearly as contiguous as Sscrofa11.1 with a contig N50 of 34.95 Mb and contig L50 of 23. The remaining sequence gaps are generally the result of poor assembly across large and highly repetitive regions such as the centromeres and tandemly duplicated gene families, including immune-related gene complexes, that often vary in gene content between haplotypes. We also further confirm homozygosity across the Babraham MHC and characterize the allele content and tissue expression of several other immune-related gene complexes, including the antibody and T cell receptor loci, the natural killer complex, and the leukocyte receptor complex. The Babraham pig genome assembly provides an alternate highly contiguous porcine genome assembly as a resource for the livestock genomics community. The assembly will also aid biomedical and veterinary research that utilizes this animal model such as when controlling for genetic variation is critical.

Advancing an integrated understanding of land–ocean connections in shaping the marine ecosystems of coastal temperate rainforest ecoregions - Brian P. V. Hunt; Simone Alin; Allison Bidlack; Heida L. Diefenderfer; Jennifer M. Jackson; Colleen T. E. Kellogg; Peter Kiffney; Kyra A. St. Pierre; Eddy Carmack; William C. Floyd; Eran Hood; Alexander R. Horner‐Devine; et al. (Limnology and Oceanography, 2024)
Land and ocean ecosystems are strongly connected and mutually interactive. As climate changes and other anthropogenic stressors intensify, the complex pathways that link these systems will strengthen or weaken in ways that are currently beyond reliable prediction. In this review we offer a framework of land–ocean couplings and their role in shaping marine ecosystems in coastal temperate rainforest (CTR) ecoregions, where high freshwater and materials flux result in particularly strong land–ocean connections. Using the largest contiguous expanse of CTR on Earth—the Northeast Pacific CTR (NPCTR)—as a case study, we integrate current understanding of the spatial and temporal scales of interacting processes across the land–ocean continuum, and examine how these processes structure and are defining features of marine ecosystems from nearshore to offshore domains. We look ahead to the potential effects of climate and other anthropogenic changes on the coupled land–ocean meta‐ecosystem. Finally, we review key data gaps and provide research recommendations for an integrated, transdisciplinary approach with the intent to guide future evaluations of and management recommendations for ongoing impacts to marine ecosystems of the NPCTR and other CTRs globally. In the light of extreme events including heatwaves, fire, and flooding, which are occurring almost annually, this integrative agenda is not only necessary but urgent.

Past fire dynamics in sub-Saharan Africa during the last 25,000 years: Climate change and increasing human impacts - Laurent Bremond; Julie C. Aleman; Charly Favier; Olivier Blarquez; Daniele Colombaroli; Simon E. Connor; Carlos E. Cordova; Colin Courtney-Mustaphi; Abraham N. Dabengwa; Graciela Gil-Romera; William D. Gosling; Tamryn Hamilton; et al. (Quaternary International, 2024)

A mechanistic modeling and estimation framework for environmental pathogen surveillance - Matthew Wascher; Colin J. Klaus; Chance Alvarado; Jenny Panescu; Mikkel Quam; Karen C. Dannemiller; Joseph H. Tien (Mathematical Biosciences, 2024)

Thermodynamic properties and revised Helgeson-Kirkham-Flowers equations of state parameters of the hydrated and dehydrated monomeric silica species at t = 0.01–600oC, P = 1–3000 bars, ρH2O = 0.35–1.1 g cm−3, and I = 0 m - Colin S. Walker; Randy C. Arthur; Sohtaro Anraku; Hiroshi Sasamoto; Morihiro Mihara (Applied Geochemistry, 2024)

Student Exposure to ANDHII Part II: Improved Confidence with Applying the Nutrition Care Process Across Cohorts - C. Colin; L. Woodcock (Journal of the Academy of Nutrition and Dietetics, 2024)

Exploration of Barriers and Enablers for the Use of the Nutrition Care Process Among a Diverse Sample of Registered Dietitians/ Nutritionists - I. Asare; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2024)

The Language of Lactation: Decoding RDNs’ Practice Patterns to Enhance Nutrition Care of Breastfeeding Dyads - A. Gaubert; J. Long; L. Woodcock; C. Colin; L. Wright; C. Papoutsakis (Journal of the Academy of Nutrition and Dietetics, 2024)

Challenges Patients Face When Transitioning from the Hospital into the Home Setting with an Enteral Feeding Tube and the Impact of Staffing a Home Enteral Nutrition Registered Dietitian Case Manager - N. Worthen; S. Lewis; L. Wright; A. Arikawa; C. Colin (Journal of the Academy of Nutrition and Dietetics, 2024)

Examining the sensitivity of ozone to NOx and VOCs in the Salt Lake City urban region from spatiotemporal patterns observed using stationary and mobile observations collected from a light-rail public transit platform - Andres Gonzalez; Derek Mallia; John C. Lin; Logan Mitchell; Taylor Y. Wilmot; Nancy Daher; Mark Sghiatti; Colin Harkins (Atmospheric Environment, 2024)

Gill raker and pyloric caeca counts differ between Arctic char ( Salvelinus alpinus ) and Dolly Varden ( S. malma ) populations across their ranges - Spencer Y. Weinstein; Colin P. Gallagher; Matthew C. Hale; Tracey N. Loewen; James D. Reist; Heidi K. Swanson (Journal of Fish Biology, 2024)
Meristic characters are often used to differentiate between closely related forms, morphs, and species of fishes, and lend insight into ecology and post‐glacial recolonization in taxa with complicated or contentious phylogenies, including the genus Salvelinus . Previous studies of meristics in Salvelinus have focused mostly on individual populations. We collated data from 456 populations/systems across the North American and Russian Arctic and sub‐Arctic, and found that counts of pyloric caeca and gill rakers differed consistently between fish visually and/or genetically identified as Arctic char and Dolly Varden across their distributional ranges.

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Assessing the risk of climate maladaptation for Canadian polar bears - L. Ruth Rivkin; Evan S. Richardson; Joshua M. Miller; Todd C. Atwood; Steven Baryluk; Erik W. Born; Corey Davis; Markus Dyck; Evelien de Greef; Kristin L. Laidre; Nicholas J. Lunn; Sara McCarthy; et al. (Ecology Letters, 2024)
The Arctic is warming four times faster than the rest of the world, threatening the persistence of many Arctic species. It is uncertain if Arctic wildlife will have sufficient time to adapt to such rapidly warming environments. We used genetic forecasting to measure the risk of maladaptation to warming temperatures and sea ice loss in polar bears ( Ursus maritimus ) sampled across the Canadian Arctic. We found evidence for local adaptation to sea ice conditions and temperature. Forecasting of genome‐environment mismatches for predicted climate scenarios suggested that polar bears in the Canadian high Arctic had the greatest risk of becoming maladapted to climate warming. While Canadian high Arctic bears may be the most likely to become maladapted, all polar bears face potentially negative outcomes to climate change. Given the importance of the sea ice habitat to polar bears, we expect that maladaptation to future warming is already widespread across Canada.

Reconstructing 120 years of climate change impacts on Joshua tree flowering - Jeremy B. Yoder; Ana Karina Andrade; Lesley A. DeFalco; Todd C. Esque; Colin J. Carlson; Daniel F. Shryock; Ray Yeager; Christopher I. Smith (Ecology Letters, 2024)
Quantifying how global change impacts wild populations remains challenging, especially for species poorly represented by systematic datasets. Here, we infer climate change effects on masting by Joshua trees ( Yucca brevifolia and Y. jaegeriana ), keystone perennials of the Mojave Desert, from 15 years of crowdsourced observations. We annotated phenophase in 10,212 geo‐referenced images of Joshua trees on the iNaturalist crowdsourcing platform, and used them to train machine learning models predicting flowering from annual weather records. Hindcasting to 1900 with a trained model successfully recovers flowering events in independent historical records and reveals a slightly rising frequency of conditions supporting flowering since the early 20th Century. This reflects increased variation in annual precipitation, which drives masting events in wet years—but also increasing temperatures and drought stress, which may have net negative impacts on recruitment. Our findings reaffirm the value of crowdsourcing for understanding climate change impacts on biodiversity.

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Evidence for the differential efficacy of yaw and pitch gaze stabilization mechanisms in people with multiple sclerosis - Colin R. Grove; Brian J. Loyd; Leland E. Dibble; Michael C. Schubert (Experimental Brain Research, 2024)

Metabolic disruptions and impaired reproductive fitness in wild-caught freshwater turtles (Emydura macquarii macquarii) exposed to elevated per- and polyfluoroalkyl substances (PFAS) - David J. Beale; Thao V. Nguyen; Utpal Bose; Rohan Shah; Joost Laurus Dinant Nelis; Sally Stockwell; James A. Broadbent; Sandra Nilsson; Rahul Rane; Leon Court; Damian C. Lettoof; Gunjan Pandey; et al. (Science of The Total Environment, 2024)

When is it safe to go home? Post-predation assessment of risk and safety when personal information conflicts with social cues - Brian D. Wisenden; Cat M. Adkins; Seth A. Campbell; Shree Chakraborty; Madelyn E. Cloutier; Alex D. Doebler; Kathryn A. Hanson; Lou Hoff; Molly I. M. Johnson; Philip S. Larson; Claire M. Lukasik; Zoe R. Michaelson; et al. (Behavioral Ecology and Sociobiology, 2024)

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

The telomere-to-telomere, gapless, phased diploid genome and methylome of the green alga Scenedesmus obliquus UTEX 3031 reveals significant heterozygosity and genetic divergence of the haplotypes - Thomas C. Biondi; Colin P.S. Kruse; Samuel I. Koehler; Taehyung Kwon; Aubrey K. Davis; Wyatt Eng; Yuliya Kunde; Cheryl D. Gleasner; Kayley T. You Mak; Juergen Polle; Blake T. Hovde; Erik R. Hanschen; et al. (Algal Research, 2024)

Doublesex is essential for masculinization but not feminization in Lygus hesperus - J. Joe Hull; Chan C. Heu; Roni J. Gross; Dannialle M. LeRoy; Inana X. Schutze; Daniel Langhorst; Jeffrey A. Fabrick; Colin S. Brent (Insect Biochemistry and Molecular Biology, 2024)

Correction: Primate population dynamics in Ngogo, Kibale National Park, Uganda, over nearly five decades - Colin A. Chapman; Samuel Angedakin; Thomas M. Butynski; Jan F. Gogarten; John C. Mitani; Thomas T. Struhsaker (Primates, 2024)

When Space and Time Matter in Environmental Injustice: A Bayesian Analysis of the Association between Socio-economic Disadvantage and Air Pollution in Greater Mexico City - Alejandro Lome-Hurtado; Julia Touza; Piran C. L. White; Colin J. McClean (Environmental Management, 2024)

Remote sensing-based drought hazard monitoring and assessment in a coastal plain: A principal component approach - Colins Johnny Jesudhas; Jeswin Titus C; Tirthankar Roy (Environmental Research, 2024)

Correction to: Coastal compartments: the role of sediment supply and morphodynamics in a beach management context - Rafael C. Carvalho; Colin D. Woodroffe (Journal of Coastal Conservation, 2024)

β-tubulin functions in spermatogenesis in Lygus hesperus Knight - Chan C. Heu; Kevin P. Le; Roni J. Gross; Inana X. Schutze; Dannialle M. LeRoy; Daniel Langhorst; Colin S. Brent; Jeffrey A. Fabrick; J. Joe Hull (Journal of Insect Physiology, 2024)

An updated review of the post-glacial history, ecology, and diversity of Arctic char (Salvelinus alpinus) and Dolly Varden (S. malma) - Spencer Y. Weinstein; Colin P. Gallagher; Matthew C. Hale; Tracey N. Loewen; Michael Power; James D. Reist; Heidi K. Swanson (Environmental Biology of Fishes, 2024)

Persistent net release of carbon dioxide and methane from an Alaskan lowland boreal peatland complex - Eugénie S. Euskirchen; Colin W. Edgar; Evan S. Kane; Mark P. Waldrop; Rebecca B. Neumann; Kristen L. Manies; Thomas A. Douglas; Catherine Dieleman; Miriam C. Jones; Merritt R. Turetsky (Global Change Biology, 2024)
Permafrost degradation in peatlands is altering vegetation and soil properties and impacting net carbon storage. We studied four adjacent sites in Alaska with varied permafrost regimes, including a black spruce forest on a peat plateau with permafrost, two collapse scar bogs of different ages formed following thermokarst, and a rich fen without permafrost. Measurements included year‐round eddy covariance estimates of net carbon dioxide (CO 2 ), mid‐April to October methane (CH 4 ) emissions, and environmental variables. From 2011 to 2022, annual rainfall was above the historical average, snow water equivalent increased, and snow‐season duration shortened due to later snow return. Seasonally thawed active layer depths also increased. During this period, all ecosystems acted as slight annual sources of CO 2 (13–59 g C m −2 year −1 ) and stronger sources of CH 4 (11–14 g CH 4 m −2 from ~April to October). The interannual variability of net ecosystem exchange was high, approximately ±100 g C m −2 year −1 , or twice what has been previously reported across other boreal sites. Net CO 2 release was positively related to increased summer rainfall and winter snow water equivalent and later snow return. Controls over CH 4 emissions were related to increased soil moisture and inundation status. The dominant emitter of carbon was the rich fen, which, in addition to being a source of CO 2 , was also the largest CH 4 emitter. These results suggest that the future carbon‐source strength of boreal lowlands in Interior Alaska may be determined by the area occupied by minerotrophic fens, which are expected to become more abundant as permafrost thaw increases hydrologic connectivity. Since our measurements occur within close proximity of each other (≤1 km 2 ), this study also has implications for the spatial scale and data used in benchmarking carbon cycle models and emphasizes the necessity of long‐term measurements to identify carbon cycle process changes in a warming climate.

The potential of high temporal resolution automatic measurements of PM2.5 composition as an alternative to the filter-based manual method used in routine monitoring - Marsailidh M. Twigg; Chiara F. Di Marco; Elizabeth A. McGhee; Christine F. Braban; Eiko Nemitz; Richard J.C. Brown; Kevin C. Blakley; Sarah R. Leeson; Agnieszka Sanocka; David C. Green; Max Priestman; Veronique Riffault; et al. (Atmospheric Environment, 2023)

Coastal compartments: the role of sediment supply and morphodynamics in a beach management context - Rafael C. Carvalho; Colin D. Woodroffe (Journal of Coastal Conservation, 2023)
Coastal compartments provide a hierarchical framework to manage beaches and coastal ecosystems in Australia. This study examines the individual behaviour of three adjacent beaches within Shoalhaven Bight, a secondary compartment on the south coast of New South Wales (NSW). The Shoalhaven River discharges intermittently into the northernmost of the beaches, and a fluvial component is detectable within beach and foredune sands. The distribution and orientation of headlands constrains dispersal of fluvial sediments, and results in lower wave-energy conditions further south, implying limited sand transport from one beach, or tertiary compartment, to another. Two years of monthly subaerial surveys across ten different profiles and modelled storm-wave conditions during the major storms, were used to compare the response of beach volume and shoreline position. The greatest changes in volume were observed near Shoalhaven Heads and the northern ends of Culburra and Warrain-Currarong beaches. Results indicate the distinct individual response of neighbouring beaches over the two-year period, in contrast to general trends in beach behavior that might be inferred from long-term regional monitoring programs. However, they also demonstrate the limitations of short-term observations in comparison to those longer-term studies. The NSW beach systems of are some of the best understood in the world in terms of regional behaviour, as a consequence of several decades of surveys on key beaches. However, more focused local monitoring programs may be needed to establish detailed coastal sand transport, and an understanding of intermittent delivery of fluvial sand and longshore inputs and outputs, within and between different compartments.

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Combined rupture mechanism of shallow foundations under drained conditions - Luca P. Argani; Alessando Gajo; Colin C. Smith (Computers and Geotechnics, 2023)

Primate population dynamics in Ngogo, Kibale National Park, Uganda, over nearly five decades - Colin A. Chapman; Samuel Angedakin; Thomas M. Butynski; Jan F. Gogarten; John C. Mitani; Thomas T. Struhsaker (Primates, 2023)

Revising vulnerability assessments of montane birds in the colombian páramo to account for threats from climate change - Christopher J Wheatley; Colin M Beale; Piran C L White; Adrián Villaseñor; Adriana Sanchez; Charles A Cunningham; Jane K Hill (Biodiversity and Conservation, 2023)
Tropical montane ecosystems are highly vulnerable to global climate change, but their species-level conservation vulnerability assessments generally do not incorporate climate threats. The Colombian páramo is a highly diverse montane ecosystem but it contains relatively few species currently identified as threatened on the IUCN Red List. We explore whether current assessments need revising to account for climate change threats for páramo species. We use a climate change vulnerability assessment framework to evaluate the risks and opportunities from climate change for 60 bird species within the Colombian páramo. We explore two potential climate change scenarios (RCP 2.6 and RCP 8.5), representing best and worst-case projections. We find that more than half (52–68%, depending on the scenario) of bird species will be threatened by climate change by the end of the century, but a very poor agreement between the current conservation status of species and their climate vulnerability score. We find ~ 90% of species identified as climate-threatened are not currently identified as being of conservation concern, representing a substantial new suite of priority species within the Colombian páramo. Overall, we identify up to 34 páramo bird species that are threatened by climate change but not currently listed as being of conservation concern. Similar mismatches may also occur in other montane taxa and so updating species risk assessments to account for climate change is urgently needed. Implementation of appropriate conservation actions is also needed to reduce species’ risks from climate change.

Community‐wide correlations between species richness, abundance and population genomic diversity in a freshwater biodiversity hotspot - Jamie R. Bucholz; Garrett W. Hopper; Irene Sánchez González; Taylor E. Kelley; Colin R. Jackson; Ryan C. Garrick; Carla L. Atkinson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Understanding patterns of diversity across macro (e.g. species‐level) and micro (e.g. molecular‐level) scales can shed light on community function and stability by elucidating the abiotic and biotic drivers of diversity within ecological communities. We examined the relationships among taxonomic and genetic metrics of diversity in freshwater mussels (Bivalvia: Unionidae), an ecologically important and species‐rich group in the southeastern United States. Using quantitative community surveys and reduced‐representation genome sequencing across 22 sites in seven rivers and two river basins, we surveyed 68 mussel species and sequenced 23 of these species to characterize intrapopulation genetic variation. We tested for the presence of species diversity–abundance correlations (i.e. the more‐individuals hypothesis, MIH), species‐genetic diversity correlations (SGDCs) and abundance‐genetic diversity correlations (AGDCs) across all sites to evaluate relationships between different metrics of diversity. Sites with greater cumulative multispecies density (a standardized metric of abundance) had a greater number of species, consistent with the MIH hypothesis. Intrapopulation genetic diversity was strongly associated with the density of most species, indicating the presence of AGDCs. However, there was no consistent evidence for SGDCs. Although sites with greater overall densities of mussels had greater species richness, sites with higher genetic diversity did not always exhibit positive correlations with species richness, suggesting that there are spatial and evolutionary scales at which the processes influencing community‐level diversity and intraspecific diversity differ. Our work reveals the importance of local abundance as indicator (and possibly a driver) of intrapopulation genetic diversity.

Grassroots Advancement of the Dietetics Profession Through Student Access to ANDHII - C. Colin; A. Mustafa (Journal of the Academy of Nutrition and Dietetics, 2023)

Obituary for Dr. Avijit Gupta (1942–2023) - Gerald C. Nanson; Colin D. Woodroffe (Geomorphology, 2023)

An investigation of an outbreak of Salmonella Newport infections linked to melons – United States, 2020 - Erin Jenkins; Ifueko Gardenhire; Brooke M. Whitney; Krystalyn B. Martin; Colin Schwensohn; Laura Gieraltowski; Molly M. Leeper; Vivien McCurdy; Monica McClure; Allison Wellman; Arthur Pightling; Michelle Smith; et al. (Food Control, 2023)

Experimental investigation on the shear behaviour of the brickwork-backfill interface in masonry arch bridges - Bowen Liu; Anastasios Drougkas; Vasilis Sarhosis; Colin C. Smith; Matthew Gilbert (Engineering Structures, 2023)

Guitarfishes are plucked: Undermanaged in global fisheries despite declining populations and high volume of unreported international trade - C. Samantha Sherman; Colin A. Simpfendorfer; Alifa B. Haque; Eric D. Digel; Patrick Zubick; Jonathan Eged; Jay H. Matsushiba; Glenn Sant; Nicholas K. Dulvy (Marine Policy, 2023)

Spatial and temporal variations of seabed sediment characteristics in the inner Louisiana shelf - Wenqiang Zhang; Kehui Xu; Colin Herke; Omar Alawneh; Navid Jafari; Kanchan Maiti; Patrick O. Clower; Cassandra N. Glaspie; Jillian C. Tupitza; Z. George Xue (Marine Geology, 2023)

Assessing Nutrition Knowledge, Diet Quality, and Physical Activity in Student Veterans - L. Robinson; C. Colin; K. Smith; M. Greene; A. Frugé (Journal of the Academy of Nutrition and Dietetics, 2023)

Use of an Escape Room to Enhance Skills and Self-efficacy Utilizing the Nutrition Care Process - I. Asare; L. Wright; C. Colin; M. Harris (Journal of the Academy of Nutrition and Dietetics, 2023)

Defining the in vivo mechanism of air pollutant toxicity using murine stress response biomarkers - Francisco Inesta-Vaquera; Lisa Miyashita; Jonathan Grigg; Colin J. Henderson; C. Roland Wolf (Science of The Total Environment, 2023)

Quantification of wetland vegetation communities features with airborne AVIRIS-NG, UAVSAR, and UAV LiDAR data in Peace-Athabasca Delta - Chao Wang; Tamlin M. Pavelsky; Ethan D. Kyzivat; Fenix Garcia-Tigreros; Erika Podest; Fangfang Yao; Xiao Yang; Shuai Zhang; Conghe Song; Theodore Langhorst; Wayana Dolan; Martin R. Kurek; et al. (Remote Sensing of Environment, 2023)

Evaluating the sustainability of the 2017 US biofuel industry with an integrated techno-economic analysis and life cycle assessment - Jack P. Smith; Braden J. Limb; Colin M. Beal; Kelly R. Banta; John L. Field; Steven J. Simske; Jason C. Quinn (Journal of Cleaner Production, 2023)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

Millimetre‐scale pollen analysis of non‐varved lacustrine sediments from Onepoto maar palaeolake, Auckland, reveals distal vegetation responses and landscape recovery following the ~25.5‐ka Ōruanui supereruption, New Zealand - Stephen B. Piva; Simon J. Barker; Rewi M. Newnham; Andrew B. H. Rees; Colin J. N. Wilson; Lionel Carter; Nels A. Iverson; Benjamin Läuchli; Paul C. Augustinus (Journal of Quaternary Science, 2023)
The ~25.5‐ka Ōruanui supereruption (Taupō volcano, New Zealand) erupted >1100 km 3 of pyroclastic material during the Last Glacial Maximum. The impacts of this event on climate and the New Zealand environment remain unresolved, particularly on ecological timescales. Using sediment cores from Onepoto maar palaeolake, Auckland (~240 km upwind from source), we have analysed pollen assemblages at contiguous 1‐mm intervals, around an intact 3‐cm layer of the Kawakawa‐Ōruanui Tephra to resolve and assess post‐eruption vegetation impacts and landscape recovery. Sediments immediately above the tephra record a decline in the relative abundance of the dominant canopy species of Fuscospora , and concurrent increase in the abundances of grasses, herbs, ferns and shrubs. These changes reflect a brief (

Salinity and temperature affect the symbiont profile and host condition of Florida USA blue crabs Callinectes sapidus - Erin A. Walters; Jamie Bojko; Claire E. Crowley; Ryan L. Gandy; Charles W. Martin; Colin P. Shea; Kelly S. Bateman; Grant D. Stentiford; Donald C. Behringer (Journal of Invertebrate Pathology, 2023)

Seismically-derived porosity of deep-sea sediments over the last 74 Ma in the equatorial Atlantic Ocean: Implications for paleo-climate - Giulia Matilde Ferrante; Satish C. Singh; Pranav Audhkhasi; Colin J. Thomson; Venkata Vaddineni; Milena Marjanović (Earth and Planetary Science Letters, 2023)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Processes and timescales of magmatic rejuvenation and residence prior to post-caldera rhyolitic eruptions: Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Simon J. Barker; Daniel J. Morgan; Colin J.N. Wilson; Bruce L.A. Charlier (Journal of Volcanology and Geothermal Research, 2023)

Perverse outcomes from fencing fauna: Loss of antipredator traits in a havened mammal population - Natasha D. Harrison; Ben L. Phillips; Nicola J. Mitchell; Julia C. Wayne; Marika A. Maxwell; Colin G. Ward; Adrian F. Wayne (Biological Conservation, 2023)

Correction: Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

A century of mercury: Ecosystem-wide changes drive increasing contamination of a tropical seabird species in the South Atlantic Ocean - Fanny Cusset; S. James Reynolds; Alice Carravieri; David Amouroux; Océane Asensio; Roger C. Dickey; Jérôme Fort; B. John Hughes; Vitor H. Paiva; Jaime A. Ramos; Laura Shearer; Emmanuel Tessier; et al. (Environmental Pollution, 2023)

Pre-eruptive rhyolite magma ascent rate is rapid and independent of eruption size: a case study from Ōkataina Volcanic Centre, Aotearoa New Zealand - Hannah C. Elms; Madison L. Myers; Alexander R. L. Nichols; Paul J. Wallace; Colin J. N. Wilson; Simon J. Barker; Bruce L. A. Charlier (Bulletin of Volcanology, 2023)
Volatile measurements in mineral-hosted sealed melt inclusions, and open-ended embayments, have previously been used to study magma ascent dynamics in large rhyolitic eruptions. However, despite occurring more frequently, smaller-volume explosive events remain under-studied. We present magmatic volatile data from quartz-hosted melt inclusions and embayments for eight post-25.4 ka rhyolitic eruptions at Ōkataina Volcanic Centre, Aotearoa New Zealand. Seven originated from within the main caldera, and the other erupted from the associated Ōkareka Structural Embayment. Melt inclusions preserve volatile contents of 2.92–5.82 wt% H 2 O and 13–126 ppm CO 2 , indicating pre-eruptive storage depths of 4.5–7.4 km, with younger eruptions being more shallow. The lack of correlation between H 2 O, CO 2 , inclusion size or distance to the crystal rim suggests magma bodies experienced variable degrees of degassing during magma storage, with some amount of post-entrapment volatile modification prior to and concurrent with final magma ascent. Diffusion modelling of measured H 2 O gradients in melt embayments indicates ascent rates of 0.10–1.67 m.s −1 over time spans of 20–230 min for the intra-caldera events. In contrast, ascent rates for the eruption from the Ōkareka Structural Embayment may be more rapid, at 1.59–4.4 m.s −1 over a time span of 22–34 min. Our findings imply that the final, pre-eruptive magma movement towards the surface could be less than a few hours. Comparisons with published data for caldera-forming explosive events reveal no clear relationships between final ascent rate, eruption size or initial volatile content, implying that other factors besides eruption volume control rhyolite magma ascent.

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Germanium speciation in experimental and natural sphalerite: Implications for critical metal enrichment in hydrothermal Zn-Pb ores - Weihua Liu; Yuan Mei; Barbara Etschmann; Matthew Glenn; Colin M. MacRae; Sam C. Spinks; Chris G. Ryan; Joël Brugger; David J. Paterson (Geochimica et Cosmochimica Acta, 2023)

Polaris Gold: An Attractive, Yellow-fleshed Tablestock Cultivar with Chipping Potential - Thomas R. Stefaniak; Jeffrey Miller; Colin R. Jones; Michael Miller; Muyideen Yusuf; Megan A. Harder; John C. Larsen; Cari A. Schmitz Carley; Darrin Haagenson; Asunta Thompson; Thomas E. Michaels; Christian Thill; et al. (American Journal of Potato Research, 2023)

Coordination of photosynthetic traits across soil and climate gradients - Andrea C. Westerband; Ian J. Wright; Vincent Maire; Jennifer Paillassa; Iain Colin Prentice; Owen K. Atkin; Keith J. Bloomfield; Lucas A. Cernusak; Ning Dong; Sean M. Gleason; Caio Guilherme Pereira; Hans Lambers; et al. (Global Change Biology, 2023)
“Least‐cost theory” posits that C 3 plants should balance rates of photosynthetic water loss and carboxylation in relation to the relative acquisition and maintenance costs of resources required for these activities. Here we investigated the dependency of photosynthetic traits on climate and soil properties using a new Australia‐wide trait dataset spanning 528 species from 67 sites. We tested the hypotheses that plants on relatively cold or dry sites, or on relatively more fertile sites, would typically operate at greater CO 2 drawdown (lower ratio of leaf internal to ambient CO 2 , C i : C a ) during light‐saturated photosynthesis, and at higher leaf N per area (N area ) and higher carboxylation capacity ( V cmax 25 ) for a given rate of stomatal conductance to water vapour, g sw . These results would be indicative of plants having relatively higher water costs than nutrient costs. In general, our hypotheses were supported. Soil total phosphorus (P) concentration and (more weakly) soil pH exerted positive effects on the N area – g sw and V cmax 25 – g sw slopes, and negative effects on C i : C a . The P effect strengthened when the effect of climate was removed via partial regression. We observed similar trends with increasing soil cation exchange capacity and clay content, which affect soil nutrient availability, and found that soil properties explained similar amounts of variation in the focal traits as climate did. Although climate typically explained more trait variation than soil did, together they explained up to 52% of variation in the slope relationships and soil properties explained up to 30% of the variation in individual traits. Soils influenced photosynthetic traits as well as their coordination. In particular, the influence of soil P likely reflects the Australia's geologically ancient low‐relief landscapes with highly leached soils. Least‐cost theory provides a valuable framework for understanding trade‐offs between resource costs and use in plants, including limiting soil nutrients.

Migratory birds with delayed spring departure migrate faster but pay the costs - Bryant C. Dossman; Amanda D. Rodewald; Colin E. Studds; Peter P. Marra (Ecology, 2023)
Migratory birds that experience poor overwintering conditions are often late to arrive at the breeding grounds, which is known to depress individual fitness. Despite the importance of this carryover effect, few studies have investigated how individuals can modify migratory behaviors en route to reduce delays on arrival and whether accelerating migration incurs survival costs. To examine this, we used Motus Wildlife Tracking System to track individual American redstarts ( Setophaga ruticilla ) as they migrated from wintering grounds in Southwest Jamaica through Florida en route to their breeding areas. We leveraged long‐term data on spring departure timing and breeding latitude to quantify the relative departure dates (early vs. delayed) of tagged individuals, which we then related to individual migration rates and apparent annual survival. Compared to those initiating migration earlier, individuals that departed relatively late (10‐day delay) migrated at a 43% faster rate, which decreased their annual survival by 6.3%. Our results are consistent with the hypothesis that spring migrants use speed to compensate for departure delays despite incurring survival costs. This compensatory behavior may potentially underly differential survival during spring migration and may be particularly widespread across short‐lived migratory birds generally considered time‐constrained.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Conceptual frameworks and key questions for assessing the contribution of marine protected areas to shark and ray conservation - Andrew Chin; Fergus John Molloy; Darren Cameron; Jon C. Day; Jessica Cramp; Karin Leeann Gerhardt; Michelle R. Heupel; Mark Read; Colin A. Simpfendorfer (Conservation Biology, 2023)
Marine protected areas (MPAs) are key tools in addressing the global decline of sharks and rays, and marine parks and shark sanctuaries of various configurations have been established to conserve shark populations. However, assessments of their efficacy are compromised by inconsistent terminology, lack of standardized approaches to assess how MPAs contribute to shark and ray conservation, and ambiguity about how to integrate movement data in assessment processes. We devised a conceptual framework to standardize key terms (e.g., protection , contribution , potential impact , risk , threat ) and used the concept of portfolio risk to identify key attributes of sharks and rays (assets), the threats they face (portfolio risk), and the specific role of MPAs in risk mitigation (insurance). Movement data can be integrated into the process by informing risk exposure and mitigation through MPAs. The framework is operationalized by posing 8 key questions that prompt practitioners to consider the assessment scope, MPA type and purpose, range of existing and potential threats, species biology and ecology, and management and operational contexts. Ultimately, MPA contributions to shark and ray conservation differ according to a complex set of human and natural factors and interactions that should be carefully considered in MPA design, implementation, and evaluation.

Quantifying and mapping species threat abatement opportunities to support national target setting - Louise Mair; Eduardo Amorim; Monira Bicalho; Thomas M. Brooks; Vincente Calfo; Renata de T. Capellão; Colin Clubbe; Marianne Evju; Eduardo P. Fernandez; Gláucia C. Ferreira; Frank Hawkins; Randall R. Jiménez; et al. (Conservation Biology, 2023)
The successful implementation of the Convention on Biological Diversity's post‐2020 Global Biodiversity Framework will rely on effective translation of targets from global to national level and increased engagement across diverse sectors of society. Species conservation targets require policy support measures that can be applied to a diversity of taxonomic groups, that link action targets to outcome goals, and that can be applied to both global and national data sets to account for national context, which the species threat abatement and restoration (STAR) metric does. To test the flexibility of STAR, we applied the metric to vascular plants listed on national red lists of Brazil, Norway, and South Africa. The STAR metric uses data on species’ extinction risk, distributions, and threats, which we obtained from national red lists to quantify the contribution that threat abatement and habitat restoration activities could make to reducing species’ extinction risk. Across all 3 countries, the greatest opportunity for reducing plant species’ extinction risk was from abating threats from agricultural activities, which could reduce species’ extinction risk by 54% in Norway, 36% in South Africa, and 29% in Brazil. Species extinction risk could be reduced by a further 21% in South Africa by abating threats from invasive species and by 21% in Brazil by abating threats from urban expansion. Even with different approaches to red‐listing among countries, the STAR metric yielded informative results that identified where the greatest conservation gains could be made for species through threat‐abatement and restoration activities. Quantifiably linking local taxonomic coverage and data collection to global processes with STAR would allow national target setting to align with global targets and enable state and nonstate actors to measure and report on their potential contributions to species conservation.

Coastal freshening drives acidification state in Greenland fjords - Henry C. Henson; Johnna M. Holding; Lorenz Meire; Søren Rysgaard; Colin A. Stedmon; Alice Stuart-Lee; Jørgen Bendtsen; Mikael Sejr (Science of The Total Environment, 2023)

Analytical performances of the LAb-CosmOrbitrap mass spectrometer for astrobiology - L. Selliez; C. Briois; N. Carrasco; L. Thirkell; B. Gaubicher; J.-P. Lebreton; F. Colin (Planetary and Space Science, 2023)

A new approach for the encapsulation of Saccharomyces cerevisiae using shellac and cellulose nanocrystals - Jiyoo Baek; Mohankandhasamy Ramasamy; David Gunhee Cho; Colin Chee Chung Soo; Sparsh Kapar; Joshua Youngchan Lee; Kam C. Tam (Food Hydrocolloids, 2023)

Multi-year evaluation of muskellunge (Esox masquinongy) spatial ecology during winter drawdowns in a regulated, urban waterway in Canada - Jordanna N. Bergman; Kate L. Neigel; Sean J. Landsman; Danny Glassman; Luc LaRochelle; Joseph R. Bennett; Colin D. Rennie; Jesse C. Vermaire; Steven J. Cooke (Hydrobiologia, 2023)

G﻿lobal phylogeography of ridley sea turtles (Lepidochelys spp.): evolution, demography, connectivity, and conservation - Sibelle Torres Vilaça; Anelise Torres Hahn; Eugenia Naro-Maciel; F. Alberto Abreu-Grobois; Brian W. Bowen; Jaqueline C. Castilhos; Claudio Ciofi; Nancy N. FitzSimmons; Michael P. Jensen; Angela Formia; Colin J. Limpus; Chiara Natali; et al. (Conservation Genetics, 2022)
Globally distributed marine taxa are well suited for investigations of biogeographic impacts on genetic diversity, connectivity, and population demography. The sea turtle genus Lepidochelys includes the wide-ranging and abundant olive ridley ( L. olivacea ), and the geographically restricted and ‘Critically Endangered’ Kemp’s ridley ( L. kempii ). To investigate their historical biogeography, we analyzed a large dataset of mitochondrial DNA (mtDNA) sequences from olive (n = 943) and Kemp’s (n = 287) ridleys, and genotyped 15 nuclear microsatellite loci in a global sample of olive ridleys (n = 285). We found that the ridley species split ~ 7.5 million years ago, before the Panama Isthmus closure. The most ancient mitochondrial olive ridley lineage, located in the Indian Ocean, was dated to ~ 2.2 Mya. Both mitochondrial and nuclear markers revealed significant structure for olive ridleys between Atlantic (ATL), East Pacific (EP), and Indo-West Pacific (IWP) areas. However, the divergence of mtDNA clades was very recent (< 1 Mya) with low within- clade diversity, supporting a recurrent extinction-recolonization model for these ocean regions. All data showed that ATL and IWP groups were more closely related than those in the EP, with mtDNA data supporting recent recolonization of the ATL from the IWP. Individual olive ridley dispersal between the ATL, EP, and IN/IWP could be interpreted as more male- than female-biased, and genetic diversity was lowest in the Atlantic Ocean. All populations showed signs of recent expansion, and estimated time frames were concordant with their recent colonization history. Investigating species abundance and distribution changes over time is central to evolutionary biology, and this study provides a historical biogeographic context for marine vertebrate conservation and management.

PIM3 kinase promotes tumor metastasis in hepatoblastoma by upregulating cell surface expression of chemokine receptor cxcr4 - Raoud Marayati; Janet Julson; Laura V. Bownes; Colin H. Quinn; Laura L. Stafman; Andee M. Beierle; Hooper R. Markert; Sara C. Hutchins; Jerry E. Stewart; David K. Crossman; Anita B. Hjelmeland; Elizabeth Mroczek-Musulman; et al. (Clinical & Experimental Metastasis, 2022)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Inferring spatially varying animal movement characteristics using a hierarchical continuous‐time velocity model - Ionut Paun; Dirk Husmeier; J. Grant C. Hopcraft; Majaliwa M. Masolele; Colin J. Torney (Ecology Letters, 2022)
Understanding the spatial dynamics of animal movement is an essential component of maintaining ecological connectivity, conserving key habitats, and mitigating the impacts of anthropogenic disturbance. Altered movement and migratory patterns are often an early warning sign of the effects of environmental disturbance, and a precursor to population declines. Here, we present a hierarchical Bayesian framework based on Gaussian processes for analysing the spatial characteristics of animal movement. At the heart of our approach is a novel covariance kernel that links the spatially varying parameters of a continuous‐time velocity model with GPS locations from multiple individuals. We demonstrate the effectiveness of our framework by first applying it to a synthetic data set and then by analysing telemetry data from the Serengeti wildebeest migration. Through application of our approach, we are able to identify the key pathways of the wildebeest migration as well as revealing the impacts of environmental features on movement behaviour.

M‐Risk : A framework for assessing global fisheries management efficacy of sharks, rays and chimaeras - C. Samantha Sherman; Glenn Sant; Colin A. Simpfendorfer; Eric D. Digel; Patrick Zubick; Grant Johnson; Michael Usher; Nicholas K. Dulvy (Fish and Fisheries, 2022)
Fisheries management is essential to guarantee sustainable capture of target species and avoid undesirable declines of incidentally captured species. A key challenge is halting and reversing declines of shark and ray species, and specifically assessing the degree to which management is sufficient to avoid declines in relatively data‐poor fisheries. While ecological risk analyses focus on intrinsic ‘productivity’ and extrinsic ‘susceptibility’, one would ideally consider the influence of ‘fisheries management’. Currently, there is no single management evaluation that can be applied to a combination of fishery types at the scale of individual country or Regional Fisheries Management Organizations (RFMOs). Here, we outline a management‐risk (M‐Risk) framework for sharks, rays and chimaeras used to evaluate species' risk of overfishing resulting from ineffective management. We illustrate our approach with application to one country (Ecuador) and RFMO (Inter‐American Tropical Tuna Commission) and illustrate the variation in scores among species. We found that while both management units assessed had similar overall scores, the scores for individual attributes varied. Ecuador scored higher in reporting‐related attributes, while the IATTC scored higher in attributes related to data collection and use. We evaluated whether the management of individual species was sufficient for their relative sensitivity by combining the management‐risk score for each species with their intrinsic sensitivity to determine a final M‐Risk score. This framework can be applied to determine which species face the greatest risk of overfishing and be used by fisheries managers to identify effective management policies by replicating regulations from countries with lower risk scores.

A sulfur and halogen budget for the large magmatic system beneath Taupō volcano - Max S. Sharpe; Simon J. Barker; Shane M. Rooyakkers; Colin J. N. Wilson; Isabelle Chambefort; Michael C. Rowe; C. Ian Schipper; Bruce L. A. Charlier (Contributions to Mineralogy and Petrology, 2022)
The transport and degassing pathways of volatiles through large silicic magmatic systems are central to understanding geothermal fluid compositions, ore deposit genesis, and volcanic eruption dynamics and impacts. Here, we document sulfur (S), chlorine (Cl), and fluorine (F) concentrations in a range of host materials in eruptive deposits from Taupō volcano (New Zealand). Materials analysed are groundmass glass, silicic melt inclusions, and microphenocrystic apatite that equilibrated in shallow melt-dominant magma bodies; silicic melt and apatite inclusions within crystal cores inferred to be sourced from deeper crystal mush; and olivine-hosted basaltic melt inclusions from mafic enclaves that represent the most primitive feedstock magmas. Sulfur and halogen concentrations each follow distinct concentration pathways during magma differentiation in response to changing pressures, temperatures, oxygen fugacities, crystallising mineral phases, the effects of volatile saturation, and the presence of an aqueous fluid phase. Sulfur contents in the basaltic melt inclusions (~ 2000 ppm) are typical for arc-type magmas, but drop to near detection limits by dacitic compositions, reflecting pyrrhotite crystallisation at ~ 60 wt. % SiO 2 during the onset of magnetite crystallisation. In contrast, Cl increases from ~ 500 ppm in basalts to ~ 2500 ppm in dacitic compositions, due to incompatibility in the crystallising phases. Fluorine contents are similar between mafic and silicic compositions (< 1200 ppm) and are primarily controlled by the onset of apatite and/or amphibole crystallisation and then destabilisation. Sulfur and Cl partition strongly into an aqueous fluid and/or vapour phase in the shallow silicic system. Sulfur contents in the rhyolite melts are low, yet the Oruanui supereruption is associated with a major sulfate peak in ice core records in Antarctica and Greenland, implying that excess S was derived from a pre-eruptive gas phase, mafic magma recharge, and/or disintegration of a hydrothermal system. We estimate that the 25.5 ka Oruanui eruption ejected > 130 Tg of S (390 Tg sulfate) and up to ~ 1800 Tg of Cl, with potentially global impacts on climate and stratospheric ozone.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

The effect of group size on individual behavior of bubble‐net feeding humpback whales in the southern Gulf of Maine - Natalie C. Mastick; David Wiley; David E. Cade; Colin Ware; Susan E. Parks; Ari S. Friedlaender (Marine Mammal Science, 2022)
In many species, group foraging is a strategy used to increase the efficiency of individuals to find and exploit patchy prey. Humpback whales ( Megaptera novaeangliae ) are one of the few baleen whale species reported to use coordinated foraging strategies. One of these behaviors, bubble‐net feeding, has been observed in several populations, though the behaviors of individuals within these groups are largely unknown. This study used multisensor kinematic tag data from 26 whales foraging in the Southern Gulf of Maine to analyze individual bubble‐net feeding behaviors. Linear mixed effects models were used to test if there were differences in individual whales' dive behaviors across group size. The results indicate that individuals performed consistent bubble‐net feeding behaviors regardless of the size of their foraging group, except when using one specific foraging behavior, the upward spiral. Overall complexity of foraging dives, based on the three‐dimensional movements of the dive, decreased with increasing group size when group members used upward spirals. This may indicate that in larger groups, participants in coordinated feeding events need to move less and expend less energy to corral prey. This study provides new insights into the effects of group size on individual behavior and group coordination in humpback whales.

Scientists Against War: A Plea to World Leaders for Better Governance - Seithikurippu R. Pandi-Perumal; Velayudhan Mohan Kumar; Namasivayam Ganesh Pandian; Joop T. de Jong; Sudalaikannu Andiappan; Alexandru Corlateanu; Arehally Marappa Mahalaksmi; Saravana Babu Chidambaram; Ramasamy Rajesh Kumar; Chellamuthu Ramasubramanian; Sudhakar Sivasubramaniam; Alvhild Alette Bjørkum; et al. (Sleep and Vigilance, 2022)

Sediment dynamics at different timescales on an embayed coast in southeastern Australia - Colin D. Woodroffe; R. C. Carvalho; T. S. N. Oliver; B. G. Thom (Journal of Coastal Conservation, 2022)
The concept of coastal sediment compartments has recently been adopted at a national scale in Australia to better understand sediment and shoreline dynamics and to underpin management of future shoreline behaviour in response to impacts of climate change. Geomorphological studies in southern NSW have provided a foundation for development of conceptual models of estuary and sandy barrier evolution. Geochronological reconstructions using radiocarbon, optically-stimulated luminescence, and other dating techniques, reviewed in this paper, demonstrate that adjacent compartments are at successive stages. Three compartments, Illawarra, Shoalhaven and Moruya, are compared, each with different catchment characteristics and different levels of human intervention. Landform change and sediment accumulation at millennial timescales enable estimates of past sediment accretion (vertical accumulation) and horizontal displacement of shorelines (particularly progradation), as a first step towards quantifying volumetric changes of morphology. Lake Illawarra is a barrier estuary at an early stage of infill, but land-use change, urbanisation, and engineering structures at the entrance have accelerated rates of sediment accumulation. The Shoalhaven River has infilled its estuary and delivers sand to the coast. It has been subject to several conspicuous anthropogenic interventions. At Moruya, ongoing supply of sand, primarily from offshore rather than from the catchment, has resulted in beach-ridge plains (strandplains) with changes in their alongshore inter-connectivity driven by differential embayment infilling. Millennial-scale geomorphology indicates landform change providing a means to determine natural trajectories of sediment transfer. However, variability is apparent at century and decadal timescales, compounded by various anthropogenic interventions. Disentangling natural and anthropogenic influences will be necessary to provide greater confidence in estimating past and present sediment budgets. Assessing sand sources and transport rates is important in relation to engineering interventions at entrances, and long-term resilience of coastal habitats. Such issues are the focus of coastal management programs, and this synthesis emphasises the relevance of a sediment budget approach to understand contemporary sediment pathways and provide an indication of future response to engineering interventions and sensitivity to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Assessing the risk of human‐to‐wildlife pathogen transmission for conservation and public health - Anna C. Fagre; Lily E. Cohen; Evan A. Eskew; Max Farrell; Emma Glennon; Maxwell B. Joseph; Hannah K. Frank; Sadie J. Ryan; Colin J Carlson; Gregory F. Albery (Ecology Letters, 2022)
The SARS‐CoV‐2 pandemic has led to increased concern over transmission of pathogens from humans to animals, and its potential to threaten conservation and public health. To assess this threat, we reviewed published evidence of human‐to‐wildlife transmission events, with a focus on how such events could threaten animal and human health. We identified 97 verified examples, involving a wide range of pathogens; however, reported hosts were mostly non‐human primates or large, long‐lived captive animals. Relatively few documented examples resulted in morbidity and mortality, and very few led to maintenance of a human pathogen in a new reservoir or subsequent “secondary spillover” back into humans. We discuss limitations in the literature surrounding these phenomena, including strong evidence of sampling bias towards non‐human primates and human‐proximate mammals and the possibility of systematic bias against reporting human parasites in wildlife, both of which limit our ability to assess the risk of human‐to‐wildlife pathogen transmission. We outline how researchers can collect experimental and observational evidence that will expand our capacity for risk assessment for human‐to‐wildlife pathogen transmission.

Multiple resource limitation of dryland soil microbial carbon cycling on the Colorado Plateau - Ryan T. Choi; Sasha C. Reed; Colin L. Tucker (Ecology, 2022)
Understanding interactions among biogeochemical cycles is increasingly important as anthropogenic alterations of global climate and of carbon (C), nitrogen (N), and phosphorus (P) cycles interactively affect the Earth system. Ecosystem processes in the dryland biome, which makes up over 40% of Earth's terrestrial surface, are often distinctively sensitive to small changes in resource availability, likely because levels of many resources are low. However, data also suggest that simultaneous changes in the availability of multiple resources may be necessary to affect a response in these low‐resource systems, offering an opportunity to test patterns and controls of co‐limitation, serial limitation, and individual limitation in soil environments. While drylands may play a governing role in key aspects of Earth's C cycle, and while an improved understanding of resource limitation could substantially improve our forecasts of dryland responses to change, our understanding of interacting controls on soil C cycle processes remains notably poor in these dry systems. Here, we address multiple fundamental hypotheses of resource controls over ecosystem function to test how water, C, N, and P regulate soil C cycling individually and interactively in a dryland ecosystem on the Colorado Plateau. Using a series of laboratory incubations, we found that, while water, C, and N limited C cycling through serial limitation, water alone resulted in an extremely small respiratory response from target organisms, whereas water + C resulted in a dramatic increase in soil C cycling, suggesting a degree of functional co‐limitation. Nitrogen additions alone resulted in no changes to soil C cycling, but when N was added in concert with water and C, N greatly increased soil C cycling rates relative to additions of water and C without N. Phosphorus additions had no effect on the C cycle either alone or synergistically. These patterns were consistent with the stoichiometry of the system and interactions among resources were surprising in ways that inform our understanding of critical theories in ecology, such as the Transient Maxima Hypothesis, supporting the suggestion that multiple resource limitation explains pulse‐dynamic C cycling in drylands better than water limitation alone.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

MASTREE+: Time‐series of plant reproductive effort from six continents - Andrew Hacket‐Pain; Jessie J. Foest; Ian S. Pearse; Jalene M. LaMontagne; Walter D. Koenig; Giorgio Vacchiano; Michał Bogdziewicz; Thomas Caignard; Paulina Celebias; Joep van Dormolen; Marcos Fernández‐Martínez; Jose V. Moris; et al. (Global Change Biology, 2022)
Significant gaps remain in understanding the response of plant reproduction to environmental change. This is partly because measuring reproduction in long‐lived plants requires direct observation over many years and such datasets have rarely been made publicly available. Here we introduce MASTREE+, a data set that collates reproductive time‐series data from across the globe and makes these data freely available to the community. MASTREE+ includes 73,828 georeferenced observations of annual reproduction (e.g. seed and fruit counts) in perennial plant populations worldwide. These observations consist of 5971 population‐level time‐series from 974 species in 66 countries. The mean and median time‐series length is 12.4 and 10 years respectively, and the data set includes 1122 series that extend over at least two decades (≥20 years of observations). For a subset of well‐studied species, MASTREE+ includes extensive replication of time‐series across geographical and climatic gradients. Here we describe the open‐access data set, available as a.csv file, and we introduce an associated web‐based app for data exploration. MASTREE+ will provide the basis for improved understanding of the response of long‐lived plant reproduction to environmental change. Additionally, MASTREE+ will enable investigation of the ecology and evolution of reproductive strategies in perennial plants, and the role of plant reproduction as a driver of ecosystem dynamics.

The emergence of marine recreational drone fishing: Regional trends and emerging concerns - Alexander C. Winkler; Edward C. Butler; Colin G. Attwood; Bruce Q. Mann; Warren M. Potts (Ambio, 2022)

Oviposition behaviour and emergence through time of the small blue butterfly (Cupido minimus) in a nature reserve in Bedfordshire, UK - Esme Ashe-Jepson; Andrew J. Bladon; Greg Herbert; Gwen E. Hitchcock; Richard Knock; Colin B. H. Lucas; Sarah H. Luke; Edgar C. Turner (Journal of Insect Conservation, 2022)
Abstract Climate change affects butterflies in many ways, influencing the timing of emergence and reproduction, habitat preferences, and behaviour. The small blue ( Cupido minimus Fuessley, 1775) is highly specialised in its host plant requirements, feeding on the seeds of a single species, kidney vetch ( Anthyllis vulneraria ), on which the larvae occur singly to avoid cannibalism. The butterfly is likely to be vulnerable to temperature-related changes in oviposition, adult emergence, and host plant flowering times, and is, therefore, a good model species for investigating climate change-related impacts. Using 26 years of data from the national UK Butterfly Monitoring Scheme (1993–2019) from one nature reserve, and 4 years of targeted egg searches (2006, 2007, 2008, 2020) from three reserves in Bedfordshire, UK, we investigated the effects of local temperature on small blue emergence date and total abundance, whether flowerhead or local environmental characteristics predicted small blue oviposition behaviour, and whether this changed between years. Small blue adults emerged on earlier dates over time, and earlier in years with higher maximum February temperatures. Total adult abundance was not predicted by monthly temperatures or total abundance in the previous year. Oviposition behaviour was broadly consistent across years, with egg presence more likely and egg abundance higher on kidney vetch flowerheads that were taller than the surrounding vegetation, and surrounded by taller vegetation and fewer mature flowerheads. The effect of solar radiation differed between years, with a negative effect on the probability of egg presence in 2007 and 2008, but a positive effect in 2020. Egg abundance per flowerhead was highly variable between years, with 2006 having four times more eggs per flowerhead than other years. This was likely driven by high adult abundance in 2006, which could have increased competition for flowerheads. Implications for insect conservation Our results indicate that management for greater availability of taller kidney vetch amongst taller vegetation would encourage small blue oviposition on a greater number of flowerheads, providing a possible means of reducing competition and increasing larval survival, and that this would be effective despite variation in adult abundance between years. The high level of competition we observed in the year with the highest adult abundance indicates that higher numbers of host plants should be encouraged to reduce competition and larval cannibalism in peak years, increasing the likelihood of long-term population persistence and growth.

Extreme bill dimorphism leads to different but overlapping isotopic niches and similar trophic positions in sexes of the charismatic extinct huia - Barbara M. Tomotani; Rodrigo B. Salvador; Amandine J. M. Sabadel; Colin M. Miskelly; Julie C. S. Brown; Josette Delgado; Patrick Boussès; Yves Cherel; Susan M. Waugh; Sarah J. Bury (Oecologia, 2022)
The New Zealand huia ( Heteralocha acutirostris ) had the most extreme bill sexual dimorphism among modern birds. Given the quick extinction of the species, the cause of the dimorphism could only be hypothesised to reflect different trophic niches and reduce male/female competition. We tested that hypothesis by combining museum specimens, geometric morphometrics, and isotopic analyses. We used geometric morphometrics to describe bill shape; measured bulk ( δ 15 N bulk ) and ( δ 13 C bulk ) values from feather as proxies of the birds’ foraging habitat and diet; and compared compound-specific stable isotopes analyses (CSIA) of nitrogen in amino acids ( δ 15 N AA ) in male–female pairs to estimate their trophic position. Sexes had significantly different, but overlapping feather δ 15 N bulk and δ 13 C bulk values, but δ 15 N AA indicated identical trophic positions and δ 15 N bulk was not related to bill shape. Trophic position was less variable among females, consistent with a specialised foraging behaviour and, thus, supporting a partial male/female foraging segregation.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Year-Round Movements of Sooty Terns (Onychoprion fuscatus) Nesting Within One of the Atlantic’s Largest Marine Protected Areas - S. James Reynolds; Colin P. Wearn; B. John Hughes; Roger C. Dickey; Lucy J. H. Garrett; Sean Walls; Fay T. Hughes; Nicola Weber; Sam B. Weber; Eliza H. K. Leat; Kenickie Andrews; Jaime A. Ramos; et al. (Frontiers in Marine Science, 2021)
Seabirds are among the most threatened birds as a result of acute exposure to many anthropogenic threats. Their effective conservation requires a detailed understanding of how seabirds use marine habitats. Recently, one of the largest no-take marine reserves in the Atlantic was designated in tropical waters surrounding Ascension Island, on which the largest Atlantic population of sooty terns ( Onychoprion fuscatus ) breeds. Although they are the most abundant tropical seabird, they appear to have suffered marked population declines on Ascension Island as they have elsewhere. Here, we describe year-round movements and habitat use of male and female sooty terns between 2011 and 2015. On average, birds traveled 47,000 km during their 8 months of migration, during which they remained within 2,900 km of the island. They spent most of the day and night in flight, only touching down briefly on the ocean most likely to feed. Habitat suitability models successfully predicted foraging ranges of birds and their at-sea distributions varied considerably between seasons, years and sexes. Considerable variation in range overlap between birds and the new marine protected area (MPA) suggests that similar such studies of other marine taxa are urgently needed. The range of sooty terns mainly falls in the high seas outside of the new MPA, highlighting the very large areas that many oceanic seabirds forage across and the challenges their conservation present.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Comparison of the distribution and phenology of Arctic Mountain plants between the early 20th and 21st centuries - Andrew S. MacDougall; Paul Caplat; Johan Olofsson; Matthias B. Siewert; Colin Bonner; Ellen Esch; Malie Lessard‐Therrien; Hannah Rosenzweig; Anne‐Kathrin Schäfer; Pia Raker; Hassan Ridha; Kjell Bolmgren; et al. (Global Change Biology, 2021)
Arctic plants are adapted to climatic variability, but their long‐term responses to warming remain unclear. Responses may occur by range shifts, phenological adjustments in growth and reproduction, or both. Here, we compare distribution and phenology of 83 arctic and boreal mountain species, sampled identically in the early 20th (1917–1919) and 21st centuries (2017–2018) from a region of northern Sweden that has warmed significantly. We test two compensatory hypotheses to high‐latitude warming—upward shifts in distribution, and earlier or extended growth and reproduction. For distribution, we show dramatic upward migration by 69% of species, averaging 6.1 m per decade, especially boreal woodland taxa whose upward expansion has reduced arctic montane habitat by 30%. Twenty percent of summit species showed distributional shifts but downward, especially moisture‐associated snowbed flora. For phenology, we detected wide inter‐annual variability in the onset of leafing and flowering in both eras. However, there was no detectable change in growing‐season length, relating to two mechanisms. First, plot‐level snow melt data starting in 1917 demonstrated that melt date, rather than vernal temperatures, better predicts plant emergence, with snow melt influenced by warmer years having greater snowfall—warmer springs did not always result in earlier emergence because snowbeds can persist longer. Second, the onset of reproductive senescence between eras was similar, even when plant emergence was earlier by a month, possibly due to intensified summer heat stress or hard‐wired ‘canalization’ where senescence occurs regardless of summer temperature. Migrations in this system have possibly buffered arctic species against displacement by boreal expansion and warming, but ongoing temperature increases, woody plant invasion, and a potential lack of flexibility in timing of senescence may foreshadow challenges.

Antifouling properties of amphiphilic poly(3-hydroxyalkanoate): an environmentally-friendly coating - A. Guennec; L. Brelle; E. Balnois; I. Linossier; E. Renard; V. Langlois; F. Faÿ; G. Q. Chen; C. Simon-Colin; K. Vallée-Réhel (Biofouling, 2021)

Continental‐scale acoustic telemetry and network analysis reveal new insights into stock structure - Elodie J. I. Lédée; Michelle R. Heupel; Matthew D. Taylor; Robert G. Harcourt; Fabrice R. A. Jaine; Charlie Huveneers; Vinay Udyawer; Hamish A. Campbell; Russell C. Babcock; Xavier Hoenner; Adam Barnett; Matias Braccini; et al. (Fish and Fisheries, 2021)
Delineation of population structure (i.e. stocks) is crucial to successfully manage exploited species and to address conservation concerns for threatened species. Fish migration and associated movements are key mechanisms through which discrete populations mix and are thus important determinants of population structure. Detailed information on fish migration and movements is becoming more accessible through advances in telemetry and analysis methods however such information is not yet used systematically in stock structure assessment. Here, we described how detections of acoustically tagged fish across a continental‐scale array of underwater acoustic receivers were used to assess stock structure and connectivity in seven teleost and seven shark species and compared to findings from genetic and conventional tagging. Network analysis revealed previously unknown population connections in some species, and in others bolstered support for existing stock discrimination by identifying nodes and routes important for connectivity. Species with less variability in their movements required smaller sample sizes (45–50 individuals) to reveal useful stock structure information. Our study shows the power of continental‐scale acoustic telemetry networks to detect movements among fishery jurisdictions. We highlight methodological issues that need to be considered in the design of acoustic telemetry studies for investigating stock structure and the interpretation of the resulting data. The advent of broad‐scale acoustic telemetry networks across the globe provides new avenues to understand how movement informs population structure and can lead to improved management.

A new approach for estimating and delineating within-field crop water stress zones with satellite imagery - Ryan Smith; Lindi Oyler; Colin Campbell; Elisa A. Woolley; Bryan G. Hopkins; Ruth Kerry; Neil C. Hansen (International Journal of Remote Sensing, 2021)

Plastic Pollution and Small Juvenile Marine Turtles: A Potential Evolutionary Trap - Emily M. Duncan; Annette C. Broderick; Kay Critchell; Tamara S. Galloway; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; David Santillo; Anton D. Tucker; Scott Whiting; Erina J. Young; Brendan J. Godley (Frontiers in Marine Science, 2021)
The ingestion of plastic by marine turtles is now reported for all species. Small juvenile turtles (including post-hatchling and oceanic juveniles) are thought to be most at risk, due to feeding preferences and overlap with areas of high plastic abundance. Their remote and dispersed life stage, however, results in limited access and assessments. Here, stranded and bycaught specimens from Queensland Australia, Pacific Ocean (PO; n = 65; 1993–2019) and Western Australia, Indian Ocean (IO; n = 56; 2015–2019) provide a unique opportunity to assess the extent of plastic (> 1mm) ingestion in five species [green ( Chelonia mydas ), loggerhead ( Caretta caretta ), hawksbill ( Eretmochelys imbricata ), olive ridley ( Lepidochelys olivacea ), and flatback turtles ( Natator depressus )]. In the Pacific Ocean, high incidence of ingestion occurred in green (83%; n = 36), loggerhead (86%; n = 7), flatback (80%; n = 10) and olive ridley turtles (29%; n = 7). There was an overall lower incidence in IO; highest being in the flatback (28%; n = 18), the loggerhead (21%; n = 14) and green (9%; n = 22). No macroplastic debris ingestion was documented for hawksbill turtles in either site although sample sizes were smaller for this species (PO n = 5; IO n = 2). In the Pacific Ocean, the majority of ingested debris was made up of hard fragments (mean of all species 52%; species averages 46–97%), whereas for the Indian Ocean these were filamentous plastics (52%; 43–77%). The most abundant colour for both sites across all species was clear (PO: 36%; IO: 39%), followed by white for PO (36%) then green and blue for IO (16%; 16%). The polymers most commonly ingested by turtles in both oceans were polyethylene (PE; PO-58%; IO-39%) and polypropylene (PP; PO-20.2%; IO-23.5%). We frame the high occurrence of ingested plastic present in this marine turtle life stage as a potential evolutionary trap as they undertake their development in what are now some of the most polluted areas of the global oceans.

Categorizing the characteristics of human carcinogens: a need for specificity - Carr J. Smith; Thomas A. Perfetti; A. Wallace Hayes; Sir Colin Berry; James E. Trosko; Judy A. King; Jay I. Goodman; C. Glenn Begley; Anthony Dayan (Archives of Toxicology, 2021)

Low‐intensity frequent fires in coniferous forests transform soil organic matter in ways that may offset ecosystem carbon losses - Adam F. A. Pellegrini; Anthony C. Caprio; Katerina Georgiou; Colin Finnegan; Sarah E. Hobbie; Jeffery A. Hatten; Robert B. Jackson (Global Change Biology, 2021)
The impact of shifting disturbance regimes on soil carbon (C) storage is a key uncertainty in global change research. Wildfires in coniferous forests are becoming more frequent in many regions, potentially causing large C emissions. Repeated low‐intensity prescribed fires can mitigate wildfire severity, but repeated combustion may decrease soil C unless compensatory responses stabilize soil organic matter. Here, we tested how 30 years of decadal prescribed burning affected C and nitrogen (N) in plants, detritus, and soils in coniferous forests in the Sierra Nevada mountains, USA. Tree basal area and litter stocks were resilient to fire, but fire reduced forest floor C by 77% (−36.4 Mg C/ha). In mineral soils, fire reduced C that was free from minerals by 41% (−4.4 Mg C/ha) but not C associated with minerals, and only in depths ≤ 5 cm. Fire also transformed the properties of remaining mineral soil organic matter by increasing the proportion of C in a pyrogenic form (from 3.2% to 7.5%) and associated with minerals (from 46% to 58%), suggesting the remaining soil C is more resistant to decomposition. Laboratory assays illustrated that fire reduced microbial CO 2 respiration rates by 55% and the activity of eight extracellular enzymes that degrade cellulosic and aromatic compounds by 40–66%. Lower decomposition was correlated with lower inorganic N (−49%), especially ammonium, suggesting N availability is coupled with decomposition. The relative increase in forms of soil organic matter that are resistant to decay or stabilized onto mineral surfaces, and the associated decline in decomposition suggest that low‐intensity fires may promote mineral soil C storage in pools with long mean residence times in coniferous forests.

Molecular Mechanisms of Coral Persistence Within Highly Urbanized Locations in the Port of Miami, Florida - Ewelina T. Rubin; Ian C. Enochs; Colin Foord; Anderson B. Mayfield; Graham Kolodziej; Isabelle Basden; Derek P. Manzello (Frontiers in Marine Science, 2021)
Healthy coral communities can be found on artificial structures (concrete walls and riprap) within the Port of Miami (PoM), Florida. These communities feature an unusually high abundance of brain corals, which have almost entirely vanished from nearby offshore reefs. These corals appear to be thriving in very low-quality waters influenced by dense ship and boat traffic, dredging, and numerous residential and industrial developments. The PoM basin is part of Biscayne Bay, an estuarine environment that experiences frequent freshwater input, high nutrient loading, hypoxia, and acidification. To investigate if there is a molecular basis behind the ability of these corals to persist within these highly “urbanized” waters, we compared whole transcriptome expression profiles from 25 PoM Pseudodiploria strigosa colonies against six conspecifics from a nearby offshore reef. We found that the urban corals exhibited higher expression of (1) transcripts encoding pattern-recognition receptors which may allow these corals to better sense and detect food particles and pathogenic invaders; (2) digestive and degradation-associated enzymes, which may suggest an elevated capacity for heterotrophy and pathogen digestion; and (3) transcripts related to innate immunity, defense, and cellular detoxification, which may collectively protect against pathogenic organisms and water pollution impacts. Large ribosomal subunit rRNA gene mapping revealed that P. strigosa colonies from the PoM sites predominantly hosted heat-tolerant endosymbionts from the genus Durusdinium while offshore conspecifics’ communities were dominated by symbionts in the genus Breviolum . These findings reveal transcriptomic plasticity and molecular mechanisms contributing to the persistence of these corals within a highly urbanized habitat.

Exploring controls of the early and stepped deglaciation on the western margin of the British Irish Ice Sheet - Sara Benetti; Richard C. Chiverrell; Colm Ó Cofaigh; Matt Burke; Alicia Medialdea; David Small; Colin Ballantyne; Mark D. Bateman; S. Louise Callard; Peter Wilson; Derek Fabel; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
New optically stimulated luminescence dating and Bayesian models integrating all legacy and BRITICE‐CHRONO geochronology facilitated exploration of the controls on the deglaciation of two former sectors of the British–Irish Ice Sheet, the Donegal Bay (DBIS) and Malin Sea ice‐streams (MSIS). Shelf‐edge glaciation occurred ~27 ka, before the global Last Glacial Maximum, and shelf‐wide retreat began 26–26.5 ka at a rate of ~18.7–20.7 m a –1 . MSIS grounding zone wedges and DBIS recessional moraines show episodic retreat punctuated by prolonged still‐stands. By ~23–22 ka the outer shelf (~25 000 km 2 ) was free of grounded ice. After this time, MSIS retreat was faster (~20 m a –1 vs. ~2–6 m a –1 of DBIS). Separation of Irish and Scottish ice sources occurred ~20–19.5 ka, leaving an autonomous Donegal ice dome. Inner Malin shelf deglaciation followed the submarine troughs reaching the Hebridean coast ~19 ka. DBIS retreat formed the extensive complex of moraines in outer Donegal Bay at 20.5–19 ka. DBIS retreated on land by ~17–16 ka. Isolated ice caps in Scotland and Ireland persisted until ~14.5 ka. Early retreat of this marine‐terminating margin is best explained by local ice loading increasing water depths and promoting calving ice losses rather than by changes in global temperatures. Topographical controls governed the differences between the ice‐stream retreat from mid‐shelf to the coast.

Orchid bees (Apidae, Euglossini) from Oil Palm Plantations in Eastern Amazon Have Larger but Not Asymmetrical Wings - Thaline de Freitas Brito; Nelson S. Pinto; Colin C. Phifer; Jessie L. Knowlton; Felipe A. L. Contrera; Márcia M. Maués; Daniel P. Silva (Neotropical Entomology, 2021)

Residency, home range and tidal habitat use of Green Turtles (Chelonia mydas) in Port Curtis, Australia - Richard D. Pillans; Gary C. Fry; Michael D. E. Haywood; Wayne Rochester; Colin J. Limpus; Toby Patterson; Russel C. Babcock (Marine Biology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Smallholder perceptions of land restoration activities: rewetting tropical peatland oil palm areas in Sumatra, Indonesia - Caroline Ward; Lindsay C. Stringer; Eleanor Warren-Thomas; Fahmuddin Agus; Merry Crowson; Keith Hamer; Bambang Hariyadi; Winda D. Kartika; Jennifer Lucey; Colin McClean; Neneng L. Nurida; Nathalie Petorelli; et al. (Regional Environmental Change, 2021)
The Indonesian government committed to restoring over 2 million ha of degraded peatland by the end of 2020, mainly to reduce peat fires and greenhouse gas emissions. Although it is unlikely the government will meet this target, restoration projects are still underway. One restoration strategy involves blocking peatland drainage canals, but the consequences of this for smallholder farmers whose livelihoods are dependent on agriculture are unclear. This paper investigates perceived impacts of canal blocks on smallholder farmers and identifies factors that affect their willingness to accept canal blocks on their land. We use data from 181 household questionnaires collected in 2018 across three villages in Jambi province, Sumatra. We found that the majority of respondents would accept canal blocks on their farms, perceiving that the blocks would have no impact on yields or farm access, and would decrease fire risk. Respondents who would not accept blocks on their farms were more likely to use canals to access their farms and perceive that canal blocks would decrease yields. The majority of farmers unwilling to accept canal blocks did not change their mind when provided with an option of a block that would allow boat travel. Our results improve understanding of why some smallholders may be unwilling to engage with peatland restoration. Further research is needed to understand the impact of canal blocks on smallholders’ yields. Engaging with stakeholders from the outset to understand farmers’ concerns, and perceptions is key if the government is to succeed in meeting its peatland restoration target and to ensure that the costs and benefits of restoration are evenly shared between local stakeholders and other actors.

Proximity-based proteomics reveals the thylakoid lumen proteome in the cyanobacterium Synechococcus sp. PCC 7002 - Kelsey K. Dahlgren; Colin Gates; Thomas Lee; Jeffrey C. Cameron (Photosynthesis Research, 2021)
Cyanobacteria possess unique intracellular organization. Many proteomic studies have examined different features of cyanobacteria to learn about the intracellular structures and their respective functions. While these studies have made great progress in understanding cyanobacterial physiology, the conventional fractionation methods used to purify cellular structures have limitations; specifically, certain regions of cells cannot be purified with existing fractionation methods. Proximity-based proteomics techniques were developed to overcome the limitations of biochemical fractionation for proteomics. Proximity-based proteomics relies on spatiotemporal protein labeling followed by mass spectrometry of the labeled proteins to determine the proteome of the region of interest. We performed proximity-based proteomics in the cyanobacterium Synechococcus sp. PCC 7002 with the APEX2 enzyme, an engineered ascorbate peroxidase. We determined the proteome of the thylakoid lumen, a region of the cell that has remained challenging to study with existing methods, using a translational fusion between APEX2 and PsbU, a lumenal subunit of photosystem II. Our results demonstrate the power of APEX2 as a tool to study the cell biology of intracellular features and processes, including photosystem II assembly in cyanobacteria, with enhanced spatiotemporal resolution.

Identification of loci for pre-harvest sprouting resistance in the highly dormant spring wheat RL4137 - M. M. Uzzal A. Liton; Curt A. McCartney; Colin W. Hiebert; Santosh Kumar; Mark C. Jordan; Belay T. Ayele (Theoretical and Applied Genetics, 2021)

Reconstructing animal management practices at Greek Early Iron Age Zagora (Andros) using stable isotopes - Rudolph Alagich; Katerina Trantalidou; Margaret C. Miller; Colin Smith (Archaeological and Anthropological Sciences, 2021)

Techniques for In Vivo Measurement of Ligament and Tendon Strain: A Review - Qiang Zhang; Naomi C. Adam; S. H. Hosseini Nasab; William R. Taylor; Colin R. Smith (Annals of Biomedical Engineering, 2021)
The critical clinical and scientific insights achieved through knowledge of in vivo musculoskeletal soft tissue strains has motivated the development of relevant measurement techniques. This review provides a comprehensive summary of the key findings, limitations, and clinical impacts of these techniques to quantify musculoskeletal soft tissue strains during dynamic movements. Current technologies generally leverage three techniques to quantify in vivo strain patterns, including implantable strain sensors, virtual fibre elongation, and ultrasound. (1) Implantable strain sensors enable direct measurements of tissue strains with high accuracy and minimal artefact, but are highly invasive and current designs are not clinically viable. (2) The virtual fibre elongation method tracks the relative displacement of tissue attachments to measure strains in both deep and superficial tissues. However, the associated imaging techniques often require exposure to radiation, limit the activities that can be performed, and only quantify bone-to-bone tissue strains. (3) Ultrasound methods enable safe and non-invasive imaging of soft tissue deformation. However, ultrasound can only image superficial tissues, and measurements are confounded by out-of-plane tissue motion. Finally, all in vivo strain measurement methods are limited in their ability to establish the slack length of musculoskeletal soft tissue structures. Despite the many challenges and limitations of these measurement techniques, knowledge of in vivo soft tissue strain has led to improved clinical treatments for many musculoskeletal pathologies including anterior cruciate ligament reconstruction, Achilles tendon repair, and total knee replacement. This review provides a comprehensive understanding of these measurement techniques and identifies the key features of in vivo strain measurement that can facilitate innovative personalized sports medicine treatment.

Warming temperatures could expose more than 1.3 billion new people to Zika virus risk by 2050 - Sadie J. Ryan; Colin J. Carlson; Blanka Tesla; Matthew H. Bonds; Calistus N. Ngonghala; Erin A. Mordecai; Leah R. Johnson; Courtney C. Murdock (Global Change Biology, 2021)
In the aftermath of the 2015 pandemic of Zika virus (ZIKV), concerns over links between climate change and emerging arboviruses have become more pressing. Given the potential that much of the world might remain at risk from the virus, we used a previously established temperature‐dependent transmission model for ZIKV to project climate change impacts on transmission suitability risk by mid‐century (a generation into the future). Based on these model predictions, in the worst‐case scenario, over 1.3 billion new people could face suitable transmission temperatures for ZIKV by 2050. The next generation will face substantially increased ZIKV transmission temperature suitability in North America and Europe, where naïve populations might be particularly vulnerable. Mitigating climate change even to moderate emissions scenarios could significantly reduce global expansion of climates suitable for ZIKV transmission, potentially protecting around 200 million people. Given these suitability risk projections, we suggest an increased priority on research establishing the immune history of vulnerable populations, modeling when and where the next ZIKV outbreak might occur, evaluating the efficacy of conventional and novel intervention measures, and increasing surveillance efforts to prevent further expansion of ZIKV.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Shelterbelt systems establishment in Saskatchewan, Canada: a multi-criteria fuzzy logic approach to land suitability mapping - Beyhan Y. Amichev; Colin P. Laroque; Kenneth W. Belcher; Murray J. Bentham; Ken C. J. Van Rees (New Forests, 2020)

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Influence of the composition and diversity of tree fodder grazed on the selection and voluntary intake by cattle in a tropical forest - S. Albores-Moreno; J. A. Alayón-Gamboa; A. Morón-Ríos; P. N. Ortiz-Colin; J. Ventura-Cordero; P. G. González-Pech; G. E. Mendoza-Arroyo; J. C. Ku-Vera; G. Jiménez-Ferrer; A. T. Piñeiro-Vázquez (Agroforestry Systems, 2020)

Shelterbelt removals in Saskatchewan, Canada: implications for long-term carbon sequestration - Beyhan Y. Amichev; Colin P. Laroque; Ken C. J. Van Rees (Agroforestry Systems, 2020)

Inter‐ and intra‐specific interactions affecting crustacean trap fisheries—Implications for management - Daniel J. Skerritt; R. Colin A. Bannister; Nicholas V. C. Polunin; Clare Fitzsimmons (Fisheries Management and Ecology, 2020)
The UK coastal trap fisheries target two key species, European lobster Homarus gammarus (L.) and brown crab Cancer pagurus L. Their stock status is assessed periodically using size‐based, yield‐per‐recruit analysis. Fishery trends are described using landings and, where available, effort data to estimate catch per unit of effort (CPUE), nominally proportional to abundance. Despite being caught together, assessments assume that concurrent capture of these species does not distort their individual CPUE estimates. Here, an in situ experiment tested impacts of inter‐specific and intra‐specific interactions by pre‐loading baited traps with different species and observing subsequent catches. Pre‐loaded European lobster significantly reduced brown crab catches, whereas, other species produced no such effects. The findings highlight the likely inconsistency of using CPUE as an index of abundance if landings data originate from a mixed‐species fishery in which species interactions and targeting behaviour of fishers are unknown or un‐quantified.

Drivers of the enhanced decline of land near-surface relative humidity to abrupt 4xCO2 in CNRM-CM6-1 - Hervé Douville; B. Decharme; C. Delire; J. Colin; E. Joetzjer; R. Roehrig; D. Saint-Martin; T. Oudar; R. Stchepounoff; A. Voldoire (Climate Dynamics, 2020)

Environmental analyses to inform transitions to sustainable diets in developing countries: case studies for Vietnam and Kenya - Martin C. Heller; Abhijeet Walchale; Brent R. Heard; Lesli Hoey; Colin K. Khoury; Stef De Haan; Dharani Dhar Burra; Thi Thanh Duong; Jamleck Osiemo; Thi Huong Trinh; Andrew D. Jones (The International Journal of Life Cycle Assessment, 2020)

Long-Term Change of Demersal Fish Assemblages on the Inshore Agulhas Bank Between 1904 and 2015 - Jock C. Currie; Lara J. Atkinson; Kerry J. Sink; Colin G. Attwood (Frontiers in Marine Science, 2020)

Correction to: Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

Review of GPS collar deployments and performance on nonhuman primates - Kerry M. Dore; Malene F. Hansen; Amy R. Klegarth; Claudia Fichtel; Flávia Koch; Andrea Springer; Peter Kappeler; Joyce A. Parga; Tatyana Humle; Christelle Colin; Estelle Raballand; Zhi-Pang Huang; et al. (Primates, 2020)

The global distribution of grass functional traits within grassy biomes - Emma C. Jardine; Gavin H. Thomas; Elisabeth J. Forrestel; Caroline E. R. Lehmann; Colin P. Osborne (Journal of Biogeography, 2020)
Aim The sorting of functional traits along environmental gradients is an important driver of community and landscape scale patterns of functional diversity. However, the significance of environmental factors in driving functional gradients within biomes and across continents remains poorly understood. Here, we evaluate the relationship of soil nutrients and climate to leaf traits in grasses (Poaceae) that are hypothesized to reflect different strategies of resource use along gradients of resource availability. Location Global. Taxon Poaceae. Methods We made direct measurements on herbarium specimens to compile a global dataset of functional traits and realized environmental niche for 279 grass species that are common in grassland and savanna biomes. We examined the strength and direction of correlations between pairwise trait combinations and measured the distribution of traits in relation to gradients of soil properties and climate, while accounting for phylogenetic relatedness. Results Leaf trait variation among species follows two orthogonal axes. One axis represents leaf size and plant height, and we showed positive scaling relationships between these size‐related traits. The other axis corresponds to economic traits associated with resource acquisition and allocation, including leaf tensile strength (LTS), specific leaf area (SLA) and leaf nitrogen content (LNC). Global‐scale variation in LNC was primarily correlated with soil nutrients, while LTS, SLA and size‐related traits showed weak relationships to environment. However, most of the trait variation occurred within different vegetation types, independent of large‐scale environmental gradients. Main conclusions Our work provides evidence among grasses for relationships at the global scale between leaf economic traits and soil fertility, and for an influence of aridity on traits related to plant size. However, large unexplained variance and strong phylogenetic signal in the model residuals imply that at this scale the evolution of functional traits is driven by factors beyond contemporary environmental or climatic conditions.

UN Decade on Ecosystem Restoration 2021–2030—What Chance for Success in Restoring Coastal Ecosystems? - Nathan J. Waltham; Michael Elliott; Shing Yip Lee; Catherine Lovelock; Carlos M. Duarte; Christina Buelow; Charles Simenstad; Ivan Nagelkerken; Louw Claassens; Colin K-C Wen; Mario Barletta; Rod M. Connolly; et al. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of 21st‐century climate, land use, and disturbances on ecosystem carbon balance in California - Benjamin M. Sleeter; David C. Marvin; D. Richard Cameron; Paul C. Selmants; A.LeRoy Westerling; Jason Kreitler; Colin J. Daniel; Jinxun Liu; Tamara S. Wilson (Global Change Biology, 2019)
Terrestrial ecosystems are an important sink for atmospheric carbon dioxide (CO 2 ), sequestering ~30% of annual anthropogenic emissions and slowing the rise of atmospheric CO 2 . However, the future direction and magnitude of the land sink is highly uncertain. We examined how historical and projected changes in climate, land use, and ecosystem disturbances affect the carbon balance of terrestrial ecosystems in California over the period 2001–2100. We modeled 32 unique scenarios, spanning 4 land use and 2 radiative forcing scenarios as simulated by four global climate models. Between 2001 and 2015, carbon storage in California's terrestrial ecosystems declined by −188.4 Tg C, with a mean annual flux ranging from a source of −89.8 Tg C/year to a sink of 60.1 Tg C/year. The large variability in the magnitude of the state's carbon source/sink was primarily attributable to interannual variability in weather and climate, which affected the rate of carbon uptake in vegetation and the rate of ecosystem respiration. Under nearly all future scenarios, carbon storage in terrestrial ecosystems was projected to decline, with an average loss of −9.4% (−432.3 Tg C) by the year 2100 from current stocks. However, uncertainty in the magnitude of carbon loss was high, with individual scenario projections ranging from −916.2 to 121.2 Tg C and was largely driven by differences in future climate conditions projected by climate models. Moving from a high to a low radiative forcing scenario reduced net ecosystem carbon loss by 21% and when combined with reductions in land‐use change (i.e., moving from a high to a low land‐use scenario), net carbon losses were reduced by 55% on average. However, reconciling large uncertainties associated with the effect of increasing atmospheric CO 2 is needed to better constrain models used to establish baseline conditions from which ecosystem‐based climate mitigation strategies can be evaluated.

Anthropogenic modifications to fire regimes in the wider Serengeti‐Mara ecosystem - James R. Probert; Catherine L. Parr; Ricardo M. Holdo; T. Michael Anderson; Sally Archibald; Colin J. Courtney Mustaphi; Andrew P. Dobson; Jason E. Donaldson; Grant C. Hopcraft; Gareth P. Hempson; Thomas A. Morrison; Colin M. Beale (Global Change Biology, 2019)
Fire is a key driver in savannah systems and widely used as a land management tool. Intensifying human land uses are leading to rapid changes in the fire regimes, with consequences for ecosystem functioning and composition. We undertake a novel analysis describing spatial patterns in the fire regime of the Serengeti‐Mara ecosystem, document multidecadal temporal changes and investigate the factors underlying these patterns. We used MODIS active fire and burned area products from 2001 to 2014 to identify individual fires; summarizing four characteristics for each detected fire: size, ignition date, time since last fire and radiative power. Using satellite imagery, we estimated the rate of change in the density of livestock bomas as a proxy for livestock density. We used these metrics to model drivers of variation in the four fire characteristics, as well as total number of fires and total area burned. Fires in the Serengeti‐Mara show high spatial variability—with number of fires and ignition date mirroring mean annual precipitation. The short‐term effect of rainfall decreases fire size and intensity but cumulative rainfall over several years leads to increased standing grass biomass and fuel loads, and, therefore, in larger and hotter fires. Our study reveals dramatic changes over time, with a reduction in total number of fires and total area burned, to the point where some areas now experience virtually no fire. We suggest that increasing livestock numbers are driving this decline, presumably by inhibiting fire spread. These temporal patterns are part of a global decline in total area burned, especially in savannahs, and we caution that ecosystem functioning may have been compromised. Land managers and policy formulators need to factor in rapid fire regime modifications to achieve management objectives and maintain the ecological function of savannah ecosystems.

Four priorities for new links between conservation science and accounting research - Clément Feger; Laurent Mermet; Bhaskar Vira; Prue F.E. Addison; Richard Barker; Frank Birkin; John Burns; Stuart Cooper; Denis Couvet; Thomas Cuckston; Gretchen C. Daily; Colin Dey; et al. (Conservation Biology, 2019)
Article impact statement : New collaborations with accounting research can improve conservation impact of ecosystem‐based information systems.

Pectobacterium and Dickeya species detected in vegetables in Northern Ireland - Maja A. Zaczek-Moczydłowska; Colin C. Fleming; Gillian K. Young; Katrina Campbell; Richard O’Hanlon (European Journal of Plant Pathology, 2019)
Destructive soft rot Pectobacteriaceae affect a number of vegetable crops and cause high economic loses in the field and storage. The diversity of Pectobacterium and Dickeya causing soft rot of vegetables in Northern Ireland is unknown. This study provides details of Pectobacterium and Dickeya spp. detected in vegetables from several locations in Northern Ireland in the years 2015–2017. Soft rot Pectobacteriaceae were identified based on DNA sequences. Thirty one strains were selected for further phylogenetic analysis based on the recA gene region. Results from the testing of over 3456 potato samples for plant health statutory purposes in years 2005–2017 demonstrated that Dickeya spp. is not the major pathogen causing soft rot or blackleg in Northern Ireland. The most predominant species causing soft rot of vegetables in Northern Ireland were Pectobacterium atrosepticum and Pectobacterium carotovorum subsp. carotovorum . Pectobacterium atrosepticum was also detected on hosts other than potato . Testing of bacteria isolated from carrots led to the detection of P. carotovorum and Dickeya sp. This is the first study to provide knowledge about Pectobacterium and Dickeya spp. diversity causing soft rot of vegetables in Northern Ireland confirmed by real-time PCR and DNA sequences. This is also the first report of the detection of D. aquatica from a source other than water.

Palynology of Iron Age and Gallo-Roman archaeological sediments from Beaurieux Les Grèves, Aisne, France - James B. Innes; Colin C. Haselgrove (Vegetation History and Archaeobotany, 2019)

The influence of tourism-based provisioning on fish behavior and benthic composition - Colin K. C. Wen; Kao-Sung Chen; Wei-Chen Tung; Anyo Chao; Ching-Wei Wang; Shao-Lun Liu; Ming-Jay Ho (Ambio, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Horizon scanning for invasive alien species with the potential to threaten biodiversity and human health on a Mediterranean island - Jodey Peyton; Angeliki F. Martinou; Oliver L. Pescott; Monica Demetriou; Tim Adriaens; Margarita Arianoutsou; Ioannis Bazos; Colin W. Bean; Olaf Booy; Marc Botham; J. Robert Britton; Javier Lobon Cervia; et al. (Biological Invasions, 2019)

Evidence from plutonic xenoliths for magma differentiation, mixing and storage in a volatile-rich crystal mush beneath St. Eustatius, Lesser Antilles - George F. Cooper; Jon D. Blundy; Colin G. Macpherson; Madeleine C. S. Humphreys; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Long‐term dietary shift and population decline of a pelagic seabird—A health check on the tropical Atlantic? - S. James Reynolds; B. John Hughes; Colin P. Wearn; Roger C. Dickey; Judith Brown; Nicola L. Weber; Sam B. Weber; Vitor H. Paiva; Jaime A. Ramos (Global Change Biology, 2019)
In the face of accelerating ecological change to the world's oceans, seabirds are some of the best bio‐indicators of marine ecosystem function. However, unravelling ecological changes that pre‐date modern monitoring programmes remains challenging. Using stable isotope analysis of feathers and regurgitants collected from sooty terns ( Onychoprion fuscatus ) nesting at a major Atlantic colony, we reconstructed a long‐term dietary time series from 1890 to the present day and show that a significant dietary shift occurred during the second half of the twentieth century coinciding with an apparent population collapse of approximately 84%. After correcting for the “Suess Effect,” δ 13 C in feathers declined by ~1.5‰ and δ 15 N by ~2‰ between the 1890s and the present day, indicating that birds changed their diets markedly over the period of population decline. Isotopic niches were equally wide before and after the population collapse but isotopic mixing models suggest that birds have grown ever more reliant on nutrient‐poor squid and invertebrates as teleost fish have declined in availability. Given that sooty terns rely heavily on associations with sub‐surface predators such as tuna to catch fish prey, the rapid expansion of industrialized fisheries for these species over the same period seems a plausible mechanism. Our results suggest that changes to marine ecosystems over the past 60 years have had a dramatic impact on the ecology of the most abundant seabird of tropical oceans, and highlight the potentially pervasive consequences of large predatory fish depletion on marine ecosystem function.

Ionome and elemental transport kinetics shaped by parallel evolution in threespine stickleback - Seth M. Rudman; Jared M. Goos; Joseph B. Burant; Kevin V. Brix; Taylor C. Gibbons; Colin J. Brauner; Punidan D. Jeyasingh (Ecology Letters, 2019)
Evidence that organisms evolve rapidly enough to alter ecological dynamics necessitates investigation of the reciprocal links between ecology and evolution. Data that link genotype to phenotype to ecology are needed to understand both the process and ecological consequences of rapid evolution. Here, we quantified the suite of elements in individuals (i.e., ionome) and differences in the fluxes of key nutrients across populations of threespine stickleback. We find that allelic variation associated with freshwater adaptation that controls bony plating is associated with changes in the ionome and nutrient recycling. More broadly, we find that adaptation of marine stickleback to freshwater conditions shifts the ionomes of natural populations and populations raised in common gardens. In both cases ionomic divergence between populations was primarily driven by differences in trace elements rather than elements typically associated with bone. These findings demonstrate the utility of ecological stoichiometry and the importance of ionome‐wide data in understanding eco‐evolutionary dynamics.

A morphology-based drowning risk index for rock platform fishing: a case study from southeastern Australia - Rafael C. Carvalho; David M. Kennedy; Colin D. Woodroffe (Natural Hazards, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Evidence gaps and biodiversity threats facing the marine environment of the United Kingdom’s Overseas Territories - Bethan C. O’Leary; Philip Fieldhouse; Colin J. McClean; Adriana E. S. Ford; Polly Burns; Julie P. Hawkins; Callum M. Roberts (Biodiversity and Conservation, 2019)

Microplastic ingestion ubiquitous in marine turtles - Emily M. Duncan; Annette C. Broderick; Wayne J. Fuller; Tamara S. Galloway; Matthew H. Godfrey; Mark Hamann; Colin J. Limpus; Penelope K. Lindeque; Andrew G. Mayes; Lucy C. M. Omeyer; David Santillo; Robin T. E. Snape; et al. (Global Change Biology, 2019)
Despite concerns regarding the environmental impacts of microplastics, knowledge of the incidence and levels of synthetic particles in large marine vertebrates is lacking. Here, we utilize an optimized enzymatic digestion methodology, previously developed for zooplankton, to explore whether synthetic particles could be isolated from marine turtle ingesta. We report the presence of synthetic particles in every turtle subjected to investigation ( n = 102) which included individuals from all seven species of marine turtle, sampled from three ocean basins (Atlantic [ATL]: n = 30, four species; Mediterranean (MED): n = 56, two species; Pacific (PAC): n = 16, five species). Most particles ( n = 811) were fibres (ATL: 77.1% MED: 85.3% PAC: 64.8%) with blue and black being the dominant colours. In lesser quantities were fragments (ATL: 22.9%: MED: 14.7% PAC: 20.2%) and microbeads (4.8%; PAC only; to our knowledge the first isolation of microbeads from marine megavertebrates). Fourier transform infrared spectroscopy (FT‐IR) of a subsample of particles ( n = 169) showed a range of synthetic materials such as elastomers (MED: 61.2%; PAC: 3.4%), thermoplastics (ATL: 36.8%: MED: 20.7% PAC: 27.7%) and synthetic regenerated cellulosic fibres (SRCF; ATL: 63.2%: MED: 5.8% PAC: 68.9%). Synthetic particles being isolated from species occupying different trophic levels suggest the possibility of multiple ingestion pathways. These include exposure from polluted seawater and sediments and/or additional trophic transfer from contaminated prey/forage items. We assess the likelihood that microplastic ingestion presents a significant conservation problem at current levels compared to other anthropogenic threats.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

The role of macroinvertebrates in the distribution of lead (Pb) within an urban marsh ecosystem - Suzanne C. Ryan; Colin S. Belby; Tisha C. King-Heiden; Roger J. Haro; Jacob Ogorek; Gretchen A. Gerrish (Hydrobiologia, 2019)

Climatic Sensitivity of Dryland Soil CO2 Fluxes Differs Dramatically with Biological Soil Crust Successional State - Colin L. Tucker; Scott Ferrenberg; Sasha C. Reed (Ecosystems, 2019)

Unravelling the complexity of magma plumbing at Mount St. Helens: a new trace element partitioning scheme for amphibole - Madeleine C. S. Humphreys; George F. Cooper; Jing Zhang; Matthew Loewen; Adam J. R. Kent; Colin G. Macpherson; Jon P. Davidson (Contributions to Mineralogy and Petrology, 2019)

Standard metabolic rate models for Carmine Shiner ( Notropis percobromus ) and Common Shiner ( Luxilus cornutus ) across different temperature regimes - Camille J. Macnaughton; Colin Kovachik; Eva C. Enders (Journal of Fish Biology, 2019)
Standard metabolic rates (SMR) were measured empirically for carmine shiner Notropis percobromus and common shiner Luxilus cornutus to develop SMR models that predict metabolic responses of each species under thermal conditions observed in the wild. SMR increased significantly with body mass and rising water temperature, ranging from 0.05 mg O 2 h −1 at 10°C to 0.89 mg O 2 h −1 at 20°C for N. percobromus weighing 0.6–2.5 g and from 0.11 mg O 2 h −1 at 10°C to 0.98 mg O 2 h −1 at 20°C for L. cornutus weighing 0.8–6.6 g. SMR models significantly differed between sympatric species on account of differences in model intercepts ( RA ) and temperature coefficients ( RQ ), however, the allometric relationships between mass and SMR did not significantly differ between species. Known distribution of N. percobromus and L. cornutus includes the Birch River located in Manitoba, Canada, where N. percobromus is listed as Endangered. Little is known about the physiology of N. percobromus or the species' ability to acclimate or adapt to different environmental conditions. While size differences between species contributed, in part, to differences in SMR predictions for Birch River populations, SMR trends ( 2 h −1 ) for individuals weighing 1 g were similar for both species across daily temperatures. Respirometry experiments contributed to developing species‐specific SMR models and inform on the effect of natural and anthropogenic stressors, namely water temperature, on the conservation of N. percobromus in this ecosystem.

Disinfection and removal of human pathogenic bacteria in arctic waste stabilization ponds - Yannan Huang; Lisbeth Truelstrup Hansen; Colin M. Ragush; Rob C. Jamieson (Environmental Science and Pollution Research, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Rapid thermal adaptation in a marine diatom reveals constraints and trade‐offs - Daniel R. O'Donnell; Carolyn R. Hamman; Evan C. Johnson; Colin T. Kremer; Christopher A. Klausmeier; Elena Litchman (Global Change Biology, 2018)
Rapid evolution in response to environmental change will likely be a driving force determining the distribution of species across the biosphere in coming decades. This is especially true of microorganisms, many of which may evolve in step with warming, including phytoplankton, the diverse photosynthetic microbes forming the foundation of most aquatic food webs. Here we tested the capacity of a globally important, model marine diatom Thalassiosira pseudonana , for rapid evolution in response to temperature. Selection at 16 and 31°C for 350 generations led to significant divergence in several temperature response traits, demonstrating local adaptation and the existence of trade‐offs associated with adaptation to different temperatures. In contrast, competitive ability for nitrogen (commonly limiting in marine systems), measured after 450 generations of temperature selection, did not diverge in a systematic way between temperatures. This study shows how rapid thermal adaptation affects key temperature and nutrient traits and, thus, a population's long‐term physiological, ecological, and biogeographic response to climate change.

Continental‐scale nitrogen pollution is shifting forest mycorrhizal associations and soil carbon stocks - Colin Averill; Michael C. Dietze; Jennifer M. Bhatnagar (Global Change Biology, 2018)
Most tree roots on Earth form a symbiosis with either ecto‐ or arbuscular mycorrhizal fungi. Nitrogen fertilization is hypothesized to favor arbuscular mycorrhizal tree species at the expense of ectomycorrhizal species due to differences in fungal nitrogen acquisition strategies, and this may alter soil carbon balance, as differences in forest mycorrhizal associations are linked to differences in soil carbon pools. Combining nitrogen deposition data with continental‐scale US forest data, we show that nitrogen pollution is spatially associated with a decline in ectomycorrhizal vs. arbuscular mycorrhizal trees. Furthermore, nitrogen deposition has contrasting effects on arbuscular vs. ectomycorrhizal demographic processes, favoring arbuscular mycorrhizal trees at the expense of ectomycorrhizal trees, and is spatially correlated with reduced soil carbon stocks. This implies future changes in nitrogen deposition may alter the capacity of forests to sequester carbon and offset climate change via interactions with the forest microbiome.

Effects of habitat type change on taxonomic and functional composition of orchid bees (Apidae: Euglossini) in the Brazilian Amazon - Thaline F. Brito; Felipe A. L. Contrera; Colin C. Phifer; Jessie L. Knowlton; Leandro S. Brasil; Márcia M. Maués; Daniel P. Silva (Journal of Insect Conservation, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Modelling Hydrodynamic Impacts of Sea-Level Rise on Wave-Dominated Australian Estuaries with Differing Geomorphology - Kristian Kumbier; Rafael C. Carvalho; Colin D. Woodroffe (Journal of Marine Science and Engineering, 2018)
Sea-level rise (SLR) will affect the hydrodynamics and flooding characteristics of estuaries which are a function of the geomorphology of particular estuarine systems. This study presents a numerical modelling of coastal flooding due to drivers such as spring-tides, storm surges and river inflows and examines how these will change under sea-level increases of 0.4 m and 0.9 m for two estuaries that are at different geomorphological evolutionary stages of infill. Our results demonstrate that estuarine response to SLR varies between different types of estuaries, and detailed modelling is necessary to understand the nature and extent of inundation in response to SLR. Comparison of modelling results indicates that floodplain elevation is fundamental in order to identify the most vulnerable systems and estimate how inundation extents and depths may change in the future. Floodplains in mature estuarine systems may drown and experience a considerable increase in inundation depths once a certain threshold in elevation has been exceeded. By contrast, immature estuarine systems may be subject to increases in relative inundation extent and substantial changes in hydrodynamics such as tidal range and current velocity. The unique nature of estuaries does not allow for generalisations; however, classifications of estuarine geomorphology could indicate how certain types of estuary may respond to SLR.

Textural and micro-analytical insights into mafic–felsic interactions during the Oruanui eruption, Taupo - Shane M. Rooyakkers; Colin J. N. Wilson; C. Ian Schipper; Simon J. Barker; Aidan S. R. Allan (Contributions to Mineralogy and Petrology, 2018)

Valuable elements in Chinese coals: a review - Shifeng Dai; Xiaoyun Yan; Colin R. Ward; James C. Hower; Lei Zhao; Xibo Wang; Lixin Zhao; Deyi Ren; Robert B. Finkelman (International Geology Review, 2018)

Offshore ocean dispersal of adult Dolly Varden Salvelinus malma in the Beaufort Sea - Michael B. Courtney; Brendan Scanlon; Randy J. Brown; Audun H. Rikardsen; Colin P. Gallagher; Andrew C. Seitz (Polar Biology, 2018)

The microbiology and treatment of human mastitis - Angeliki Angelopoulou; Des Field; C. Anthony Ryan; Catherine Stanton; Colin Hill; R. Paul Ross (Medical Microbiology and Immunology, 2018)

Evacuation of multiple magma bodies and the onset of caldera collapse in a supereruption, captured in glass and mineral compositions - Elliot J. Swallow; Colin J. N. Wilson; Madison L. Myers; Paul J. Wallace; Katie S. Collins; Euan G. C. Smith (Contributions to Mineralogy and Petrology, 2018)

Cytochrome b 5 impacts on cytochrome P450-mediated metabolism of benzo[a]pyrene and its DNA adduct formation: studies in hepatic cytochrome b 5 /P450 reductase null (HBRN) mice - Lindsay Reed; Iveta Mrizova; Frantisek Barta; Radek Indra; Michaela Moserova; Klaus Kopka; Heinz H. Schmeiser; C. Roland Wolf; Colin J. Henderson; Marie Stiborova; David H. Phillips; Volker M. Arlt (Archives of Toxicology, 2018)

The 5-HT2C receptor agonist meta-chlorophenylpiperazine (mCPP) reduces palatable food consumption and BOLD fMRI responses to food images in healthy female volunteers - Jason M. Thomas; Colin T. Dourish; Jeremy Tomlinson; Zaki Hassan-Smith; Peter C. Hansen; Suzanne Higgs (Psychopharmacology, 2018)

Barriers and Solutions to Conducting Large International, Interdisciplinary Research Projects - Erin C. Pischke; Jessie L. Knowlton; Colin C. Phifer; Jose Gutierrez Lopez; Tamara S. Propato; Amarella Eastmond; Tatiana Martins de Souza; Mark Kuhlberg; Valentin Picasso Risso; Santiago R. Veron; Carlos Garcia; Marta Chiappe; et al. (Environmental Management, 2017)

Bird community responses to afforested eucalyptus plantations in the Argentine pampas - Colin C. Phifer; Jessie L. Knowlton; Christopher R. Webster; David J. Flaspohler; Julian A. Licata (Biodiversity and Conservation, 2017)

Social and spatial effects on genetic variation between foraging flocks in a wild bird population - Reinder Radersma; Colin J. Garroway; Anna W. Santure; Isabelle de Cauwer; Damien R. Farine; Jon Slate; Ben C. Sheldon (Molecular Ecology, 2017)
Social interactions are rarely random. In some instances, animals exhibit homophily or heterophily, the tendency to interact with similar or dissimilar conspecifics, respectively. Genetic homophily and heterophily influence the evolutionary dynamics of populations, because they potentially affect sexual and social selection. Here, we investigate the link between social interactions and allele frequencies in foraging flocks of great tits ( Parus major ) over three consecutive years. We constructed co‐occurrence networks which explicitly described the splitting and merging of 85,602 flocks through time (fission–fusion dynamics), at 60 feeding sites. Of the 1,711 birds in those flocks, we genotyped 962 individuals at 4,701 autosomal single nucleotide polymorphisms ( SNP s). By combining genomewide genotyping with repeated field observations of the same individuals, we were able to investigate links between social structure and allele frequencies at a much finer scale than was previously possible. We explicitly accounted for potential spatial effects underlying genetic structure at the population level. We modelled social structure and spatial configuration of great tit fission–fusion dynamics with eigenvector maps. Variance partitioning revealed that allele frequencies were strongly affected by group fidelity (explaining 27%–45% of variance) as individuals tended to maintain associations with the same conspecifics. These conspecifics were genetically more dissimilar than expected, shown by genomewide heterophily for pure social (i.e., space‐independent) grouping preferences. Genomewide homophily was linked to spatial configuration, indicating spatial segregation of genotypes. We did not find evidence for homophily or heterophily for putative socially relevant candidate genes or any other SNP markers. Together, these results demonstrate the importance of distinguishing social and spatial processes in determining population structure.

A Simple Method for the Purification of Nisin - Ronan Gough; Beatriz Gómez-Sala; Paula M. O’Connor; Mary C. Rea; Song Miao; Colin Hill; André Brodkorb (Probiotics and Antimicrobial Proteins, 2017)

The role of ecology, neutral processes and antagonistic coevolution in an apparent sexual arms race - Jennifer C. Perry; Colin J. Garroway; Locke Rowe (Ecology Letters, 2017)
Some of the strongest examples of a sexual ‘arms race’ come from observations of correlated evolution in sexually antagonistic traits among populations. However, it remains unclear whether these cases truly represent sexually antagonistic coevolution; alternatively, ecological or neutral processes might also drive correlated evolution. To investigate these alternatives, we evaluated the contributions of intersex genetic correlations, ecological context, neutral genetic divergence and sexual coevolution in the correlated evolution of antagonistic traits among populations of Gerris incognitus water striders. We could not detect intersex genetic correlations for these sexually antagonistic traits. Ecological variation was related to population variation in the key female antagonistic trait (spine length, a defence against males), as well as body size. Nevertheless, population covariation between sexually antagonistic traits remained substantial and significant even after accounting for all of these processes. Our results therefore provide strong evidence for a contemporary sexual arms race.

The transcriptional landscape of seasonal coat colour moult in the snowshoe hare - Mafalda S. Ferreira; Paulo C. Alves; Colin M. Callahan; João P. Marques; L. Scott Mills; Jeffrey M. Good; José Melo‐Ferreira (Molecular Ecology, 2017)
Seasonal coat colour change is an important adaptation to seasonally changing environments but the evolution of this and other circannual traits remains poorly understood. In this study, we use gene expression to understand seasonal coat colour moulting in wild snowshoe hares ( Lepus americanus ). We used hair colour to follow the progression of the moult, simultaneously sampling skin from three moulting stages in hares collected during the peak of the spring moult from white winter to brown summer pelage. Using RNA sequencing, we tested whether patterns of expression were consistent with predictions based on the established phases of the hair growth cycle. We found functionally consistent clustering across skin types, with 766 genes differentially expressed between moult stages. “White” pelage showed more differentially expressed genes that were upregulated relative to other skin types, involved in the transition between late telogen (quiescent stage) and the onset of anagen (proliferative stage). Skin samples from transitional “intermediate” and “brown” pelage were transcriptionally similar and resembled the regressive transition to catagen (regressive stage). We also detected differential expression of several key circadian clock and pigmentation genes, providing important means to dissect the bases of alternate seasonal colour morphs. Our results reveal that pelage colour is a useful biomarker for seasonal change but that there is a consistent lag between the main gene expression waves and change in visible coat colour. These experiments establish that developmental sampling from natural populations of nonmodel organisms can provide a crucial resource to dissect the genetic basis and evolution of complex seasonally changing traits.

A cascade of magmatic events during the assembly and eruption of a super-sized magma body - Aidan. S. R. Allan; Simon J. Barker; Marc-Alban Millet; Daniel J. Morgan; Shane M. Rooyakkers; C. Ian Schipper; Colin J. N. Wilson (Contributions to Mineralogy and Petrology, 2017)

Multi-criteria correlation of tephra deposits to source centres applied in the Auckland Volcanic Field, New Zealand - Jenni L. Hopkins; Colin J. N. Wilson; Marc-Alban Millet; Graham S. Leonard; Christian Timm; Lucy E. McGee; Ian E. M. Smith; Euan G. C. Smith (Bulletin of Volcanology, 2017)

Induction of anthocyanin in the inner epidermis of red onion leaves by environmental stimuli and transient expression of transcription factors - Elizabeth J. Wiltshire; Colin C. Eady; David A. Collings (Plant Cell Reports, 2017)

Decreasing worker size diversity does not affect colony performance during laboratory challenges in the ant Temnothorax nylanderi - T. Colin; C. Doums; R. Péronnet; M. Molet (Behavioral Ecology and Sociobiology, 2017)

Current and projected global distribution of Phytophthora cinnamomi , one of the world's worst plant pathogens - Treena I. Burgess; John K. Scott; Keith L. Mcdougall; Michael J. C. Stukely; Colin Crane; William A. Dunstan; Frances Brigg; Vera Andjic; Diane White; Tim Rudman; Frans Arentz; Noboru Ota; et al. (Global Change Biology, 2017)
Globally, Phytophthora cinnamomi is listed as one of the 100 worst invasive alien species and active management is required to reduce impact and prevent spread in both horticulture and natural ecosystems. Conversely, there are regions thought to be suitable for the pathogen where no disease is observed. We developed a climex model for the global distribution of P. cinnamomi based on the pathogen's response to temperature and moisture and by incorporating extensive empirical evidence on the presence and absence of the pathogen. The climex model captured areas of climatic suitability where P. cinnamomi occurs that is congruent with all available records. The model was validated by the collection of soil samples from asymptomatic vegetation in areas projected to be suitable by the model for which there were few records. DNA was extracted, and the presence or absence of P. cinnamomi was determined by high‐throughput sequencing ( HTS ). While not detected using traditional isolation methods, HTS detected P. cinnamomi at higher elevations in eastern Australia and central Tasmania as projected by the climex model. Further support for the climex model was obtained using the large data set from south‐west Australia where the proportion of positive records in an area is related to the Ecoclimatic Index value for the same area. We provide for the first time a comprehensive global map of the current P. cinnamomi distribution, an improved climex model of the distribution, and a projection to 2080 of the distribution with predicted climate change. This information provides the basis for more detailed regional‐scale modelling and supports risk assessment for governments to plan management of this important soil‐borne plant pathogen.

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Analysis of G ambierdiscus transcriptome data supports ancient origins of mixotrophic pathways in dinoflagellates - Dana C. Price; Natalie Farinholt; Colin Gates; Alexander Shumaker; Nicole E. Wagner; Paul Bienfang; Debashish Bhattacharya (Environmental Microbiology, 2016)
Summary Toxic dinoflagellates pose serious threats to human health and to fisheries. The genus Gambierdiscus is significant in this respect because its members produce ciguatoxin that accumulates in predominantly tropical marine food webs and leads to ciguatera fish poisoning. Understanding the biology of toxic dinoflagellates is crucial to developing control strategies. To this end, we generated a de novo transcriptome library from G. caribaeus and studied its growth under different culture conditions to elucidate pathways of carbon (C) and nitrogen (N) utilization. We also gathered available dinoflagellate transcriptome data to trace the evolutionary history of C and N pathways in this phylum. We find that rather than being specific adaptations to the epiphytic lifestyle in G. caribaeus , the majority of dinoflagellates share a large array of genes that putatively confer mixotrophy and the ability to use N via the ornithine‐urea cycle and nitric oxide synthase production. These results suggest that prior to plastid endosymbiosis, the dinoflagellate ancestor possessed complex pathways that linked metabolism, intercellular signaling, and stress responses to environmental cues that have been maintained by extant photosynthetic species. This metabolic flexibility likely explains the success of dinoflagellates in marine ecosystems and may presage difficulties in controlling the spread of toxic species.

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

A Conceptualization of the Utility of Subjective Cognitive Decline in Clinical Trials of Preclinical Alzheimer’s Disease - Rachel F. Buckley; Victor L. Villemagne; Colin L. Masters; Kathryn A. Ellis; Christopher C. Rowe; Keith Johnson; Reisa Sperling; Rebecca Amariglio (Journal of Molecular Neuroscience, 2016)

The effects of four transplantation methods on five coral species at the Sanya Bay - Yuyang Zhang; Hui Huang; Jieying Huang; Feng You; Jiansheng Lian; Jianhui Yang; Colin K. C. Wen (Acta Oceanologica Sinica, 2016)

LSD1-Mediated Demethylation of H3K4me2 Is Required for the Transition from Late Progenitor to Differentiated Mouse Rod Photoreceptor - Evgenya Y. Popova; Carolina Pinzon-Guzman; Anna C. Salzberg; Samuel Shao-Min Zhang; Colin J. Barnstable (Molecular Neurobiology, 2016)

Isolation of isoprene degrading bacteria from soils, development of isoA gene probes and identification of the active isoprene‐degrading soil community using DNA‐stable isotope probing - Myriam El Khawand; Andrew T. Crombie; Antonia Johnston; Dmitrii V. Vavlline; Joseph C. McAuliffe; Jacob A. Latone; Yuliya A. Primak; Sang‐Kyu Lee; Gregg M. Whited; Terry J. McGenity; J. Colin Murrell (Environmental Microbiology, 2016)
Summary Emissions of biogenic volatile organic compounds (bVOCs), are an important element in the global carbon cycle, accounting for a significant proportion of fixed carbon. They contribute directly and indirectly to global warming and climate change and have a major effect on atmospheric chemistry. Plants emit isoprene to the atmosphere in similar quantities to emissions of methane from all sources and each accounts for approximately one third of total VOCs. Although methanotrophs, capable of growth on methane, have been intensively studied, we know little of isoprene biodegradation. Here, we report the isolation of two isoprene‐degrading strains from the terrestrial environment and describe the design and testing of polymerase chain reaction (PCR) primers targeting isoA , the gene encoding the active‐site component of the conserved isoprene monooxygenase, which are capable of retrieving isoA sequences from isoprene‐enriched environmental samples. Stable isotope probing experiments, using biosynthesized 13 C‐labelled isoprene, identified the active isoprene‐degrading bacteria in soil. This study identifies novel isoprene‐degrading strains using both culture‐dependent and, for the first time, culture‐independent methods and provides the tools and foundations for continued investigation of the biogeography and molecular ecology of isoprene‐degrading bacteria.

Paradigms for parasite conservation - Eric R. Dougherty; Colin J. Carlson; Veronica M. Bueno; Kevin R. Burgio; Carrie A. Cizauskas; Christopher F. Clements; Dana P. Seidel; Nyeema C. Harris (Conservation Biology, 2016)
Parasitic species, which depend directly on host species for their survival, represent a major regulatory force in ecosystems and a significant component of Earth's biodiversity. Yet the negative impacts of parasites observed at the host level have motivated a conservation paradigm of eradication, moving us farther from attainment of taxonomically unbiased conservation goals. Despite a growing body of literature highlighting the importance of parasite‐inclusive conservation, most parasite species remain understudied, underfunded, and underappreciated. We argue the protection of parasitic biodiversity requires a paradigm shift in the perception and valuation of their role as consumer species, similar to that of apex predators in the mid‐20th century. Beyond recognizing parasites as vital trophic regulators, existing tools available to conservation practitioners should explicitly account for the unique threats facing dependent species. We built upon concepts from epidemiology and economics (e.g., host‐density threshold and cost‐benefit analysis) to devise novel metrics of margin of error and minimum investment for parasite conservation. We define margin of error as the risk of accidental host extinction from misestimating equilibrium population sizes and predicted oscillations, while minimum investment represents the cost associated with conserving the additional hosts required to maintain viable parasite populations. This framework will aid in the identification of readily conserved parasites that present minimal health risks. To establish parasite conservation, we propose an extension of population viability analysis for host–parasite assemblages to assess extinction risk. In the direst cases, ex situ breeding programs for parasites should be evaluated to maximize success without undermining host protection. Though parasitic species pose a considerable conservation challenge, adaptations to conservation tools will help protect parasite biodiversity in the face of an uncertain environmental future.

Genetic mapping of SrCad and SNP marker development for marker-assisted selection of Ug99 stem rust resistance in wheat - Mulualem T. Kassa; Frank M. You; Tom G. Fetch; Pierre Fobert; Andrew Sharpe; Curtis J. Pozniak; James G. Menzies; Mark C. Jordan; Gavin Humphreys; Tingting Zhu; Ming-Cheng Luo; Curt A. McCartney; et al. (Theoretical and Applied Genetics, 2016)

Dietary shift in juvenile coral trout (Plectropomus maculatus) following coral reef degradation from a flood plume disturbance - Colin K. C. Wen; Mary C. Bonin; Hugo B. Harrison; David H. Williamson; Geoffrey P. Jones (Coral Reefs, 2016)

A geostatistical approach for delineating the potential groundwater recharge zones in the hard rock terrain of Tirunelveli taluk, Tamil Nadu, India - M. Kirubakaran; J. Colins Johnny; C. Ashokraj; S. Arivazhagan (Arabian Journal of Geosciences, 2016)

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

How plants connect pollination and herbivory networks and their contribution to community stability - Alix M. C. Sauve; Elisa Thébault; Michael J. O. Pocock; Colin Fontaine (Ecology, 2016)
Pollination and herbivory networks have mainly been studied separately, highlighting their distinct structural characteristics and the related processes and dynamics. However, most plants interact with both pollinators and herbivores, and there is evidence that both types of interaction affect each other. Here we investigated the way plants connect these mutualistic and antagonistic networks together, and the consequences for community stability. Using an empirical data set, we show that the way plants connect pollination and herbivory networks is not random and promotes community stability. Analyses of the structure of binary and quantitative networks show different results: the plants’ generalism with regard to pollinators is positively correlated to their generalism with regard to herbivores when considering binary interactions, but not when considering quantitative interactions. We also show that plants that share the same pollinators do not share the same herbivores. However, the way plants connect pollination and herbivory networks promotes stability for both binary and quantitative networks. Our results highlight the relevance of considering the diversity of interaction types in ecological communities, and stress the need to better quantify the costs and benefits of interactions, as well as to develop new metrics characterizing the way different interaction types are combined within ecological networks.

Stability of a diamond-shaped module with multiple interaction types - Alix M. C. Sauve; Colin Fontaine; Elisa Thébault (Theoretical Ecology, 2016)

Beyond arctic and alpine: the influence of winter climate on temperate ecosystems - Laura M. Ladwig; Zak R. Ratajczak; Troy W. Ocheltree; Katya A. Hafich; Amber C. Churchill; Sarah J. K. Frey; Colin B. Fuss; Clare E. Kazanski; Juan D. Muñoz; Matthew D. Petrie; Andrew B. Reinmann; Jane G. Smith (Ecology, 2016)
Winter climate is expected to change under future climate scenarios, yet the majority of winter ecology research is focused in cold‐climate ecosystems. In many temperate systems, it is unclear how winter climate relates to biotic responses during the growing season. The objective of this study was to examine how winter weather relates to plant and animal communities in a variety of terrestrial ecosystems ranging from warm deserts to alpine tundra. Specifically, we examined the association between winter weather and plant phenology, plant species richness, consumer abundance, and consumer richness in 11 terrestrial ecosystems associated with the U.S. Long‐Term Ecological Research ( LTER ) Network. To varying degrees, winter precipitation and temperature were correlated with all biotic response variables. Bud break was tightly aligned with end of winter temperatures. For half the sites, winter weather was a better predictor of plant species richness than growing season weather. Warmer winters were correlated with lower consumer abundances in both temperate and alpine systems. Our findings suggest winter weather may have a strong influence on biotic activity during the growing season and should be considered in future studies investigating the effects of climate change on both alpine and temperate systems.

Home range size of adult Indo‐Pacific bottlenose dolphins ( Tursiops aduncus ) in a coastal and estuarine system is habitat and sex‐specific - Kate R. Sprogis; Holly C. Raudino; Robert Rankin; Colin D. MacLeod; Lars Bejder (Marine Mammal Science, 2016)
This study examined sex‐specific differences in home range size of adult Indo‐Pacific bottlenose dolphins off Bunbury, Western Australia. We applied a new kernel density estimation approach that accounted for physical barriers to movements. A Bayesian mixture model was developed to estimate a sex effect in home range size with latent group partitioning constrained by association data. A post hoc analysis investigated group partitioning relating to the proportion of time spent in open vs . sheltered waters. From 2007 to 2013, photographic‐identification data were collected along boat‐based systematic transect lines ( n = 586). Analyses focused on adult dolphins of known sex (sighted ≥ 30 times; n = 22 males and 34 females). The 95% utilization distributions of males varied between 27 and 187 km 2 ( ; 94.8 ± 48.15) and for females between 20 and 133 km 2 (65.6 ± 30.9). The mixture model indicated a 99% probability that males had larger home ranges than females. Dolphins mostly sighted in open waters had larger home ranges than those in sheltered waters. Home ranges of dolphins sighted in sheltered waters overlapped with areas of highest human activity. We suggest that sex differences in home ranges are driven by male mating strategies, and home range size differences between habitats may be influenced by prey availability and predation risk.

Eruptive and environmental processes recorded by diatoms in volcanically dispersed lake sediments from the Taupo Volcanic Zone, New Zealand - Margaret A. Harper; Shirley A. Pledger; Euan G. C. Smith; Alexa R. Van Eaton; Colin J. N. Wilson (Journal of Paleolimnology, 2015)

Development and applications of a DNA labeling method with magnetic nanoparticles to study the role of horizontal gene transfer events between bacteria in soil pollutant bioremediation processes - J. Pivetal; M. Frénéa-Robin; N. Haddour; C. Vézy; L. F. Zanini; G. Ciuta; N. M. Dempsey; F. Dumas-Bouchiat; G. Reyne; S. Bégin-Colin; D. Felder-Flesh; C. Ghobril; et al. (Environmental Science and Pollution Research, 2015)

Rainfall Variability in the Shoalhaven River Catchment and its Relation to Climatic Indices - Rafael C. Carvalho; Colin D. Woodroffe (Water Resources Management, 2015)

Photosynthetic innovation broadens the niche within a single species - Marjorie R. Lundgren; Guillaume Besnard; Brad S. Ripley; Caroline E. R. Lehmann; David S. Chatelet; Ralf G. Kynast; Mary Namaganda; Maria S. Vorontsova; Russell C. Hall; John Elia; Colin P. Osborne; Pascal‐Antoine Christin (Ecology Letters, 2015)
Adaptation to changing environments often requires novel traits, but how such traits directly affect the ecological niche remains poorly understood. Multiple plant lineages have evolved C 4 photosynthesis, a combination of anatomical and biochemical novelties predicted to increase productivity in warm and arid conditions. Here, we infer the dispersal history across geographical and environmental space in the only known species with both C 4 and non‐C 4 genotypes, the grass Alloteropsis semialata . While non‐C 4 individuals remained confined to a limited geographic area and restricted ecological conditions, C 4 individuals dispersed across three continents and into an expanded range of environments, encompassing the ancestral one. This first intraspecific investigation of C 4 evolutionary ecology shows that, in otherwise similar plants, C 4 photosynthesis does not shift the ecological niche, but broadens it, allowing dispersal into diverse conditions and over long distances. Over macroevolutionary timescales, this immediate effect can be blurred by subsequent specialisation towards more extreme niches.

Regulation of plasmid‐encoded isoprene metabolism in R hodococcus , a representative of an important link in the global isoprene cycle - Andrew T. Crombie; Myriam El Khawand; Virgil A. Rhodius; Kevin A. Fengler; Michael C. Miller; Gregg M. Whited; Terry J. McGenity; J. Colin Murrell (Environmental Microbiology, 2015)
Summary Emissions of biogenic volatile organic compounds ( VOCs ) form an important part of the global carbon cycle, comprising a significant proportion of net ecosystem productivity. They impact atmospheric chemistry and contribute directly and indirectly to greenhouse gases. Isoprene, emitted largely from plants, comprises one third of total VOCs , yet in contrast to methane, which is released in similar quantities, we know little of its biodegradation. Here, we report the genome of an isoprene degrading isolate, R hodococcus sp. AD 45, and, using mutagenesis shows that a plasmid‐encoded soluble di‐iron centre isoprene monooxygenase ( IsoMO ) is essential for isoprene metabolism. Using RNA sequencing ( RNAseq ) to analyse cells exposed to isoprene or epoxyisoprene in a substrate‐switch time‐course experiment, we show that transcripts from 22 contiguous genes, including those encoding IsoMO , were highly upregulated, becoming among the most abundant in the cell and comprising over 25% of the entire transcriptome. Analysis of gene transcription in the wild type and an IsoMO ‐disrupted mutant strain showed that epoxyisoprene, or a subsequent product of isoprene metabolism, rather than isoprene itself, was the inducing molecule. We provide a foundation of molecular data for future research on the environmental biological consumption of this important, climate‐active compound.

Fine-scale temporal recovery, reconstruction and evolution of a post-supereruption magmatic system - Simon J. Barker; Colin J. N. Wilson; Aidan S. R. Allan; C. Ian Schipper (Contributions to Mineralogy and Petrology, 2015)

Proceedings of the second international molecular pathological epidemiology (MPE) meeting - Shuji Ogino; Peter T. Campbell; Reiko Nishihara; Amanda I. Phipps; Andrew H. Beck; Mark E. Sherman; Andrew T. Chan; Melissa A. Troester; Adam J. Bass; Kathryn C. Fitzgerald; Rafael A. Irizarry; Karl T. Kelsey; et al. (Cancer Causes & Control, 2015)

Inferring social structure from temporal data - Ioannis Psorakis; Bernhard Voelkl; Colin J. Garroway; Reinder Radersma; Lucy M. Aplin; Ross A. Crates; Antica Culina; Damien R. Farine; Josh A. Firth; Camilla A. Hinde; Lindall R. Kidd; Nicole D. Milligan; et al. (Behavioral Ecology and Sociobiology, 2015)

Conserved transcriptional responses to cyanobacterial stressors are mediated by alternate regulation of paralogous genes in Daphnia - Jana Asselman; Michael E. Pfrender; Jacqueline A. Lopez; Dieter I. M. De Coninck; Colin R. Janssen; Joseph R. Shaw; Karel A. C. De Schamphelaere (Molecular Ecology, 2015)
Despite a significant increase in genomic data, our knowledge of gene functions and their transcriptional responses to environmental stimuli remains limited. Here, we use the model keystone species Daphnia pulex to study environmental responses of genes in the context of their gene family history to better understand the relationship between genome structure and gene function in response to environmental stimuli. Daphnia were exposed to five different treatments, each consisting of a diet supplemented with one of five cyanobacterial species, and a control treatment consisting of a diet of only green algae. Differential gene expression profiles of Daphnia exposed to each of these five cyanobacterial species showed that genes with known functions are more likely to be shared by different expression profiles, whereas genes specific to the lineage of Daphnia are more likely to be unique to a given expression profile. Furthermore, while only a small number of nonlineage‐specific genes were conserved across treatment type, there was a high degree of overlap in expression profiles at the functional level. The conservation of functional responses across the different cyanobacterial treatments can be attributed to the treatment‐specific expression of different paralogous genes within the same gene family. Comparison with available gene expression data in the literature suggests differences in nutritional composition in diets with cyanobacterial species compared to diets of green algae as a primary driver for cyanobacterial effects on Daphnia . We conclude that conserved functional responses in Daphnia across different cyanobacterial treatments are mediated through alternate regulation of paralogous gene families.

Enrichment of U–Se–Mo–Re–V in coals preserved within marine carbonate successions: geochemical and mineralogical data from the Late Permian Guiding Coalfield, Guizhou, China - Shifeng Dai; Vladimir V. Seredin; Colin R. Ward; James C. Hower; Yunwei Xing; Weiguo Zhang; Weijiao Song; Peipei Wang (Mineralium Deposita, 2015)

Mapping and quantification of planted tree and shrub shelterbelts in Saskatchewan, Canada - Beyhan Y. Amichev; Murray J. Bentham; Darrel Cerkowniak; John Kort; Suren Kulshreshtha; Colin P. Laroque; Joseph M. Piwowar; Ken C. J. Van Rees (Agroforestry Systems, 2015)

Connectivity of wood thrush breeding, wintering, and migration sites based on range‐wide tracking - Calandra Q. Stanley; Emily A. McKinnon; Kevin C. Fraser; Maggie P. Macpherson; Garth Casbourn; Lyle Friesen; Peter P. Marra; Colin Studds; T. Brandt Ryder; Nora E. Diggs; Bridget J. M. Stutchbury (Conservation Biology, 2015)
Many migratory animals are experiencing rapid population declines, but migration data with the geographic scope and resolution to quantify the complex network of movements between breeding and nonbreeding regions are often lacking. Determining the most frequently used migration routes and nonbreeding regions for a species is critical for understanding population dynamics and making effective conservation decisions. We tracked the migration of individual Wood Thrushes (Hylocichla mustelina) (n = 102) from across their range with light‐level geolocators and, for the first time, quantified migration routes and wintering regions for distinct breeding populations. We identified regional and species‐level migratory connectivity networks for this declining songbird by combining our tracking results with range‐wide breeding abundance estimates and forest cover data. More than 50% of the species occupied the eastern wintering range (Honduras to Costa Rica), a region that includes only one‐third of all wintering habitat and that is undergoing intensive deforestation. We estimated that half of all Wood Thrushes in North America migrate south through Florida in fall, whereas in spring approximately 73% funnel northward through a narrow span along the central U.S. Gulf Coast (88–93°W). Identifying migratory networks is a critical step for conservation of songbirds and we demonstrated with Wood Thrushes how it can highlight conservation hotspots for regional populations and species as a whole. Conectividad de Sitios de Reproducción, Invierno y Migración del Zorzal con Base en Rastreo de Cobertura Amplia

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Bubble development in explosive silicic eruptions: insights from pyroclast vesicularity textures from Raoul volcano (Kermadec arc) - Melissa D. Rotella; Colin J. N. Wilson; Simon J. Barker; Katharine V. Cashman; Bruce F. Houghton; Ian C. Wright (Bulletin of Volcanology, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

A Rifapentine-Containing Inhaled Triple Antibiotic Formulation for Rapid Treatment of Tubercular Infection - John Gar Yan Chan; Anneliese S. Tyne; Angel Pang; Hak-Kim Chan; Paul M. Young; Warwick J. Britton; Colin C. Duke; Daniela Traini (Pharmaceutical Research, 2014)

Case–control association study of polymorphisms in the voltage-gated sodium channel genes SCN1A, SCN2A, SCN3A, SCN1B, and SCN2B and epilepsy - Larry Baum; Batoul Sadat Haerian; Ho-Keung Ng; Virginia C. N. Wong; Ping Wing Ng; Colin H. T. Lui; Ngai Chuen Sin; Chunbo Zhang; Brian Tomlinson; Gary Wing-Kin Wong; Hui Jan Tan; Azman Ali Raymond; et al. (Human Genetics, 2014)

Soil microbial and nutrient responses to 7 years of seasonally altered precipitation in a Chihuahuan Desert grassland - Colin W. Bell; David T. Tissue; Michael E. Loik; Matthew D. Wallenstein; Veronica Acosta ‐ Martinez; Richard A. Erickson; John C. Zak (Global Change Biology, 2014)
Soil microbial communities in Chihuahuan Desert grasslands generally experience highly variable spatiotemporal rainfall patterns. Changes in precipitation regimes can affect belowground ecosystem processes such as decomposition and nutrient cycling by altering soil microbial community structure and function. The objective of this study was to determine if increased seasonal precipitation frequency and magnitude over a 7‐year period would generate a persistent shift in microbial community characteristics and soil nutrient availability. We supplemented natural rainfall with large events (one/winter and three/summer) to simulate increased precipitation based on climate model predictions for this region. We observed a 2‐year delay in microbial responses to supplemental precipitation treatments. In years 3–5, higher microbial biomass, arbuscular mycorrhizae abundance, and soil enzyme C and P acquisition activities were observed in the supplemental water plots even during extended drought periods. In years 5–7, available soil P was consistently lower in the watered plots compared to control plots. Shifts in soil P corresponded to higher fungal abundances, microbial C utilization activity, and soil pH . This study demonstrated that 25% shifts in seasonal rainfall can significantly influence soil microbial and nutrient properties, which in turn may have long‐term effects on nutrient cycling and plant P uptake in this desert grassland.

Behavioral and neurophysiological study of attentional and inhibitory processes in ADHD-combined and control children - S. Baijot; N. Deconinck; H. Slama; I. Massat; C. Colin (Acta Neurologica Belgica, 2013)

Methanobactin and MmoD work in concert to act as the ‘copper‐switch’ in methanotrophs - Jeremy D. Semrau; Sheeja Jagadevan; Alan A. DiSpirito; Ashraf Khalifa; Julie Scanlan; Brandt H. Bergman; Brittani C. Freemeier; Bipin S. Baral; Nathan L. Bandow; Alexey Vorobev; Daniel H. Haft; Stéphane Vuilleumier; et al. (Environmental Microbiology, 2013)
Summary Biological oxidation of methane to methanol by aerobic bacteria is catalysed by two different enzymes, the cytoplasmic or soluble methane monooxygenase ( sMMO ) and the membrane‐bound or particulate methane monooxygenase ( pMMO ). Expression of MMOs is controlled by a ‘copper‐switch’, i.e. sMMO is only expressed at very low copper : biomass ratios, while pMMO expression increases as this ratio increases. Methanotrophs synthesize a chalkophore, methanobactin, for the binding and import of copper. Previous work suggested that methanobactin was formed from a polypeptide precursor. Here we report that deletion of the gene suspected to encode for this precursor, mbnA , in M ethylosinus trichosporium OB3 b, abolishes methanobactin production. Further, gene expression assays indicate that methanobactin, together with another polypeptide of previously unknown function, MmoD , play key roles in regulating expression of MMOs . Based on these data, we propose a general model explaining how expression of the MMO operons is regulated by copper, methanobactin and MmoD . The basis of the ‘copper‐switch’ is MmoD , and methanobactin amplifies the magnitude of the switch. Bioinformatic analysis of bacterial genomes indicates that the production of methanobactin‐like compounds is not confined to methanotrophs, suggesting that its use as a metal‐binding agent and/or role in gene regulation may be widespread in nature.

Novel statistical methods for integrating genetic and stable isotope data to infer individual‐level migratory connectivity - Colin W. Rundel; Michael B. Wunder; Allison H. Alvarado; Kristen C. Ruegg; Ryan Harrigan; Andrew Schuh; Jeffrey F. Kelly; Rodney B. Siegel; David F. DeSante; Thomas B. Smith; John Novembre (Molecular Ecology, 2013)
Methods for determining patterns of migratory connectivity in animal ecology have historically been limited due to logistical challenges. Recent progress in studying migratory bird connectivity has been made using genetic and stable‐isotope markers to assign migratory individuals to their breeding grounds. Here, we present a novel B ayesian approach to jointly leverage genetic and isotopic markers and we test its utility on two migratory passerine bird species. Our approach represents a principled model‐based combination of genetic and isotope data from samples collected on the breeding grounds and is able to achieve levels of assignment accuracy that exceed those of either method alone. When applied at large scale the method can reveal specific migratory connectivity patterns. In W ilson's warblers ( W ilsonia pusilla ), we detect a subgroup of birds wintering in B aja that uniquely migrate preferentially from the coastal P acific N orthwest. Our approach is implemented in a way that is easily extended to accommodate additional sources of information (e.g. bi‐allelic markers, species distribution models, etc.) or adapted to other species or assignment problems.

Urban behavioural adaptation - Colin J. Garroway; Ben C. Sheldon (Molecular Ecology, 2013)
A large and growing proportion of the world is impacted directly by human activities; among the most extreme of these is the spread of urban environments. Environmental change associated with urbanization represents a potentially potent source of selection. While urban environments generally have lowered biodiversity, some clades seem to thrive in urban settings. For example, many members of the bird family Turdidae, known as the ‘true thrushes’ and the blackbird Turdus merula (Fig. 1) in particular, are familiar urban species. Indeed, the colonization of urban environments by blackbirds has become a textbook case study for our understanding of the many ways a wild species can deal with urbanization. In this issue, Mueller et al . ( Molecular Ecology , 00, 2013, 00) add to that story by beginning to address the genetic nature of behavioural adaptation of blackbirds colonizing urban areas. They do this by testing for divergence between paired urban and rural samples at a suite of candidate genes with hypothesized effects on behaviours thought to be important for the colonization of urban environments. They find evidence for consistent patterns of divergence at an exonic microsatellite associated with the SERT gene. SERT has a number of hypothesized behavioural effects, including harm avoidance, which may be associated with tolerating the hustle and bustle of urban environments. This is among the first evidence that behavioural differences between urban and rural environments have a genetic basis and this work suggests that urban environments can in some cases exert homogeneous selection pressures.

Forest water use and water use efficiency at elevated CO 2 : a model‐data intercomparison at two contrasting temperate forest FACE sites - Martin G. De Kauwe; Belinda E. Medlyn; Sönke Zaehle; Anthony P. Walker; Michael C. Dietze; Thomas Hickler; Atul K. Jain; Yiqi Luo; William J. Parton; I. Colin Prentice; Benjamin Smith; Peter E. Thornton; et al. (Global Change Biology, 2013)
Predicted responses of transpiration to elevated atmospheric CO 2 concentration ( eCO 2 ) are highly variable amongst process‐based models. To better understand and constrain this variability amongst models, we conducted an intercomparison of 11 ecosystem models applied to data from two forest free‐air CO 2 enrichment ( FACE ) experiments at Duke University and Oak Ridge National Laboratory. We analysed model structures to identify the key underlying assumptions causing differences in model predictions of transpiration and canopy water use efficiency. We then compared the models against data to identify model assumptions that are incorrect or are large sources of uncertainty. We found that model‐to‐model and model‐to‐observations differences resulted from four key sets of assumptions, namely (i) the nature of the stomatal response to elevated CO 2 (coupling between photosynthesis and stomata was supported by the data); (ii) the roles of the leaf and atmospheric boundary layer (models which assumed multiple conductance terms in series predicted more decoupled fluxes than observed at the broadleaf site); (iii) the treatment of canopy interception (large intermodel variability, 2–15%); and (iv) the impact of soil moisture stress (process uncertainty in how models limit carbon and water fluxes during moisture stress). Overall, model predictions of the CO 2 effect on WUE were reasonable (intermodel μ = approximately 28% ± 10%) compared to the observations (μ = approximately 30% ± 13%) at the well‐coupled coniferous site (Duke), but poor (intermodel μ = approximately 24% ± 6%; observations μ = approximately 38% ± 7%) at the broadleaf site (Oak Ridge). The study yields a framework for analysing and interpreting model predictions of transpiration responses to eCO 2 , and highlights key improvements to these types of models.

Effects of risperidone, amisulpride and nicotine on eye movement control and their modulation by schizotypy - Anne Schmechtig; Jane Lees; Lois Grayson; Kevin J. Craig; Rukiya Dadhiwala; Gerard R. Dawson; J. F. William Deakin; Colin T. Dourish; Ivan Koychev; Katrina McMullen; Ellen M. Migo; Charlotte Perry; et al. (Psychopharmacology, 2013)

Florivores prefer white versus pink petal color morphs in wild radish, Raphanus sativus - Andrew C. McCall; Stephen J. Murphy; Colin Venner; Monique Brown (Oecologia, 2013)

Ubiquitin–Proteasome System Impairment and MPTP-Induced Oxidative Stress in the Brain of C57BL/6 Wild-type and GSTP Knockout Mice - Andreia Neves Carvalho; Carla Marques; Elsa Rodrigues; Colin J. Henderson; C. Roland Wolf; Paulo Pereira; Maria João Gama (Molecular Neurobiology, 2013)

Bayesian modelling the retreat of the Irish Sea Ice Stream - Richard C. Chiverrell; Ian M. Thrasher; Geoffrey S. P. Thomas; Andreas Lang; James D. Scourse; Katrien J. J. van Landeghem; Danny Mccarroll; Chris D. Clark; Colm Ó Cofaigh; David J. A. Evans; Colin K. Ballantyne (Journal of Quaternary Science, 2013)
We present an 8000‐year history spanning 650 km of ice margin retreat for the largest marine‐terminating ice stream draining the former British–Irish Ice Sheet. Bayesian modelling of the geochronological data shows the ISIS expanded 34.0–25.3 ka, accelerating into the Celtic Sea to reach maximum limits 25.3–24.5 ka before a collapse with rapid marginal retreat to the northern Irish Sea Basin (ISB). This retreat was rapid and driven by climatic warming, sea‐level rise, mega‐tidal amplitudes and reactivation of meridional circulation in the North Atlantic. The retreat, though rapid, is uneven, with the stepped retreat pattern possibly a function of the passage of the ice stream between normal and adverse ice bed gradients and changing ice stream geometry. Initially, wide calving margins and adverse slopes encouraged rapid retreat (∼550 m a −1 ) that slowed (∼100 m a −1 ) at the topographic constriction and bathymetric high between southern Ireland and Wales before rates increased (∼200 m a −1 ) across adverse bed slopes and wider and deeper basin configuration in the northern ISB. These data point to the importance of the ice bed slope and lateral extent in predicting the longer‐term (>1000 a) patterns and rates of ice‐marginal retreat during phases of rapid collapse, which has implications for the modelling of projected rapid retreat of present‐day ice streams. Copyright © 2013 John Wiley & Sons, Ltd.

Local climatic drivers of changes in phenology at a boreal-temperate ecotone in eastern North America - Colin M. Beier; John C. Stella; Martin Dovčiak; Stacy A. McNulty (Climatic Change, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Centralized mouse repositories - Leah Rae Donahue; Martin Hrabe de Angelis; Michael Hagn; Craig Franklin; K. C. Kent Lloyd; Terry Magnuson; Colin McKerlie; Naomi Nakagata; Yuichi Obata; Stuart Read; Wolfgang Wurst; Andreas Hörlein; et al. (Mammalian Genome, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Contrasting pyroclast density spectra from subaerial and submarine silicic eruptions in the Kermadec arc: implications for eruption processes and dredge sampling - Simon J. Barker; Melissa D. Rotella; Colin J. N. Wilson; Ian C. Wright; Richard J. Wysoczanski (Bulletin of Volcanology, 2012)

Glutathione S-Transferase pi Mediates MPTP-Induced c-Jun N-Terminal Kinase Activation in the Nigrostriatal Pathway - Margarida Castro-Caldas; Andreia Neves Carvalho; Elsa Rodrigues; Colin Henderson; C. Roland Wolf; Maria João Gama (Molecular Neurobiology, 2012)

A comparison of the short-term toxicity of cadmium to indigenous and alien gammarid species - Pieter Boets; Koen Lock; Peter L. M. Goethals; Colin R. Janssen; Karel A. C. De Schamphelaere (Ecotoxicology, 2012)

A radical approach to beating hypoxia: depressed free radical release from heart fibres of the hypoxia-tolerant epaulette shark (Hemiscyllum ocellatum) - Anthony J. R. Hickey; Gillian M. C. Renshaw; Ben Speers-Roesch; Jeffrey G. Richards; Yuxiang Wang; Anthony P. Farrell; Colin J. Brauner (Journal of Comparative Physiology B, 2012)

Plant dispersal in the sub‐Antarctic inferred from anisotropic genetic structure - CÉLINE BORN; PETER C. Le ROUX; COLIN SPOHR; MELODIE A. McGEOCH; BETTINE JANSEN Van VUUREN (Molecular Ecology, 2012)
Climatic conditions and landscape features often strongly affect species’ local distribution patterns, dispersal, reproduction and survival and may therefore have considerable impacts on species’ fine‐scale spatial genetic structure (SGS). In this study, we demonstrate the efficacy of combining fine‐scale SGS analyses with isotropic and anisotropic spatial autocorrelation techniques to infer the impact of wind patterns on plant dispersal processes. We genotyped 1304 Azorella selago (Apiaceae) specimens, a wind‐pollinated and wind‐dispersed plant, from four populations distributed across sub‐Antarctic Marion Island. SGS was variable with Sp values ranging from 0.001 to 0.014, suggesting notable variability in dispersal distance and wind velocities between sites. Nonetheless, the data supported previous hypotheses of a strong NW–SE gradient in wind strength across the island. Anisotropic autocorrelation analyses further suggested that dispersal is strongly directional, but varying between sites depending on the local prevailing winds. Despite the high frequency of gale‐force winds on Marion Island, gene dispersal distance estimates ( σ ) were surprisingly low (

Characterisation and sediment–source linkages of intertidal sediment of the UK’s north Sefton Coast using magnetic and textural properties: findings and limitations - Vanessa J. C. Holden; Annie T. Worsley; Colin A. Booth; Graham Lymbery (Ocean Dynamics, 2011)

Estimation of Mussel Population Response to Hydrologic Alteration in a Southeastern U.S. Stream - James T. Peterson; Jason M. Wisniewski; Colin P. Shea; C. Rhett Jackson (Environmental Management, 2011)

Cytochrome b 5 null mouse: a new model for studying inherited skin disorders and the role of unsaturated fatty acids in normal homeostasis - Robert D. Finn; Lesley A. McLaughlin; Catherine Hughes; Chengli Song; Colin J. Henderson; C. Roland Wolf (Transgenic Research, 2011)

MC1R genotype may modify the effect of sun exposure on melanoma risk in the GEM study - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Peter Kanetsky; Richard P. Gallagher; Colin B. Begg; Robert C. Millikan; Terence Dwyer; Stefano Rosso; Loraine D. Marrett; Nancy E. Thomas; Marianne Berwick (Cancer Causes & Control, 2010)

The structure of dopamine induced α-synuclein oligomers - Agata Rekas; Robert B. Knott; Anna Sokolova; Kevin J. Barnham; Keyla A. Perez; Colin L. Masters; Simon C. Drew; Roberto Cappai; Cyril C. Curtain; Chi L. L. Pham (European Biophysics Journal, 2010)

Changes in the distribution of native fishes in response to introduced species and other anthropogenic effects - Evelyn Habit; Priscila Piedra; Daniel E. Ruzzante; Sandra J. Walde; Mark C. Belk; Víctor E. Cussac; Jorge Gonzalez; Nicole Colin (Global Ecology and Biogeography, 2010)
Aim Globally, one of the major threats to the integrity of native faunas is the loss of biodiversity that can result from the introduction of exotics. Here we document recent changes in the distribution of five common fish species that are linked to introductions in Chile. Location Chile from 28° S to 54° S. Methods We assess the extent of changes in distribution of galaxiid species by comparing their historical and current distributions based on the results of the most extensive survey of freshwater fishes in Chile to date, a range that encompasses the full latitudinal and elevational range of the Galaxiidae in Chile. We test for relationships of the distributions and abundances of native fishes with the incidence of introduced species. Results The latitudinal range of Galaxias maculatus has declined by 26%, and most of this reduction has occurred in the northern part of its range. Aplochiton taeniatus and Brachygalaxias bullocki have experienced reductions (8–17% loss) in total drainage area occupied, and they have disappeared from, or are now extremely difficult to find, in latitudes 36° to 41° S, coincidently with areas of urban growth and intense economic activities. The distribution of Galaxias platei has, instead, increased considerably. In northern basins, G. maculatus has apparently been replaced by an introduced poeciliid Gambusia sp. High‐elevation systems remain dominated by native Galaxias platei , whereas systems at intermediate elevations, especially rivers, are now dominated by introduced salmonids. Within drainages, native galaxiids remain abundant where exotic salmonid abundance is low. Main conclusions We suggest that negative interactions between introduced and native fish are responsible for some of the range reductions among Galaxiidae in Chile. The severity of the impacts varies with latitude and altitude and is probably related to temperature. The effects of Gambusia are restricted to warmer systems. Native fish also appear to have found temperature refugia from salmonids; impacts are low in the warmer northern and coastal systems, as well as in high‐altitude relatively cold systems. Native fish also appear less vulnerable to salmonids in lakes than in rivers. This study identifies watersheds critical for the conservation of biodiversity within the Galaxiidae.

Urban realities: the contribution of residential gardens to the conservation of urban forest remnants - Brendan J. Doody; Jon J. Sullivan; Colin D. Meurk; Glenn H. Stewart; Harvey C. Perkins (Biodiversity and Conservation, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Determination of the compositional change (1999–2006) in the pine forests of British Columbia due to mountain pine beetle infestation - Colin Robertson; Carson J. Q. Farmer; Trisalyn A. Nelson; Ian K. Mackenzie; Michael A. Wulder; Joanne C. White (Environmental Monitoring and Assessment, 2009)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

The influence of deprivation and ethnicity on the incidence of esophageal cancer in England - Sheldon C. Cooper; Rosie Day; Colin Brooks; Cheryl Livings; Catherine S. Thomson; Nigel J. Trudgill (Cancer Causes & Control, 2009)

Characterisation and expression of SPLUNC2, the human orthologue of rodent parotid secretory protein - Lynne Bingle; Frances A. Barnes; Hayley Lunn; Maslinda Musa; Steve Webster; C. W. Ian Douglas; Simon S. Cross; Alec S. High; Colin D. Bingle (Histochemistry and Cell Biology, 2009)

Amyloid Imaging in Alzheimer’s Disease and Other Dementias - Michelle T. Fodero-Tavoletti; Roberto Cappai; Catriona A. McLean; Kerryn E. Pike; Paul A. Adlard; Tiffany Cowie; Andrea R. Connor; Colin L. Masters; Christopher C. Rowe; Victor L. Villemagne (Brain Imaging and Behavior, 2009)

Siderocalins: siderophore-binding proteins of the innate immune system - Matthew C. Clifton; Colin Corrent; Roland K. Strong (BioMetals, 2009)

Isolation and Analysis of Bacteria with Antimicrobial Activities from the Marine Sponge Haliclona simulans Collected from Irish Waters - Jonathan Kennedy; Paul Baker; Clare Piper; Paul D. Cotter; Marcella Walsh; Marlies J. Mooij; Marie B. Bourke; Mary C. Rea; Paula M. O’Connor; R. Paul Ross; Colin Hill; Fergal O’Gara; et al. (Marine Biotechnology, 2009)

Mechanistic insight into the initiation step of the reaction of Burkholderia pseudomallei catalase-peroxidase with peroxyacetic acid - Ben Wiseman; Julie Colin; Andrew T. Smith; Anabella Ivancich; Peter C. Loewen (JBIC Journal of Biological Inorganic Chemistry, 2009)

Effects of salinity and nutrients on microbial assemblages in Louisiana wetland sediments - Colin R. Jackson; Scarlett C. Vallaire (Wetlands, 2009)

The Influence of Membrane Lipids in Staphylococcus aureus Gamma-Hemolysins Pore Formation - C. Potrich; H. Bastiani; D. A. Colin; S. Huck; G. Prévost; M. Dalla Serra (The Journal of Membrane Biology, 2009)

A review of cephalopod–environment interactions in European Seas - Graham J. Pierce; Vasilis D. Valavanis; Angel Guerra; Patricia Jereb; Lydia Orsi-Relini; Jose M. Bellido; Isidora Katara; Uwe Piatkowski; João Pereira; Eduardo Balguerias; Ignacio Sobrino; Eugenia Lefkaditou; et al. (Hydrobiologia, 2008)

A Global Baseline for Spawning Aggregations of Reef Fishes - YVONNE SADOVY DE MITCHESON; ANDREW CORNISH; MICHAEL DOMEIER; PATRICK L. COLIN; MARTIN RUSSELL; KENYON C. LINDEMAN (Conservation Biology, 2008)
Species that periodically and predictably congregate on land or in the sea can be extremely vulnerable to overexploitation. Many coral reef fishes form spawning aggregations that are increasingly the target of fishing. Although serious declines are well known for a few species, the extent of this behavior among fishes and the impacts of aggregation fishing are not appreciated widely. To profile aggregating species globally, establish a baseline for future work, and strengthen the case for protection, we (as members of the Society for the Conservation of Reef Fish Aggregations) developed a global database on the occurrence, history, and management of spawning aggregations. We complemented the database with information from interviews with over 300 fishers in Asia and the western Pacific. Sixty‐seven species, mainly commercial, in 9 families aggregate to spawn in the 29 countries or territories considered in the database. Ninety percent of aggregation records were from reef pass channels, promontories, and outer reef‐slope drop‐offs. Multispecies aggregation sites were common, and spawning seasons of most species typically lasted Epinephelus striatus ), has undergone substantial declines in aggregations throughout its range and is now considered threatened. Our findings have important conservation and management implications for aggregating species given that exploitation pressures on them are increasing, there is little effective management, and 79% of those aggregations sufficiently well documented were reported to be in decline. Nonetheless, a few success stories demonstrate the benefits of aggregation management. A major shift in perspective on spawning aggregations of reef fish, from being seen as opportunities for exploitation to acknowledging them as important life‐history phenomena in need of management, is urgently needed.

Does the preferential microbial colonisation of ferromagnesian minerals affect mineral weathering in soil? - Michael J. Wilson; Giacomo Certini; Colin D. Campbell; Ian C. Anderson; Stephen Hillier (The Science of Nature, 2008)

The Cry48Aa‐Cry49Aa binary toxin from Bacillus sphaericus exhibits highly restricted target specificity - Gareth W. Jones; Margaret C. Wirth; Rose G. Monnerat; Colin Berry (Environmental Microbiology, 2008)
Summary The Cry48Aa/Cry49Aa binary toxin of Bacillus sphaericus was recently discovered by its ability to kill Culex quinquefasciatus mosquito larvae through a novel interaction between its two components. We have investigated the target specificity of this toxin and show it to be non‐toxic to coleopteran, lepidopteran and other dipteran insects, including closely related Aedes and Anopheles mosquitoes. This represents an unusually restricted target range for crystal toxins from either B. sphaericus or Bacillus thuringiensis. Gut extracts from Culex and Aedes larvae show differential processing of the Cry48Aa protein, with the location of cleavage sites in Culex reflecting those previously shown for the activation of Cry4 toxins in mosquitoes. Pre‐activation of Cry48Aa/Cry49Aa with Culex extracts, however, fails to induce toxicity to Aedes larvae. Co‐administration of Cry49Aa with Cry4Aa gives higher than predicted toxicity, perhaps suggesting weak synergism against Culex larvae between Cry49Aa and other three‐domain Cry toxins.

The ART of Loss: Aβ Imaging in the Evaluation of Alzheimer’s Disease and other Dementias - Victor L. Villemagne; Michelle T. Fodero-Tavoletti; Kerryn E. Pike; Roberto Cappai; Colin L. Masters; Christopher C. Rowe (Molecular Neurobiology, 2008)

NADPH oxidase involvement in cellular integrity - Neil Macpherson; Seiji Takeda; Zhonglin Shang; Adeeba Dark; Jennifer C. Mortimer; Colin Brownlee; Liam Dolan; Julia M. Davies (Planta, 2008)

Exploring gene-environment interactions in Parkinson’s disease - Colin C. McCulloch; Denise M. Kay; Stewart A. Factor; Ali Samii; John G. Nutt; Donald S. Higgins; Alida Griffith; John W. Roberts; Berta C. Leis; Jennifer S. Montimurro; Cyrus P. Zabetian; Haydeh Payami (Human Genetics, 2008)

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

The enzymatic basis for pesticide bioremediation - Colin Scott; Gunjan Pandey; Carol J. Hartley; Colin J. Jackson; Matthew J. Cheesman; Matthew C. Taylor; Rinku Pandey; Jeevan L. Khurana; Mark Teese; Chris W. Coppin; Kahli M. Weir; Rakesh K. Jain; et al. (Indian Journal of Microbiology, 2008)

Large scale transcriptome analysis of the effects of nitrogen nutrition on accumulation of stem carbohydrate reserves in reproductive stage wheat - Sari A. Ruuska; David C. Lewis; Gavin Kennedy; Robert T. Furbank; Colin L. D. Jenkins; Linda M. Tabe (Plant Molecular Biology, 2008)

Bladder cancer angiogenesis and metastasis—translation from murine model to clinical trial - Peter C. Black; Colin P. N. Dinney (Cancer and Metastasis Reviews, 2007)

Respiratory properties of blood in flatback turtles (Natator depressus) - Jannie B. Sperling; Gordon C. Grigg; Lyn A. Beard; Colin J. Limpus (Journal of Comparative Physiology B, 2007)

Projected Changes in Terrestrial Carbon Storage in Europe under Climate and Land-use Change, 1990–2100 - Sönke Zaehle; Alberte Bondeau; Timothy R. Carter; Wolfgang Cramer; Markus Erhard; I. Colin Prentice; I. Reginster; Mark D. A. Rounsevell; Stephen Sitch; Benjamin Smith; Pascalle C. Smith; Martin Sykes (Ecosystems, 2007)

Generation of rat mutants using a coat color-tagged Sleeping Beauty transposon system - Baisong Lu; Aron M. Geurts; Christophe Poirier; Deborah C. Petit; Wilbur Harrison; Paul A. Overbeek; Colin E. Bishop (Mammalian Genome, 2007)

Ambient UV, personal sun exposure and risk of multiple primary melanomas - Anne Kricker; Bruce K. Armstrong; Chris Goumas; Melisa Litchfield; Colin B. Begg; Amanda J. Hummer; Loraine D. Marrett; Beth Theis; Robert C. Millikan; Nancy Thomas; Hoda Anton Culver; Richard P. Gallagher; et al. (Cancer Causes & Control, 2007)

Antennally mediated negative feedback regulation of pheromone production in the pine engraver beetle, Ips pini - Matthew D. Ginzel; Jeremy C. Bearfield; Christopher I. Keeling; Colin C. McCormack; Gary J. Blomquist; Claus Tittiger (The Science of Nature, 2006)

Validated age and growth of the sandbar shark, Carcharhinus plumbeus (Nardo 1827) in the waters off Western Australia - Rory B. McAuley; Colin A. Simpfendorfer; Glenn A. Hyndes; Rick R. Allison; Justin A. Chidlow; Stephen J. Newman; Rod C. J. Lenanton (Environmental Biology of Fishes, 2006)

Species diversity and ecology of Tonle Sap Great Lake, Cambodia - Ian C. Campbell; Colin Poole; Wim Giesen; John Valbo-Jorgensen (Aquatic Sciences, 2006)

Model‐based uncertainty in species range prediction - Richard G. Pearson; Wilfried Thuiller; Miguel B. Araújo; Enrique Martinez‐Meyer; Lluís Brotons; Colin McClean; Lera Miles; Pedro Segurado; Terence P. Dawson; David C. Lees (Journal of Biogeography, 2006)
Aim Many attempts to predict the potential range of species rely on environmental niche (or ‘bioclimate envelope’) modelling, yet the effects of using different niche‐based methodologies require further investigation. Here we investigate the impact that the choice of model can have on predictions, identify key reasons why model output may differ and discuss the implications that model uncertainty has for policy‐guiding applications. Location The Western Cape of South Africa. Methods We applied nine of the most widely used modelling techniques to model potential distributions under current and predicted future climate for four species (including two subspecies) of Proteaceae. Each model was built using an identical set of five input variables and distribution data for 3996 sampled sites. We compare model predictions by testing agreement between observed and simulated distributions for the present day (using the area under the receiver operating characteristic curve (AUC) and kappa statistics) and by assessing consistency in predictions of range size changes under future climate (using cluster analysis). Results Our analyses show significant differences between predictions from different models, with predicted changes in range size by 2030 differing in both magnitude and direction (e.g. from 92% loss to 322% gain). We explain differences with reference to two characteristics of the modelling techniques: data input requirements (presence/absence vs. presence‐only approaches) and assumptions made by each algorithm when extrapolating beyond the range of data used to build the model. The effects of these factors should be carefully considered when using this modelling approach to predict species ranges. Main conclusions We highlight an important source of uncertainty in assessments of the impacts of climate change on biodiversity and emphasize that model predictions should be interpreted in policy‐guiding applications along with a full appreciation of uncertainty.

Downscaling heavy precipitation over the United Kingdom: a comparison of dynamical and statistical methods and their future scenarios - Malcolm R. Haylock; Gavin C. Cawley; Colin Harpham; Rob L. Wilby; Clare M. Goodess (International Journal of Climatology, 2006)
Six statistical and two dynamical downscaling models were compared with regard to their ability to downscale seven seasonal indices of heavy precipitation for two station networks in northwest and southeast England. The skill among the eight downscaling models was high for those indices and seasons that had greater spatial coherence. Generally, winter showed the highest downscaling skill and summer the lowest. The rainfall indices that were indicative of rainfall occurrence were better modelled than those indicative of intensity. Models based on non‐linear artificial neural networks were found to be the best at modelling the inter‐annual variability of the indices; however, their strong negative biases implied a tendency to underestimate extremes. A novel approach used in one of the neural network models to output the rainfall probability and the gamma distribution scale and shape parameters for each day meant that resampling methods could be used to circumvent the underestimation of extremes. Six of the models were applied to the Hadley Centre global circulation model HadAM3P forced by emissions according to two SRES scenarios. This revealed that the inter‐model differences between the future changes in the downscaled precipitation indices were at least as large as the differences between the emission scenarios for a single model. This implies caution when interpreting the output from a single model or a single type of model (e.g. regional climate models) and the advantage of including as many different types of downscaling models, global models and emission scenarios as possible when developing climate‐change projections at the local scale. Copyright © 2006 Royal Meteorological Society

Seashells: Detoxifying Agents for Metal-Contaminated Waters - Helen E. A. Tudor; Carl C. Gryte; Colin C. Harris (Water, Air, & Soil Pollution, 2006)

Geographic patterns of herbivory and resource allocation to defense, growth, and reproduction in an invasive biennial, Alliaria petiolata - Kristin C. Lewis; F.A. Bazzaz; Qing Liao; Colin M. Orians (Oecologia, 2006)

Xaf1 can cooperate with TNFα in the induction of apoptosis, independently of interaction with XIAP - Yan Xia; Rachel Novak; Jennifer Lewis; Colin S. Duckett; Andrew C. Phillips (Molecular and Cellular Biochemistry, 2006)

Evolutionary Basis of Codon Usage and Nucleotide Composition Bias in Vertebrate DNA Viruses - Laura A. Shackelton; Colin R. Parrish; Edward C. Holmes (Journal of Molecular Evolution, 2006)

One step closer to fixing association studies: evidence for age- and gender-specific allele frequency variations and deviations from Hardy-Weinberg expectations in controls - Haydeh Payami; Motao Zhu; Jennifer Montimurro; Robert Keefe; Colin C. McCulloch; Lina Moses (Human Genetics, 2005)

Effects of paroxetine on cardiovascular response to mental stress in subjects with a history of coronary artery disease and no psychiatric diagnoses - Michael Golding; Michael Kotlyar; Stanley W. Carson; Sherri Hoyler; Cindy Lazarus; Colin Davidson; Joseph Guzzo; Eric Sontz; J. C. Garbutt (Psychopharmacology, 2005)

Targeted disruption of mouse Coch provides functional evidence that DFNA9 hearing loss is not a COCH haploinsufficiency disorder - Tomoko Makishima; Clara I. Rodriguez; Nahid G. Robertson; Cynthia C. Morton; Colin L. Stewart; Andrew J. Griffith (Human Genetics, 2005)

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

Chemistry and Pharmacology of Gynostemma pentaphyllum - Valentina Razmovski-Naumovski; Tom Hsun-Wei Huang; Van Hoan Tran; George Qian Li; Colin C. Duke; Basil D. Roufogalis (Phytochemistry Reviews, 2005)

Major gaps in the distribution of protected areas for threatened and narrow range Afrotropical plants - Neil Burgess; Wolfgang KÜper; Jens Mutke; Joanna Brown; Sally Westaway; Susie Turpie; Charles Meshack; James Taplin; Colin McClean; Jon C. Lovett (Biodiversity and Conservation, 2005)

Bacterial diversity in the bacterioneuston (sea surface microlayer): the bacterioneuston through the looking glass - Mark P. Franklin; Ian R. McDonald; David G. Bourne; Nicholas J. P. Owens; Robert C. Upstill‐Goddard; J. Colin Murrell (Environmental Microbiology, 2005)
Summary The bacterioneuston is defined as the community of bacteria present within the neuston or sea surface microlayer. Bacteria within this layer were sampled using a membrane filter technique and bacterial diversity was compared with that in the underlying pelagic coastal seawater using molecular ecological techniques. 16S rRNA gene libraries of ≈ 500 clones were constructed from both bacterioneuston and the pelagic water samples and representative clones from each library were sequenced for comparison of bacterial diversity. The bacterioneuston was found to have a significantly lower bacterial diversity than the pelagic seawater, with only nine clone types (ecotaxa) as opposed to 46 ecotaxa in the pelagic seawater library. Surprisingly, the bacterioneuston clone library was dominated by 16S rRNA gene sequences affiliated to two groups of organisms, Vibrio spp. which accounted for over 68% of clones and Pseudoalteromonas spp. accounting for 21% of the library. The dominance of these two 16S rRNA gene sequence types within the bacterioneuston clone library was confirmed in a subsequent gene probing experiment. 16S rRNA gene probes specific for these groups of bacteria were designed and used to probe new libraries of 1000 clones from both the bacterioneuston and pelagic seawater DNA samples. This revealed that 57% of clones from the bacterioneuston library hybridized to a Vibrio sp.‐specific 16S rRNA gene probe and 32% hybridized to a Pseudoalteromonas sp.‐specific 16S rRNA gene probe. In contrast, the pelagic seawater library resulted in only 13% and 8% of 16S rRNA gene clones hybridizing to the Vibrio sp. and Pseudoalteromonas sp. probes respectively. Results from this study suggest that the bacterioneuston contains a distinct population of bacteria and warrants further detailed study at the molecular level.

Cerebrospinal fluid from human immunodeficiency virus–infected individuals facilitates neurotoxicity by suppressing intracellular calcium recovery - Rick B Meeker; Jeramiah C Boles; Kevin R Robertson; Colin D Hall (Journal of NeuroVirology, 2005)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Familial aggregation of melanoma risks in a large population-based sample of melanoma cases - Colin B. Begg; Amanda Hummer; Urvi Mujumdar; Bruce K. Armstrong; Anne Kricker; Loraine D. Marrett; Robert C. Millikan; Stephen B. Gruber; Hoda Anton-Culver; Judith B. Klotz; Roberto Zanetti; Richard P. Gallagher; et al. (Cancer Causes & Control, 2004)

Biomonitoring of Element Deposition Using Mosses in the 2000 French Survey: Identifying Sources and Spatial Trends - S. Gombert; C. Rausch De Traubenberg; R. Losno; S. Leblond; J. L. Colin; D. Cossa (Journal of Atmospheric Chemistry, 2004)

A Method to Quantify and Analyze the Foraging Activity of Honey Bees: Relevance to the Sublethal Effects Induced by Systemic Insecticides - M. E. Colin; J. M. Bonmatin; I. Moineau; C. Gaimon; S. Brun; J. P. Vermandere (Archives of Environmental Contamination and Toxicology, 2004)

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.

Pre-eruptive magma mixing in ash-flow deposits of the Tertiary Rum Igneous Centre, Scotland - Valentin R. Troll; Colin H. Donaldson; C. Henry. Emeleus (Contributions to Mineralogy and Petrology, 2004)

Identity and diversity of coral endosymbionts (zooxanthellae) from three Palauan reefs with contrasting bleaching, temperature and shading histories - K. E. FABRICIUS; J. C. MIEOG; P. L. COLIN; D. IDIP; M. J. H. VAN OPPEN (Molecular Ecology, 2004)
The potential of corals to associate with more temperature‐tolerant strains of algae (zooxanthellae, Symbiodinium ) can have important implications for the future of coral reefs in an era of global climate change. In this study, the genetic identity and diversity of zooxanthellae was investigated at three reefs with contrasting histories of bleaching mortality, water temperature and shading, in the Republic of Palau (Micronesia). Single‐stranded conformation polymorphism and sequence analysis of the ribosomal DNA internal transcribed spacer (ITS)1 region was used for genotyping. A chronically warm but partly shaded coral reef in a marine lake that is hydrographically well connected to the surrounding waters harboured only two single‐stranded conformation polymorphism profiles (i.e. zooxanthella communities). It consisted only of Symbiodinium D in all 13 nonporitid species and two Porites species investigated, with the remaining five Porites harbouring C•. Despite the high temperature in this lake (> 0.5° above ambient), this reef did not suffer coral mortality during the (1998) bleaching event, however, no bleaching‐sensitive coral families and genera occur in the coral community. This setting contrasts strongly with two other reefs with generally lower temperatures, in which 10 and 12 zooxanthella communities with moderate to low proportions of clade D zooxanthellae were found. The data indicate that whole coral assemblages, when growing in elevated seawater temperatures and at reduced irradiance, can be composed of colonies associated with the more thermo‐tolerant clade D zooxanthellae. Future increases in seawater temperature might, therefore, result in an increasing prevalence of Symbiodinium phylotype D in scleractinian corals, possibly associated with a loss of diversity in both zooxanthellae and corals.

Structure–activity relationships in platinum–acridinylthiourea conjugates: effect of the thiourea nonleaving group on drug stability, nucleobase affinity, and in vitro cytotoxicity - Margaret C. Ackley; Colin G. Barry; Amanda M. Mounce; Michael C. Farmer; Beth-Erin Springer; Cynthia S. Day; Marcus W. Wright; Susan J. Berners-Price; Suzanne M. Hess; Ulrich Bierbach (JBIC Journal of Biological Inorganic Chemistry, 2004)

Methionine oxidation: Implications for the mechanism of toxicity of the β-amyloid peptide from Alzheimer's disease - Giuseppe D. Ciccotosto; Kevin J. Barnham; Robert A. Cherny; Colin L. Masters; Ashley I. Bush; Cyril C. Curtain; Roberto Cappai; Deborah Tew (International Journal of Peptide Research and Therapeutics, 2003)

Diversity of fungi in organic soils under a moorland – Scots pine ( Pinus sylvestris L.) gradient - Ian C. Anderson; Colin D. Campbell; James I. Prosser (Environmental Microbiology, 2003)
Summary The conservation and regeneration of native Scots pine ( Pinus sylvestris L.) woodlands is being actively encouraged by conservation agencies in the UK because of their high biodiversity value. In the present study, the consequences of regeneration on terrestrial fungal communities was determined in three parallel transects running from open moorland, through an intermediate zone showing seedling colonization, into a mature Scots pine forest at Abernethy Forest, Cairngorm, Scotland. Soil cores were taken at 18 m intervals along each 180 m transect, and the diversity of the soil fungal community was investigated by DGGE and sequence analysis of ITS fragments PCR‐amplified from DNA extracted from soil. Analysis of DGGE profiles generated for two of the three transects indicates a clear shift in the community from the moorland region of the transects to the forest region. Whereas a few bands were present at all sampling points across the transects, the majority of bands were unique to either the moorland or forest samples. FASTA database searches of ITS sequence data generated from excised DGGE bands revealed the closest species match for each band. In some cases, the similarity of ITS sequences to database sequences was poor, but the remaining sequences were most closely related to ITS sequences of both mycorrhizal and non‐mycorrhizal fungi. The data are discussed in relation to the effect of native pine woodland expansion on the soil fungal community.

Viability of invertebrate diapausing eggs collected from residual ballast sediment - Sarah A. Bailey; Ian C. Duggan; Colin D. A. van Overdijk; Philip T. Jenkins; Hugh J. MacIsaac (Limnology and Oceanography, 2003)
Natural or anthropogenic movement of sediments may be an important vector for the dispersal of invertebrate resting stages between water bodies. Here we record the presence of invertebrate diapausing eggs in residual sediments from transoceanic vessels and explore whether these may pose an invasion risk. Viability of diapausing eggs was explored under light and dark conditions using sediment collected from eleven tanks on nine vessels operating on the Great Lakes. Seventeen cladoceran, copepod, and rotifer taxa were identified. Four of the species hatched have not yet been reported as established in the Great Lakes. Egg viability for individual species varied from 0% to 92%. Exposure to saline water may impact egg viability of some freshwater species. Generally, the proportion of eggs hatched in light and dark treatments did not differ significantly, indicating that light was not required to terminate diapause. As a result, eggs could potentially hatch in dark ballast tanks when immersed in freshwater loaded as ballast during operation on the Great Lakes. Viability of diapausing eggs differed among ballast tanks on a single vessel, indicating that tanks with independent ballast histories have different invasion risks. While additional work is needed to quantify risk, results from this study indicate that vessels entering the Great Lakes with only residual ballast are a potential vector for the introduction of new nonindigenous species during multiport operations.

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Growth of sulfate-reducing bacteria and methanogenic archaea with methylated sulfur compounds: a commentary on the thermodynamic aspects - Johannes C. M. Scholten; J. Colin Murrell; Donovan P. Kelly (Archives of Microbiology, 2003)

Gene transfer by adenovirus-mimetic peptides in the presence of a cationic lipid and/or adenovirus. Analysis of the contribution of the viral and nonviral components - S. Moritz; M. Colin; M. Keller; B. Klonjkowski; J. Capeau; C. Coutelle; J. Chroboczek; M. C. Brahimi-Horn (Archives of Virology, 2003)

Potential bias of fungal 18S rDNA and internal transcribed spacer polymerase chain reaction primers for estimating fungal biodiversity in soil - Ian C. Anderson; Colin D. Campbell; James I. Prosser (Environmental Microbiology, 2003)
Summary Four fungal 18S rDNA and internal transcribed spacer (ITS) polymerase chain reaction (PCR) primer pairs were tested for their specificity towards target fungal DNA in soil DNA extracts, and their ability to assess the diversity of fungal communities in a natural grassland soil was compared. Amplified PCR products were cloned, and ≈ 50 clones from each library were sequenced. Phylogenetic analysis and database searches indicated that each of the sequenced cloned DNA fragments was of fungal origin for each primer pair, with the exception of the sequences generated using the 18S rDNA primers nu‐SSU‐0817 and nu‐SSU‐1196, where 35 of the 50 sequenced clones represented soil invertebrates. Although some of the primers have previously been suggested to be biased towards certain fungal taxonomic groups, the ratio of sequences representing each of the four main fungal phyla, Ascomycota , Basidiomycota , Chytridiomycota and Zygomycota , was similar for each of the primer pairs, suggesting that primer bias may be less significant than previously thought. Collector's curves were plotted to estimate the coverage obtained for each of the clone libraries after clustering the sequences into operational taxonomic units at a level of 99% sequence similarity. The curves indicated that good coverage of diversity was achieved, with the exception of the clone library constructed using primers nu‐SSU‐0817 and nu‐SSU‐1196, on account of the high number of non‐fungal sequences obtained. The work demonstrates the usefulness of 18S rDNA and ITS PCR primers for assessing fungal diversity in environmental samples, and it also highlights some potential limitations of the approach with respect to PCR primer specificity and bias.

Ds transposition mediated by transient transposase expression in Heiracium aurantiacum - Richard J. Weld; Ross A. Bicknell; Jack A. Heinemann; Colin C. Eady (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

El Niño related coral bleaching in Palau, Western Caroline Islands - J. Bruno; C. Siddon; J. Witman; P. Colin; M. Toscano (Coral Reefs, 2001)

Linkage of prostate cancer susceptibility loci to chromosome 1 - Jianfeng Xu; Siqun L. Zheng; Bao-li Chang; Jeffrey R. Smith; John D. Carpten; O. Colin Stine; Sarah D. Isaacs; Kathy E. Wiley; Lauren Henning; Charles Ewing; Piroska Bujnovszky; Eugene R. Bleeker; et al. (Human Genetics, 2001)

Caldera formation in the Rum Central Igneous Complex, Scotland - Valentin R. Troll; C. Henry Emeleus; Colin H. Donaldson (Bulletin of Volcanology, 2000)

Acute and chronic effects of an aromatase inhibitor on territorial aggression in breeding and nonbreeding male song sparrows - Kiran K. Soma; Kim A. Sullivan; Anthony D. Tramontin; Colin J. Saldanha; Barney A. Schlinger; John C. Wingfield (Journal of Comparative Physiology A, 2000)

Assessment of the metabolic activity of Acremonium chrysogenum using Acridine Orange - Erzsébet Sándor; Levente Karaffa; Gopal C. Paul; István Pócsi; Colin R. Thomas; Attila Szentirmai (Biotechnology Letters, 2000)

Oxygenation and perfusion of rabbit tibialis anterior muscle subjected to different patterns of electrical stimulation - Adam R. Greenbaum; Jonathan C. Jarvis; Daniel O'Hare; Sanjiv Manek; Colin J. Green; John R. Pepper; C. Peter Winlove; Stanley Salmons (Journal of Muscle Research and Cell Motility, 2000)

Simulating Historical Variability in the Amount of Old Forests in the Oregon Coast Range - Michael C. Wimberly; Thomas A. Spies; Colin J. Long; Cathy Whitlock (Conservation Biology, 2000)
We developed the landscape age‐class demographics simulator ( LADS) to model historical variability in the amount of old‐growth and late‐successional forest in the Oregon Coast Range over the past 3,000 years. The model simulated temporal and spatial patterns of forest fires along with the resulting fluctuations in the distribution of forest age classes across the landscape. Parameters describing historical fire regimes were derived from data from a number of existing dendroecological and paleoecological studies. Our results indicated that the historical age‐class distribution was highly variable and that variability increased with decreasing landscape size. Simulated old‐growth percentages were generally between 25% and 75% at the province scale (2,250,000 ha) and never fell below 5%. In comparison, old‐growth percentages varied from 0 to 100% at the late‐successional reserve scale (40,000 ha). Province‐scale estimates of current old‐growth (5%) and late‐successional forest (11%) in the Oregon Coast Range were lower than expected under the simulated historical fire regime, even when potential errors in our parameter estimates were considered. These uncertainties do, however, limit our ability to precisely define ranges of historical variability. Our results suggest that in areas where historical disturbance regimes were characterized by large, infrequent fires, management of forest age classes based on a range of historical variability may be feasible only at relatively large spatial scales. Comprehensive landscape management strategies will need to consider other factors besides the percentage of old forests on the landscape, including the spatial pattern of stands and the rates and pathways of landscape change.

CHARACTERIZATION OF CANCER CELL LINES ESTABLISHED FROM TWO HUMAN METASTATIC BREAST CANCERS - SHANKAR K. NAYAK; SURABHI KAKATI; SHASHI R. HARVEY; COLIN C. MALONE; ANDREW N. CORNFORTH; ROBERT O. DILLMAN (In Vitro Cellular & Developmental Biology - Animal, 2000)

Characterization of a mouse laminin receptor gene homologous to the human blood group Lutheran gene - C. Rahuel; Y. Colin; D. Goossens; P. Gane; W. El Nemer; J. P. Cartron; C. Le Van Kim (Immunogenetics, 1999)

Structure and expression of the mouse homologue of the XK gene - Emmanuel Collec; Yves Colin; Florence Carbonnet; Claude Hattab; Olivier Bertrand; Jean Pierre Cartron; C. Le Van Kim (Immunogenetics, 1999)

Absorption cross-sections of atmospheric constituents: NO2, O2, and H2O - Christian Hermans; Ann C. Vandaele; Michel Carleer; Sophie Fally; Réginald Colin; Alain Jenouvrier; Bernard Coquart; Marie-France Mérienne (Environmental Science and Pollution Research, 1999)

Electron-energy-loss spectroscopic imaging of calcium and nitrogen in the cell walls of apple fruits - I. Max Huxham; Michael C. Jarvis; Lynette Shakespeare; Colin J. Dover; David Johnson; J. Paul Knox; Graham B. Seymour (Planta, 1999)

Characterisation of structural tree root architecture using 3D digitising and AMAPmod software - F. Danjon; H. Sinoquet; C. Godin; F. Colin; M. Drexhage (Plant and Soil, 1999)

Changes in the location of polyphenol oxidase in potato ( Solanum tuberosum L.) tuber during cell death in response to impact injury: comparison with wound tissue - Joanna C. Partington; Colin Smith; G. Paul Bolwell (Planta, 1999)

Biome reconstruction from pollen and plant macrofossil data for Africa and the Arabian peninsula at 0 and 6000 years - Dominique Jolly; I. Colin Prentice; Raymonde Bonnefille; Aziz Ballouche; Martin Bengo; Patrice Brenac; Guillaume Buchet; David Burney; Jean‐Pierre Cazet; Rachid Cheddadi; Therese Edorh; Hilaire Elenga; et al. (Journal of Biogeography, 1998)
Biome reconstruction from pollen and plant macrofossil data provides an objective method to reconstruct past vegetation. Biomes for Africa and the Arabian peninsula have been mapped for 6000 years bp and provide a new standard for the evaluation of simulated palaeovegetation distributions. A test using modern pollen data shows the robustness of the biomization method, which is able to predict the major vegetation types with a high confidence level. The application of the procedure to the 6000 years data set (pollen and plant macrofossil analyses) shows systematic differences from the present that are consistent with the numerous previous regional and continental interpretations, while providing a more extensive and more objective basis for such interpretations. Madagascar, eastern, southern and central Africa show only minor changes in terms of biomes, compared to present. Major changes in biome distributions occur north of 15°N, with steppe in many low‐elevation sites that are now desert, and temperate xerophytic woods/scrub and warm mixed forest in the Saharan mountains. These shifts in biome distributions imply significant changes in climate, especially precipitation, between 6000 years and present, reflecting a change in monsoon extent combined with a southward expansion of Mediterranean influence.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

The petrogenesis of Tertiary cone-sheets in Ardnamurchan, NW Scotland: petrological and geochemical constraints on crustal contamination and partial melting - Jörg Geldmacher; Karsten M. Haase; Colin W. Devey; C. Dieter Garbe-Schönberg (Contributions to Mineralogy and Petrology, 1998)

Increased gene expression of plasminogen activators and inhibitors in left ventricular hypertrophy - Colin M. Bloor; Lana Nimmo; Dan McKirnan; Y. Zhang; Francis C. White (Molecular and Cellular Biochemistry, 1997)

Purification of an elicitor-induced glucan synthase (callose synthase) from suspension cultures of French bean ( Phaseolus vulgaris L.): purification and immunolocation of a probable M r -65 000 subunit of the enzyme - Barbara A. McCormack; Abigail C. E. Gregory; Maria E. Kerry; Colin Smith; G. Paul Bolwell (Planta, 1997)

Trinucleotide Microsatellite Loci and Increased Heterozygosity in Cross-Species Applications in the Social Wasp, Polistes - Joan E. Strassmann; John M. Peters; Karen Barefield; Carlos R. Solís; Colin R. Hughes; David C. Queller (Biochemical Genetics, 1997)

Rapid increases in cytokinin concentration in lateral buds of chickpea ( Cicer arietinum L.) during release of apical dominance - Colin G. N. Turnbull; Myriam A. A. Raymond; Ian C. Dodd; Suzanne E. Morris (Planta, 1997)

Ontogenetic expression of chromogranin A and its derived peptides, WE-14 and pancreastatin, in the rat neuroendocrine system - Sharon C. Barkatullah; W. J. Curry; Colin F. Johnston; John C. Hutton; Keith D. Buchanan (Histochemistry and Cell Biology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Cost-effectiveness of screening blood donors for hepatitis C and non-A, non-B, non-C hepatitis - C. Colin; P. Vergnon; A. M. Jullien; S. Excoffier; Y. Matillon; C. Trepo; J. P. Aymard; D. Bastit; M. L. Bidet; R. Breviere; F. Chenais; F. Hau; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Methylosulfonomonas methylovora gen. nov., sp. nov., and Marinosulfonomonas methylotropha gen. nov., sp. nov.: novel methylotrophs able to grow on methanesulfonic acid - Andrew J. Holmes; D. P. Kelly; Simon C. Baker; A. S. Thompson; Paolo De Marco; Elizabeth M. Kenna; J. Colin Murrell (Archives of Microbiology, 1997)

The anaerobic biodegradation of diethanolamine by a nitrate reducing bacterium - Jeremy S. Knapp; Nicholas D. Jenkey; Colin C. Townsley (Biodegradation, 1996)

Molecular analysis of methane monooxygenase from Methylococcus capsulatus (Bath) - Andrew C. Stainthorpe; J. Colin Murrell; George P. C. Salmond; Howard Dalton; Veronica Lees (Archives of Microbiology, 1989)